Techno-economic performance of an advanced process for synergistic removal of NO/SO2/CO2 via H2O2 pre-oxidation coupled with ammonia scrubbing - Jiaxing Du; Qingqing Liang; Yifan Wang; Hui Xu; Linlin Xu; Yan Liang; Guangying Wang; Lei Bei; Chuanwei Li; Zewei Zhang; Lushi Sun (Fuel, 2027)

hCG orchestrates ovulation in swamp eel (Monopterus albus) via progesterone, metabolic reprogramming, and pyroptosis - Mingsen Zhou; Linlin Wang; Shuo Zheng; Anfu Shen; Xuewen Rao; Liang Ke; Wenhao Hu; Changqing Han; Xiangjiang Liu; Guangfu Hu (Aquaculture, 2027)

Prevalence of Klebsiella pneumoniae in raw milk and biocontrol potential of phage vB_Kpn_18-1 - Ting Qin; Xinyan Yao; Dai Peng; Chaoxiang Jia; Linlin Huang; Yingqian Han; Yanbin Yang; Yang Liu; Guoyu Yang; Juan Geng; Yueying Wang; Heping Li (International Dairy Journal, 2026)

Single-cell transcriptomics reveals cellular heterogeneity and cell–cell communication networks in free gossypol-induced enteritis in juvenile largemouth bass (Micropterus salmoides) - Xinpeng Wang; Wanying Jiang; Linlin Li; Jun Wen; Limeng Wang; Shimei Lin; Yongjun Chen; Li Luo; Xinghua Zhou; Yuanfa He (Fish & Shellfish Immunology, 2026)

The impact of energy structure on sectoral carbon emissions: Evidence from China - Lei Bei; Chaolong Duan; Yongkui Du; Chao Wu; Wentao Li; Hanping Mao; Wu Yang; Ben Wang; Linlin Xu; Ruisi Wang; Xiao Liu; Lushi Sun; et al. (Energy and Climate Change, 2026)

ARHI as a key regulator of EMT and metastasis in pancreatic cancer via the Notch-1 pathway - Jingjing Liu; Yiqun Zhao; Ying Wang; Ying Shi; Qiang Zhi; Linlin Chen; Yuhao Ke; Jianlin Ren (Human Genetics, 2026)

Deposition distribution and optimization of a vertical three-zone counter-spraying device for greenhouse tomatoes - Zhongqing Sun; Yonghua Zhang; Liangchun Qi; Yumei Tang; Pei Wang; Zhenglin Liu; Linlin Yang; Xiuying Tang (Crop Protection, 2026)

Improving soil quality and wheat yield via conservation tillage in a semiarid region: A long-term field study integrating microorganisms and ecoenzymatic stoichiometry - Linlin Wang; Lingling Li; Zhuzhu Luo; Junhong Xie (Soil and Tillage Research, 2026)

KaMYB71 positively regulates drought tolerance in Krascheninnikovia arborescens - Dazhuang Qi; Yuyi Hou; Huihui Liu; Xiaodong Yu; Linlin Zheng; Yingchun Wang (Plant Science, 2026)

The spatial divergence mechanism in the ecological resilience of Qinghai spruce to compound dry-hot extremes across the northeastern Qinghai-Tibet Plateau - Xuan Li; Xiaohua Gou; Dingcai Yin; Linlin Gao; Wenhuo Liu; Dingyun Zhang; Zibo Wang; Jianye Yu (Forest Ecology and Management, 2026)

Integrated computational and in vivo evidence prioritizes MYH6 as a candidate node in PFOS-associated HCM-like cardiac remodeling - Hao Gao; Li Ma; Shiyi Tan; Xulei Zuo; Wei Wang; Linlin Zhang; Qin Ding; Rongli Sun; Yuepu Pu; Juan Zhang (Environmental Pollution, 2026)

Assessing present-day tectonic stability, sea-level change, and tsunami hazards from a coastal multi-hazard GNSS station in the southern South China Sea - Qiang Qiu; Linlin Li; Mai Ye; Hongqiang Yang; Xingyu Song; Jian Ping Yin; Tingting Zheng; Jinghe Cao; Peitao Wang; Zhanying Chen; Zhiwen Zhang; Kuilin Xiao; et al. (Engineering Geology, 2026)

Synthesis and characterization of porous carbon from Hawaii nut shells for effective CO2 capture - Xiaohan Liu; Yingyi Wang; Zhentao Chen; Xin Hu; Qiang Xiao; Leihong Zhao; Muslum Demir; Murat Kilic; Mohammed K. Al Mesfer; Linlin Wang (Biomass and Bioenergy, 2026)

UPCRISPR: an ultrafast, one-tube multiplexed nucleic acid detection system for resolving the diagnostic gray zone in HPV16/18 detection - Linlin Bai; Dianwei Liu; Chunyan Qian; Weiqi Yuan; Kaiming Guo; Yao Wang; Feng Qian; Mingmin Shi; Bei Wang; Rui Wang (Analytica Chimica Acta, 2026)

MOF-derived carbon membranes for catalytic ozonation: Site-dependent evolution of surface atomic oxygen enables efficient water purification - Guanjin Liu; Linlin Zang; Dongwei Lu; Yinkun Sun; Hui Zhang; Yichao Hu; Zhiyu Sun; Wei Wang; Zhiqiang Sun; Jun Ma (Water Research, 2026)

Effects of evidence-based perineal massage on maternal and neonatal physiological outcomes and childbirth experience in primiparous women: A quasi-experimental study - Yuxuan Li; Linlin Cao; Hongxiao He; Haishan Wei; Hong Lu; Shenglian Ni; Jie Lu; Ruiqing Dong; Mengting Wang; Xiaoding Zhou (Next Research, 2026)

Ultramicroporous N-doped carbons prepared by KHC2O4 activation for CO2 adsorption - Yujia Yin; Yingyi Wang; Ziyun Li; Ya Liu; Leihong Zhao; Muslum Demir; Aseel Zaid; Linlin Wang; Xin Hu (Journal of Environmental Chemical Engineering, 2026)

Numerical simulation of regenerative accumulator for CO2 heat pump system in electric vehicles - Linlin Wang; Jiabao Ren; Rujie Yu; Baomin Dai; Tonghua Zou (International Journal of Refrigeration, 2026)

Characteristics of overpressure and thermal effects of methane–air explosions in tunnels - Linlin Gu; Zhenjing Nie; Yi Li; Zhen Wang; Chuyuan Huang; Xianfeng Chen (Fuel, 2026)

Isolation and characterization of broad-host-range bacteriophages and their alleviation of liver and kidney injury in a mouse model of S. aureus infection - Xinyan Yao; Linlin Huang; Chaoxiang Jia; Dai Peng; Rui Cao; Xiangshun Sun; Yingqian Han; Yang Liu; Yanbin Yang; Guoyu Yang; Yueying Wang; Heping Li (Food Research International, 2026)

Ginsenoside Rk1 reprograms ‘cold’ cancer cell membranes into a ‘hot’ antigen repertoire for highly immunogenic cancer vaccines - Fangming Dong; Linlin Qu; Lebin Wang; Jing Zhao; Zhiguang Duan; Xueqing Yu; Xiaoxuan Ma; Daidi Fan (Chemical Engineering Journal, 2026)

Plasma-based biomimetic antigen outpost synergizes with immune checkpoint blockade to enhance antitumor immunity via dual inhibition of SOCS1 and PD-L1 pathways in dendritic cells - Siyuan Meng; Fangnan Lv; Jieqing Chen; Linlin Tao; Hao Guo; Danhui Wang; Jie Sun; Jian Li; Ning Liu; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2026)

Heterogeneous reaction of NO2 with hydroxyapatite particles: Effects on phosphorus water solubility - Linlin Ye; Yan Huang; Linfeng Zhang; Panya Xu; Jingjing Wang; Chengzhu Zhu; Tong Zhu; Mingjin Wang (Atmospheric Environment, 2026)

The Ecosystem Health Assessment of the Intertidal Zone in the Yellow River Delta - Shaoyu Jiang; Baoquan Li; Jiao Wang; Jing Chen; Linlin Chen (Wetlands, 2026)

Optimal grasping direction of a flexible gripper and its RGB-D multimodal estimation method - Jingwei Sun; Linlin Sun; Shuangxi Liu; Huawei Yang; Zixu Chen; Hongjian Zhang; Jinxing Wang (Computers and Electronics in Agriculture, 2026)

Nonlinear abiotic transformation of a representative organic micropollutant in a deep stratified reservoir: Critical roles of iron and dissolved organic matter - Linlin Wang; Yi Li; Longfei Wang; Li Lin (Water Research, 2026)

Representation of western boundary currents under different climatologies with varying horizontal resolutions - Hong Li; Guihua Wang; Fanghua Xu; Lijing Cheng; Junde Li; LinLin Zhang; Yuntao Wang; Wei Li; Haiqing Yu; Zenghong Liu; Zhijin Li (Progress in Oceanography, 2026)

A YjiC-like UDP-glycosyltransferase CtYjiC regulates melanization, infection-related development and virulence in Colletotrichum truncatum - Yulin Qian; Xiaoying Zhai; Qinyi Wang; Jun Liu; Linlin Zhang; Yaxin Zhang; Chunzhi Jin; Long Jin; Kee-Sun Shin; Qin Xiong (Physiological and Molecular Plant Pathology, 2026)

Moisture transport patterns over the Northeastern Tibetan Plateau revealed by tree-ring δ18O records - Kai Wang; Xiaohua Gou; Takeshi Nakatsuka; Yiran Zhang; Jiangzhou Feng; Linlin Gao; Tao Wang; Yang Deng; Zhen Li; Kaixuan Yang; Xuan Li; Chongshan Wang; et al. (Journal of Hydrology, 2026)

Network toxicology and multi-omics reveal the mechanism of testicular toxicity induced by chronic AFB1 exposure in male quails - Zhenlei Ping; Yu Wang; Linlin Fu; Xiaoying Cui; Songtao Zheng; Xiaowen Jiang; Wenhui Yu (Journal of Hazardous Materials, 2026)

Organophosphate flame retardants and incident type 2 diabetes: Integrating population evidence, mechanistic insights, and effect modification by healthy lifestyle - Xueyan Wu; Yilin Zhou; Yue Nie; Haoran Xu; Hengrui Liu; Mengke Cheng; Yao Guo; Fangyuan Lin; Xin Tang; Peihan Chen; Dandan Wei; Jian Hou; et al. (Journal of Hazardous Materials, 2026)

Unique coordination of four-metal-atom clusters on C5N2H2 boosts nitrogen reduction reaction performance: a DFT study - Linlin Li; Shaopeng Xu; Yan Yan; Mengmeng Wang; Yan Chen; Jiaojiao Chen; Wei Li; Xunlei Ding (Fuel, 2026)

Genomics-driven risk assessment of antimicrobial resistance: Current status, challenges, and future perspectives - Peipei Cheng; Qian Wang; Wanting He; Xueyuan Zhu; Yu Cheng; Linlin Xiao; Qingli Dong (Food Research International, 2026)

Rural domestic waste generation characteristics and treatment-related greenhouse gas emissions: A case study of Guangdong Province, China - Yao He; Jie Zhang; Chen Lin; Linlin Xia; Yazhuo Wang; Hewen Zhou; Xun-an Ning (Environmental Pollution, 2026)

Porous solar evaporator with hierarchical photothermal structure for highly-performance desalination and water remediation - Yuqian He; Chunguang Liu; Linlin Yan; Mi Zhou; Kai Wang; Yingjie Zhang; Xi Quan Cheng (Chemical Engineering Journal, 2026)

A dual-modified NASICON cathode achieving 15,000 cycles and wide-temperature operation (−20 to 55 °C) for practical sodium-ion batteries - Linying Yuan; Yuping Liao; Bing Han; Tianchen Shen; Kai Wang; Luyang Chen; Shigang Lu; Linlin Wang (Chemical Engineering Journal, 2026)

Metagenomic insights into the distribution and potential influencing factors of antibiotic resistance genes in historically polluted lake sediments - Jinyang Fu; Zhunjie Li; Caixi Hu; Linlin Yao; Mengxi Cao; Yiran Dong; Pu Wang; Yong Liang; Lei Tong; Jianbo Shi (Aquatic Toxicology, 2026)

Aurantio-Obtusin Attenuates Aβ-Induced Cognitive Impairment and Synaptic Dysfunction by Suppressing Neuroinflammation in Mice - Xueying Feng; Wei Yu; Song Guo; Yanyan Ji; Junhua Li; Ling Wang; Guolu Zhong; Shiyi Li; Linlin Niu; Danxin Zhu; Kan Zhou; Yehong Du (Journal of Neuroimmune Pharmacology, 2026)

Antibiotics and antibiotic resistance genes increase cyanobacterial blooms by altering microbial nitrogen transformations in water and sediment - Linlin Zhu; Tao Huang; Bo Wang; Lijun Zhou; Qingye Sun; Kaining Chen (Water Research, 2026)

Retraction notice to “Study on the effect of SDBS and SDS on deep coal seam water injection” [Sci. Total Environ. 856 (2023) 158930] - Lianman Xu; Yajing Li; Linlin Du; Fengshuo Yang; Runjie Zhang; Hao Wei; Gang Wang; Zhe Hao (Science of The Total Environment, 2026)

Biodegradable piezoelectric suture for real-time biomechanical sensing and therapeutic intervention - Quanhong Hu; Chuyu Tang; Zhirong Liu; Shaobo Wang; Zhuo Wang; Genglin Chen; Shuncheng Yao; Zhuoheng Jiang; Songjing Zhong; Yuxuan Zhang; Linlin Li (Science Bulletin, 2026)

Hydrothermal response to changes in snow and vegetation cover in Xinjiang, China - Huimin Yang; Yuehong Ran; Yichi Xu; Lihong Wang; Linlin Cui; Xiangqian Li; Mengwen Peng (Journal of Environmental Management, 2026)

Synergistic enhancement of heavy rare earth elements leaching from ion-adsorption rare earth ores using fungal metabolites supplemented with ammonium sulfate - Yun Fang; Hailan Wang; Linlin Yan; Jianxiong Zeng; Siqi Chen; Jun Liu; Guowei Wang; Yang Liu; Jun Wang; Chunqiao Xiao (Hydrometallurgy, 2026)

Ambient-temperature hydrogen storage kinetics of magnesium-based composites enabled by acetone-assisted ball milling and TiF3 catalysis - Linlin Zhang; Qingyun Shi; Chunmin Zhang; Bingbing Chen; Chunli Wang; Limin Wang; Yong Cheng (Fuel, 2026)

Co-combustion of municipal solid waste and antibiotic fermentation residue: Gaseous pollutant emissions and ash slagging characteristics - Changhong Huang; Yuhang Du; Lei Bei; Jiaxing Du; Wu Yang; Ben Wang; Linlin Xu; Lushi Sun (Fuel, 2026)

Effect of coupled temperature-humidity drying on multi-scale structure and in vitro digestibility of corn resistant starch - Qing Su; Lirong Chen; Linlin Sun; Xingya Wang; Yuqiu Guo; Meimei Zhao; Kaichang Liu; Kuijie Gong (Food Chemistry, 2026)

High internal phase emulsions stabilised by amyloid fibrils from 7S/11S soybean protein at varying ratios: Study on interfacial behaviour, rheological properties and curcumin delivery potential - Tianlu Han; Ruqi Guo; Yuexin An; Yuyang Huang; Linlin Liu; Zihan Wang; Ying Zhu; Xiuqing Zhu (Food Chemistry, 2026)

An accelerated XFEM framework for fatigue crack propagation analysis of shield tunnel linings subjected to cyclic train loads - Wenbo Yang; Zhenian Wang; Linlin Yang; Ziyuan Su; Yang Zhou; Chaofan Yao; Fangyin Wu (Computers and Geotechnics, 2026)

NAS-PINNv2: Improved neural architecture search framework for physics-informed neural networks in low-temperature plasma simulation - Yifan Wang; Linlin Zhong (Computer Physics Communications, 2026)

Enzymatic synthesis of oligodextran with prebiotic potential by a recombinant dextransucrase from Latilactobacillus sakei L3 - Binbin Wang; Linlin Hao; Kaiyue Zuo; Xiaojing Liu; Huimin Yao; Weizhong Liu; Fangkun Zhao; Lei Pan; Baomei Wu (Carbohydrate Polymers, 2026)

Exploring Co-occurrence Patterns of Macrobenthic Communities Across Intertidal and Offshore Zones in the Yellow River Delta, China - Jiao Wang; Shaoyu Jiang; Debin Sun; Jing Chen; Baoquan Li; Linlin Chen (Wetlands, 2026)

Understanding eco-hydrological processes in winter wheat croplands through physically consistent modelling - Linlin Li; Yunfei Wang; Aofan Cui; Xinyu Mao; Wenjun Zhao; Wei Li (Theoretical and Applied Climatology, 2026)

2-Methoxyestradiol Suppresses Stemness and Epithelial-Mesenchymal Transition in Drug-Resistant Esophageal Squamous Cell Carcinoma by Targeting the Snail Signaling Pathway in Cancer Stem Cells - Jie Yan; Shuhua Han; Keqi Zhang; Linlin Li; Mingjing He; Haoqing Cao; Meiru Zhu; Bingjie Bi; Qiang Xu; Cong Wang (Stem Cell Reviews and Reports, 2026)

Role of M1 macrophage-derived exosomes in infantile hemangioma regression via AMPK/SIRT1/PGC1α pathway - LinLin Yue; XiuWen Zheng; XiaoQiang Wen; Yong Zeng; Wei Peng; QianDuo Li; LinShan Zeng; JinPing Liu; Yu Wang; WenQing Fu; HaiJin Liu; Feng Chen (Molecular & Cellular Toxicology, 2026)

Interdecadal change in triggering effect of subtropical Indian Ocean dipole on tropical Indian Ocean dipole and the role of Southern annular mode - Junqiao Feng; Linlin Zhang; Fujun Wang (Climate Dynamics, 2026)

Benthic Fauna of Foraminifera and Their Distribution Pattern in Sishili Bay, Northern Yellow Sea, China - Tatyana S. Tarasova; Baoquan Li; Yulia A. Trebukhova; Ilia A. Shcherbakov; Aleksandra V. Romanova; Konstantin A. Lutaenko; Jiao Wang; Jing Chen; Linlin Chen (Journal of Ocean University of China, 2026)

Performance and wastewater treatment efficiency of artificially prepared aerobic granular sludge - Xuanzhe Yan; Jinlong Wang; Kailong Liu; Hao Wu; Wei He; Yongmei Zhang; Linlin Tong; Su Li; Zhaoyang You (Biodegradation, 2026)

Clinical and Molecular Characterization of Five Additional Individuals With SATB2-Associated Syndrome in Guangxi - Sheng Yi; Qinle Zhang; Fei Chen; Xunzhao Zhou; Qiang Zhang; Shang Yi; Xiaofei Zhang; Jiale Qian; Linlin Wang; Shujie Zhang; Biyan Chen; Zailong Qin; et al. (Biochemical Genetics, 2026)

Microbiological safety of dehydrated foods: risk analysis, technology evaluation, and synergistic strategies for next-generation processing - Yu Wang; Wenchao Liu; Linlin Li; Weiwei Cao; Junliang Chen; Chung Lim Law; Guangyue Ren; Xu Duan (Critical Reviews in Food Science and Nutrition, 2026)

Breakage mitigation optimization strategy for a spiral-groove wheel fertilizer distributor based on a controlled-release fertilizer breakage model - Hongjian Zhang; Xiubo Chen; Xinpeng Cao; Yongxian Wang; Xin Han; Junshuo Xu; Linlin Sun; Jing Wang; Linlong Jing; Jinxing Wang (Computers and Electronics in Agriculture, 2026)

Co-adaptive dynamics of human activity and crop Climatic Niches in the Neolithic Wei River Valley, China (8000–4000 cal. BP) - Xiang Jinhui; Shao Bingxin; Zhou Mile; Wang Yanpeng; Zhai Linlin; Chen Honghai; Zhang Gaike; Ma Zhikun (Quaternary Science Reviews, 2026)

Structural snapshots of plant-specific KCS6-CER2 complex reveal the elongation mechanism of very-long-chain fatty acids - Yang Wang; Haiyan Wang; Xianpeng Yang; Yujiao Qin; Rangwei Xu; Ting Liu; Chunmei Shi; Hongyan Zhang; Linlin Zhong; Xiaolu Qu; Feng Zhu; Xiuxin Deng; et al. (Molecular Plant, 2026)

Photothermal-enhanced capillary/siphon-driven self-priming pump for highly efficient recovery of various oils - Feilong Liu; Linlin Yan; Yingjie Zhang; Jun Ma; Pengcheng Liu; Longjun Wang; Da long Li; Xiquan Cheng (Journal of Hazardous Materials, 2026)

Numerical simulation and improvement of the temperature rise evolution during the Cryo-compressed hydrogen filling process in type III vessels - Linlin Gao; Haocheng Wang; Bo Tang; Teng Zhang; Xueqiang Dong; Maoqiong Gong (International Journal of Refrigeration, 2026)

Insights into Cronobacter sakazakii adaptation to Benzalkonium chloride: virulence assessment and transcriptomics analysis - Hongmei Niu; Xiang Wang; Yuan Wang; Xiaojie Qin; Lei Fang; Jianwen Gao; Yanqi Zhou; Linlin Xiao; Qingli Dong (Food Research International, 2026)

Effects of the foliar application of selenite at different growth stages on selenium transformation, silage quality and the metabolome of tiger nut (Cyperus esculentus L.) - Kexin Wang; Ting Gong; Xinge Du; Wei Liu; Ruize Sun; Chenghao Che; Yilin Zou; Shengnan Sun; Linlin Mei; Guofu Hu (Food Chemistry, 2026)

Lymph node–targeting GM-CSF vesicles produced in situ by ultrasound-activated bacterial factories for enhanced immunotherapy - Yue Yuan; Beibei Zhang; Shaobo Duan; Ruiqing Liu; Juan Zhang; Rui Zhang; Qi Zhou; Linlin Zhang; Xiaoxia Xu; Zesheng Li; Yuanyuan Liu; Xiaoxiao Li; et al. (Chemical Engineering Journal, 2026)

Fabrication of aramid nanofiber/silver nanoparticles composite aerogels for enhanced electromagnetic interference shielding - Mingyan Wang; Linlin Cheng; Jinxiao Hou; Shaojuan Chen; Liang Jiang; Yanfen Zhou (Chemical Engineering Journal, 2026)

Pharmacovigilance insights into drug-induced hypercalcemia: evidence from the U.S. FDA Adverse Event Reporting System (FAERS) database - Wensheng Liu; Linlin Wang; Xue Song; Xuan Ye; Yunlan Ding; Jiyong Liu; Qiong Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

An NDVI-constrained multi-source remote sensing data fusion network for detecting the level of larch caterpillar (Dendrolimus superans) infestation - Linlin Wu; Mingchang Wang; Fengyan Wang; Dehua Mao (Journal of Mountain Science, 2026)

Extreme warming and pulsed volcanism during the Paleocene-Eocene Thermal Maximum - Abdelhamid M. Salman; Xue-Ting Wang; Zuoling Chen; Linlin Cui; Hongwei Li; Xu Wang (Science China Earth Sciences, 2026)

Triggering Effect of Indian Ocean Dipole on Subtropical Indian Ocean Dipole: Interdecadal Change and Modulation by Interdecadal Pacific Oscillation - Junqiao Feng; Linlin Zhang; Fujun Wang (International Journal of Climatology, 2026)
Based on observational and reanalysis datasets, this study examines the relationship between the tropical Indian Ocean Dipole (IOD) that matures in boreal autumn and the subsequent Subtropical Indian Ocean Dipole (SIOD) that occurs in the following boreal winter, as well as its interdecadal variability over 1960–2024. Results suggest that a significant correlation between IOD and SIOD only exists in 1979–2005. During this strong correlation period, an intense IOD can trigger a persistent meridional circulation and mid‐latitude Rossby wave train, maintaining an anomalous cyclone–anticyclone pair (CACP) over the subtropical Indian Ocean, with the cyclone in the west and the anticyclone in the east, ultimately leading to the development of SIOD via local air–sea coupling. In other periods, this relationship weakens and the described coupling pathway fails to establish. A key factor enabling this efficient cross‐seasonal linkage is the presence of sustained oceanic memory. Specifically, the sea surface temperature and subsurface heat anomalies associated with the IOD persist from boreal autumn into winter, providing a thermal precondition that interacts with the atmospheric circulation to eventually develop the SIOD. Further analysis indicates that this interdecadal variation is modulated by the Interdecadal Pacific Oscillation (IPO). Specifically, the positive phase of IPO strengthens the Indo–Pacific Walker circulation anomaly, reinforces the tropical–subtropical meridional pathway, and thereby enhances the IOD's triggering effect on SIOD. In contrast, the negative IPO phase suppresses this pathway. This study offers new mechanistic insights that advance our understanding of cross‐seasonal interactions in the Indian Ocean and contribute to improved climate predictions. Furthermore, it clarifies the importance of accounting for non‐stationarity in the climatic background for seasonal forecasting.

Prenatal Cerium Exposure and Neural Tube Defect Risk: A Case-control Study in Shanxi, China - Jing Wei; Fuyuan Yin; Zuqun Jin; Ning Kang; Dezheng Fu; Tian Tian; Yun Huang; Zhiwen Li; Linlin Wang; Lei Jin; Aiguo Ren; Shengju Yin (Biological Trace Element Research, 2026)

Antibacterial and antioxidant activity of ginsenosides from ginseng rootlets and their application in beef preservation - Junshun Zhang; Maoyu Wang; Suwan Lu; Yuhui Zhi; Luchen Bi; Yuxian Wang; Linlin Yin; Yi Wang; Zhina Chen (World Journal of Microbiology and Biotechnology, 2026)

Mechanistic study of wheat straw-enhanced sulfur release and denitrification in a pyrite-based bioretention system: Iron–sulfur–carbon synergistic interactions - Zhaoyang You; Jinlong Wang; Tao Wang; Xi Chen; Yongmei Zhang; Su Li; Linlin Tong; Kinjal J. Shah (Chemosphere, 2026)

Rupture characteristics and liquefaction-induced mudflow mechanisms of the 2023 Jishishan Ms. 6.2 earthquake on the northeastern Tibetan Plateau margin - Junyi Wang; Weimin Wang; Linlin Li; Chao Wang; Jiankun He; Lin Ding (Tectonophysics, 2026)

Exposure to polycyclic aromatic hydrocarbons during maternal pregnancy: Effects of DNA damage on neural tube defects in offspring - Xiaoqian Jia; Yingfeng Gao; Yuan Li; Ruiwei Xu; Lei Jin; Linlin Wang; Aiguo Ren; Le Zhang; Yali Zhang; Shanshan Lin; Jicheng Gong; Zhiwen Li (Journal of Hazardous Materials, 2026)

Lactiplantibacillus plantarum enables metal recovery from spent LiNi0.33Co0.33Mn0.33O2 cathode via EPS-mediated synergistic bioleaching - Min Li; Hong Wang; Danni Zhang; Zhong Li; Qiuli Xia; Xianjun Guan; Yaojie Yu; Linlin Tong; Junting Tong; Yongqiang Fan; Fuhui Wang; Dake Xu (Journal of Hazardous Materials, 2026)

Built-in electric field engineering in boron and bithiophene Co-doped carbon nitride for boosting photodegradation: Mechanism and toxicity assessment - Siyi Wang; Ting Wang; Liang Wang; Tianyu Zhou; Linlin Liu; Chunbo Liu (Journal of Environmental Chemical Engineering, 2026)

Nitrogen cycle suppression and enhanced carbon burial during the Paleocene-Eocene thermal maximum, recorded from Tarfa section, Egypt (Tethys Ocean) - Abdelhamid M. Salman; Xueting Wang; Zuoling Chen; Hongwei Li; Linlin Cui; Nageh A. Obaidalla; Xu Wang (Global and Planetary Change, 2026)

Mechanism of texture formation in dried fruits and vegetables: from macroscopic to the molecular level - Rongtian An; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Min Zhang; Chung Lim Law; Xu Duan (Food Control, 2026)

3-mercaptopropyltriethoxysilane modified zein electrospun membrane for ethylene removal and its application to banana preservation - Feng Xiao; Yimeng Zhang; Haoran Wang; Ji Wei; Linlin Li; Hualin Wang (Food Packaging and Shelf Life, 2026)

Breaking the trade-off: A phosphorylated interpenetrating network bridging ion-conduction pathways for safe and high-performance solid-state batteries - Yuyang Wang; Linlin Wang; Jie Yang; Qiuya Wang; Junye Zhang; Cheng Liu; Zaichao Zhang; Le Xu; Rundong Chen; Tianchen Shen; Shigang Lu; Luyang Chen (Chemical Engineering Journal, 2026)

Responses of sedimentary magnetic susceptibility and metal contents to climate and anthropogenic activity changes: examination on lake records across the Asian monsoon region - Haiyang Yu; Shuangchi Liu; Jule Xiao; Xu Wang; Linlin Cui; Licheng Guo; Xueting Wang; Shihao Zhang (CATENA, 2026)

Impacts of different physics schemes on hurricane forecasting in the unified forecast system (UFS) - Linlin Pan; Kathryn Newman; Mrinal Biswas; Brianne Nelson; Bin Liu; Zhan Zhang; Xuejin Zhang; Shuanglong Jin; Zongpeng Song; Rui Hu; Shuanglei Feng; Bo Wang; et al. (Atmospheric Research, 2026)

CLEC14A mediates trophoblast dysfunction in unexplained miscarriage by disrupting the cAMP/ERK signaling pathway - Jianing Wang; Yawei Shao; Linlin Zhou; Ruyue Ma; Shunli Dong; Ruiheng Zhao (Journal of Molecular Histology, 2026)

ABEEM/MM Magnesium Force Field for Proteins and Aqueous Solutions - Jing Zhang; Linan Lu; Runqiang Yu; Linlin Liu; Lei Wang; Cui Liu; Lidong Gong; Zhongzhi Yang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Comparison of Turbulent Transport Dissimilarity and the Role of Coherent Structures in the Unstable Surface Layer Between Urban and Rural Areas - Qiyue Sun; Lu Zhang; Jiesheng Xue; Linlin Wang; Yubin Li; Yuanjian Yang (Boundary-Layer Meteorology, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Cohort Profile: The Chinese Ovarian Aging Cohort (COACH) - Changjing Wang; Tingting Meng; Wei Luo; Jiangtao Zhang; Yongzhi Cao; Cheng Li; Jing Zhang; Xuan Gao; Peihao Liu; Chenxi Li; Dongshan Zhu; Tao Zhang; et al. (Phenomics, 2026)

Linking genetic connectivity and ecological niche similarity to inform coastal biosecurity management: a global case study of Mytilopsis sallei - Hao Dong; Linlin Zhao; Liuyi Huang; Xiaoyang Wang; Changdong Liu (Ocean & Coastal Management, 2026)

Polyphenol oxidase-mediated browning during storage of Pinus elliottii oleoresin: characterization of pine-needle PPO and antibrowning action of L-cysteine - Siheng Zhang; Hanxiao Liu; Jingcong Liu; Lu Qin; Xin Li; Xuanrou Wei; Xiaopeng Chen; Linlin Wang (Food Bioscience, 2026)

Effects of combined selenium and sulfur application on glucosinolate biosynthesis in Chinese cabbage sprouts - Huixia Bai; Linlin Zhao; Yafang Luo; Qi Hu; Lingling Liu; Yang Chen; Huan Wang; Yushu Wang (Physiology and Molecular Biology of Plants, 2026)

Advances in bacterial synthesis pathways of bioflocculants and their applications in mine wastewater treatment - Linlin Zhang; Zhaofeng Liu; Qiang Guo; Jiawei Tang; Xiaoduan Li; Qun Wang (World Journal of Microbiology and Biotechnology, 2026)

LDH-based avermectin nanopesticide modulates bioaccumulation, antioxidant responses, and microbiota stability in earthworms' gut - Shuting Yang; Yiqiong Li; Chao Zong; Xinglu Pan; Haonan Wang; Qingkui Fang; Linlin Shi; Fengshou Dong; Haiqun Cao (Pesticide Biochemistry and Physiology, 2026)

The role of microplastics in bioavailability and toxicity of triclosan in the soil-earthworm system: Inhibitor or facilitator - Xian Chen; Jingcheng Liang; Linlin Shi; Shipeng Luo; Rong Ji; Jiehong Cheng; Ying Wu; Yuchen Wang (Journal of Environmental Chemical Engineering, 2026)

Efficient hydrogenation of heavy turpentine into high-energy-density biofuel over MOF-derived nano-Ni@C/rGO and associated kinetic insights - Xiaoying Tang; Yongxiong Yang; Ying Tang; Shen Luo; Xiaopeng Chen; Xu Wei; Linlin Wang (Journal of Environmental Chemical Engineering, 2026)

Unlocking circularity in rural waste management in northwest China: A systematic framework to quantify energy-environment-pollution nexus - Yuansheng Huang; Linlin Wang; Yi Liu; Yihan Chen; Xinglin Zhang; Yiliang He (Journal of Cleaner Production, 2026)

DMSO intercalation tunes antibiofouling properties of MXene/PVDF composite membranes: Toward sustainable wastewater treatment - Chenhong Cheng; Yuanyuan Zhang; Haochuan Yang; Jie Zhang; Linlin Yang; Rubing Dong; Jiayi Cui; Yongli Qin; Xueye Wang; Xingran Zhang; Jinxing Ma; Junjian Zheng (Journal of Environmental Chemical Engineering, 2026)

The biotransformation and toxicity of sulfamethoxazole in phycosphere indicates potential in-situ removal of antibiotics by microalgae - Qing Wang; Linlin Geng; Yanbin Ma; Jie Wang; Ka Zhang; Jiao He; Shang Ren; Yan Sun; Xuli Li; Shaojing Sun; Yi Luo (Journal of Environmental Chemical Engineering, 2026)

Engineering the 1T/2H-MoSe2 phase junction as an S-scheme cocatalyst for boosted photocatalytic hydrogen evolution - Linlin Gao; Yamei Huang; Jiayi Meng; Yifan Liao; Zizheng Wang; Quanmei Zhou; Yuchen Wei; Wei-Lin Dai (Journal of Environmental Chemical Engineering, 2026)

Association of prenatal exposure to polychlorinated biphenyls with cleft lip and/or palate risk in offspring: A case-control study - Sainan Li; Shujian Lin; Yongyan Chen; Yiqi Ding; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Journal of Environmental Sciences, 2026)

Insights into the mechanism of nutty aroma formation by Staphylococcus saprophyticus in fermented sausages - Jikun He; Youqin Duan; Shuting Yang; Fidel Toldrá; Jiong Zheng; Muying Du; Linlin Wang; Nodali Ndraha; Shuyao Wang; Juan Chen (International Journal of Food Microbiology, 2026)

Seven neonicotinoids and twenty-two metabolites in seven food matrices by optimized QuEChERS-HPLC-MS/MS and dietary risk assessment - Zhenzhen Zhou; Xueyan Zhao; Junfeng Lu; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie; Fajun Tian (Food Chemistry, 2026)

Multifunctional nanoemulsion co-delivering Lactobacillus plantarum supernatant and Litsea cubeba essential oil: Construction and application in fiddlehead fern preservation - Jiayue Song; Dengyi Ye; Wenjia Li; Qiao Guo; Yanan Zhang; Xiyu Wang; Ping Tang; Ping Chen; Linlin Xu (Food Bioscience, 2026)

Characterization of a novel lytic Mooglevirus phage to control Salmonella Senftenberg and its application in foods - Jiayi Xue; Tingyu Liu; Linlin Xiao; Jiuchao Zhu; Yi Hong; Xiang Wang; Jinghang Zhang; Hengyi Hu; Zhuosi Li; Qingli Dong; Xiaojie Qin (Food Control, 2026)

Advances in the understanding of spatiotemporal distribution and hazard assessment of volcanic tsunamis - Kan Zhang; Linlin Li; Peng Du; Tingting Fan; Weitao Wang; Peizhen Zhang (Science China Earth Sciences, 2026)

Proteostasis Collapse Drives Effector Memory T Cells Re-expressing CD45RA (TEMRA) Generation in the Tumor Microenvironment - Linlin Li; Shuo Kan; Qiang Huang; Shiwen Wang; Yuchen Han; Liang Chen; Jun Jin (Phenomics, 2026)

Association Between Maternal Exposure to Eight Metals at Everyday or Low Levels During the Periconceptional Period and Risk for Fetal Congenital Heart Defects: A Case-Control Study in China - Xin Pi; Chunyi Liu; Xiaoqian Jia; Yali Zhang; Jufen Liu; Linlin Wang; Zhiwen Li; Aiguo Ren; Lei Jin (Exposure and Health, 2026)

Resilient-based seismic design of a seismically isolated multitower-connected building - Xinyu Wang; Linlin Xie; Demin Zeng; Tao Wang; Aiqun Li (Earthquake Engineering and Engineering Vibration, 2026)

Biochar and manure amendments mitigate chemical-fertilizer-induce negative effects on soil microbiomes, with implications for crop productivity gain - Pan Jiang; Hao Huang; Jinmeng Hu; Linlin Wang; Yuping Zhang; Xiangmin Rong; Jianwei Peng; Gongwen Luo (Applied Soil Ecology, 2026)

Hominin occupation of the Western Qinling Mountains as early as ∼900 ka - Zaijun Li; Jian Wang; Chongwen Luo; Yongbo Quan; Linlin Yan; Yuanxin Li; Linxueyi Wang; Shengli Yang; Jia Jia; Ziwei Tao; Tingjiang Peng; Zhenzhong Tian; et al. (Science Bulletin, 2026)

Coastal land reclamation induced estuarine nutrient-related eutrophication stressors: phenomena, evaluation and management strategies - Linlin Wang; Yuehua Guo; Wenbin Liu; Huaihao Shao; Shuangliang Dai; Lin Mu; Xianzhong Mao; Hongsheng Bi; Kai Zhou; Xiaoyu Lei (Journal of Hydrology, 2026)

Pretreatment-driven shrinkage regulation in Chinese yam during multiphase microwave drying - Rongtian An; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Min Zhang; Chung Lim Law; Xu Duan (Journal of Food Engineering, 2026)

Selective separation of rare earth from acetatesolution containing aluminum by nonequilibrium extraction - Linlin Chang; Jian Li; Dongyue Xie; Xudong Liu; Yaobin Lai; Jiayi Zan; Chenjiahui Wang; Yangyang Xie; Xuxia Zhang; Hui Zhang; Tao Qi; Rongde Li; et al. (Journal of Environmental Management, 2026)

Source and accumulation of helium in the Dongsheng gas Field, Ordos Basin, China: Insights from noble gas isotopes - Yu Gao; Shuangjian Li; Xiaoqi Wu; Dongya Zhu; Pengpeng Li; Linlin Wang; Guangxiang Liu; Jiahao Lv; Jiarun Liu; Quanyou Liu (Journal of Asian Earth Sciences, 2026)

Effects of Lactiplantibacillus plantarum and Staphylococcus simulans fermentation on Maillard reaction and flavor characteristics in a myofibrillar protein-glucose reaction system - Xuefei Shao; Huhu Wang; Xiangyu Song; Xue Gong; Linlin Cai; Xinglian Xu (Food Chemistry, 2026)

Chemical and sensory characteristics of Baiye No.1 (BY1H) yellow tea: Insights into flavoring mechanism and quality valuation - Shiyu Zhang; Xinzhuan Yao; Yanxia Wang; Muhammad Safiullah Virk; Shiyu Tian; Zhenkedai Yuan; Qihong Zou; Linlin Li; Shenyuan Ye; Hu Tang; Litang Lu (Food Bioscience, 2026)

Amyloid fibrillation of different ratios of 7S/11S soy protein: comparison of fibril structural characteristics and analysis of the potential for preparing high-internal-phase emulsions - Tianlu Han; Lidan Qiu; Qinlin Hu; Ruqi Guo; Ying Zhu; Yuyang Huang; LinLin Liu; Ying Wang; Xiuqing Zhu (Food Hydrocolloids, 2026)

Occurrence, composition profiles, and human exposure assessment of liquid crystal monomers in indoor dust from Wuxi, China - Yiyang Yao; Linlin Wu; Run Zhou; Xi Wang; Yan Gong; Rong Chen; Wenwei Liu (Environmental Pollution, 2026)

Potential folate-depleting effect of organochlorine pesticide exposure in elevating homocysteine levels - Tian Tian; Ning Kang; Dezheng Fu; Linlin Wang; Lei Jin; Zhiwen Li; Jun Zhang; Jie Qiao; Aiguo Ren; Shengju Yin (Environmental Pollution, 2026)

Synergistic effects of crystal-facet on dehalogenation kinetics and poison tolerance of Pd-based electrocatalytic membranes for efficient removal of halogenated pollutants - Yinkun Sun; Dongwei Lu; Xianci Pan; Rongxin Zeng; Zhiyu Sun; Xueying Chen; Yumei Wang; Qingcan Zhou; Yichao Hu; Linlin Zang; Guanjin Liu; Jun Ma (Chemical Engineering Journal, 2026)

Deubiquitinases in liver diseases: from mechanisms to targeted therapy - Zhenge Zhang; Wanli Duan; Yixiang Wang; Peng Hao; Linlin Chen; Ziyi Hao; Ming He; Yingli Wu; Hao Luo (Science China Life Sciences, 2026)

An overview of GNSS for tsunami early warning: From lithosphere to ionosphere - Kejie Chen; Haishan Chai; Jiafeng Li; Guoguang Wei; Mingzhe Lyu; Wenfeng Cui; Chuang Shi; Linlin Li; Peitao Wang; Wei Lu; Jian Lin (Science China Earth Sciences, 2026)

Damage and Creep Response of Tunnel Lining Concrete at Elevated Temperatures - Linlin Yao; Linlin Gu; Zhen Wang; Zhiquan Huang; Fei Gao (Geotechnical and Geological Engineering, 2026)

The intra-annual tree-ring δ18O records from the northeastern Tibetan Plateau can reflect seasonal variations of relative humidity and the intra-annual distribution of precipitation - Kai Wang; Xiaohua Gou; Takeshi Nakatsuka; Yiran Zhang; Tao Wang; Linlin Gao; Yang Deng; Zhen Li; Kaixuan Yang; Xuan Li; Chongshan Wang; Zibo Wang (Agricultural and Forest Meteorology, 2026)

Tidal irrigation-based rice cultivation enhances coastal blue carbon and decreases GHG emissions in brackish mudflats - Lang Zhang; Linlin Li; Hualei Yang; Wenbang Tang; Ji Chen; Hongkai Zhou; Ying Huang; Xuechu Chen; Xiuzhen Li; Ming Luo; Xingyun Huang; Faming Wang; et al. (Agricultural and Forest Meteorology, 2026)

Insights into low temperature adaptation in Epinephelus awoara through integrated genome and transcriptome analysis - Linna Wang; Shuai Chen; Zhentong Li; Yang Liu; Shihao Wang; Tangtang Ding; Fengfan Yang; Chunbai Zhang; Linlin Li; Wensheng Li; Qingbin Wang; Xia Zhao; et al. (Aquaculture, 2026)

sRNA networks as molecular switches: Decoding foodborne bacterial pathogen adaptation from farm to fork to clinic and prospects for next-generation precision interventions - Linlin Cai; Huhu Wang; Yunting Xie; Xinglian Xu; Guanghong Zhou (Trends in Food Science & Technology, 2026)

Endophytic fungi-mediated drought tolerance in spring wheat under no-tillage with straw cover on the Loess Plateau, China - Changliang Du; Lingling Li; Junhong Xie; Khuram Shehzad Khan; Linlin Wang; Zhuzhu Luo; Lingzhi Li; Zechariah Effah; Muhammad Zahid Mumtaz (Soil and Tillage Research, 2026)

From firm to soft: Maturity-driven mechanical damage behavior of apples - Zixu Chen; Linlong Jing; Ruofei Liu; Huawei Yang; Linlin Sun; Xinpeng Cao; Yongxian Wang; Shenghui Fu; Hongjian Zhang; Jinxing Wang (Postharvest Biology and Technology, 2026)

Cadmium exposure is associated with impaired ovarian function: Potential role of cadmium-induced ferroptosis in granulosa cells - Jing Li; Yutong Wang; Yali Huang; Nidong Li; Yingxin Zhu; Shengli Lin; Linlin Wang; Wei Guo; Lailai Yan; Chan Tian; Ying Wang (Journal of Hazardous Materials, 2026)

Analysis of shrinkage deformation behavior in microwave vacuum drying of Chinese yam based on evolution of physical properties - Qian Zhou; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Tongxiang Yang; Junliang Chen; Guangyue Ren; Chung Lim Law; Xu Duan (Journal of Food Engineering, 2026)

The sequestration of metal nanoparticles in the liver: A trade-off between density and degradability - Junjie Ma; Li Zeng; Yaquan Liu; Shunhao Wang; Min Li; Linlin Yao; Gang Tang; Ziniu Wang; Jiexia Cheng; Qi Wu; Guangxuan Wang; Chunzhen Shi; et al. (Journal of Environmental Sciences, 2026)

Influence of pore fluid on the elasto-plastic property of shales - Linghao Chen; Wanqing Shen; Shuitao Zhang; Zhilei Luo; Jianfu Shao; Linlin Wang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Globally synchronous acceleration of soil formation approximately 12,000 years ago - Licheng Guo; Qiaowen Zhang; Haozhong Xue; Shangfa Xiong; Shiling Yang; Zihua Tang; Linlin Cui; Jingyi Cui; Yongda Wang; Shihao Zhang (Global and Planetary Change, 2026)

Cultured meat protein has significantly higher digestibility and more potential bioactive peptides than traditional animal and plant proteins - Yunting Xie; Shijie Ding; Jie Wang; Chong Wang; Linlin Cai; Xiufeng Li; Guanghong Zhou; Chunbao Li (Food Chemistry, 2026)

Mechanism of physicochemical changes in potato starch gel induced by citric acid-autoclaving for texture improvement and resistant starch formation - Linlin Cui; Xinzhu Wang; Shuhan Ge; Xia Li; Yu Wang; Bo Nan; Zhicheng Zhang; Yuhua Wang (Food Chemistry, 2026)

Unveiling structural evolution during high-moisture extrusion of soy protein isolate-wheat gluten systems with soy dietary fiber: A sudden shutdown-based study - Ruqi Guo; Haojia Zhang; Yang Gao; Zihan Wang; Yinlin Wang; Ying Zhu; Linlin Liu; Xiuqing Zhu (Food Chemistry, 2026)

Development and application of a numerical model of an asynchronized parallel double-stage fluid viscous damper for seismic responses control based on OpenSees - Linlin Xie; Haoxiang Wang; Cantian Yang; Aiqun Li; Yue Chen (Engineering Structures, 2026)

Enhanced selectivity for the removal of Al3+ from the simulated rare earth leachate via a 3D electrochemical hydrolysis process - Chenjiahui Wang; Jian Li; Dongyue Xie; Xudong Liu; Jiayi Zan; Linlin Chang; Yaobin Lai; Yangyang Xie; Xuxia Zhang; Hui Zhang; Tao Qi; Rongde Li; et al. (Desalination, 2026)

Black phosphorus quantum dots regulate inflammation and neural stem cells differentiation via Notch1 signaling through cell adhesion - Lu Chen; Yongyuan Guo; Lusen Shi; Shiji Zhang; Linlin Jiang; Yong Chang; Haoran Liu; Zihang Wang; Na Li; Shiqing Feng (Chemical Engineering Journal, 2026)

Hydrodynamics, mixing performance and power consumption in horizontal millimeter-scale helical tube reactors: comprehensive experimental and numerical investigations across a wide range of centrifugal-to-gravitational acceleration ratio - Zhongyao Zhang; Yuanjie Wu; Xiaopeng Chen; Jiezhen Liang; Qianyun Tan; Chenghong Wu; Bo Feng; Denghan Luo; Linlin Wang (Chemical Engineering Journal, 2026)

O2-supplementing photosensitizer AuNCs@TAT as a highly efficient NIR-II-controllable pyroptosis inducer for cancer photoimmunotherapy - Linlin Xie; Xingye Ma; Zheng Wang; Caifang Wang; Zhongxin Xiao; Ling-Dong Sun; Chun-Hua Yan; Chen-Jie Fang (Chemical Engineering Journal, 2026)

Consolidated bio-saccharification (CBS) enhanced hydrogen production via bioaugmentation to eliminate cellobiose inhibition: Investigation on hydrogen production performance and microbial community - Sheng Tao; Song Chengwei; Liu Qianchi; Song Zhiwei; Yang Chunxue; Sun Caiyu; Li Lixin; Huang Linlin; Wang Miao (Biocatalysis and Agricultural Biotechnology, 2026)

Numerical Simulation of Gas Production and Geomechanical Response of Heterogeneous Gas Hydrate Reservoirs - Jiuhui Cheng; Shuitao Zhang; Linlin Wang; Guangjin Chen (Natural Resources Research, 2026)

An integrated multiscale computational study of nephrotoxicity mechanism of citrinin and its metabolites (CIMs)：density functional theory, network toxicology, and molecular dynamics simulation - Jiaxing Li; Furong Xue; Linlin Xu; Huijing Zhang; Xizi Zhang; Chenchen Qi; Chengtao Wang; Wei Chen; Di Zhang (Mycotoxin Research, 2026)

Dynamic Mechanisms of Land Use Conflict Under Main Function Oriented Zone Planning: A Case Study of Beijing-Tianjin-Hebei Region - Yang Zheng; Linlin Cheng; Junqi Wang; Yifang Wang; Huizhen Cui (Chinese Geographical Science, 2026)

Juvenile-Onset Cerebrotendinous Xanthomatosis with Novel Compound Heterozygous CYP27A1 Mutations: Case Series and Literature Review - Kefang Du; Chunrong Wang; Linlin Wan; Zhao Chen; Hongyu Yuan; Qian Jiang; Xiao Dong; Daji Chen; Riwei Ouyang; Xiafei Long; Xiaokang Wu; Xinying Xiao; et al. (The Cerebellum, 2026)

Drug screening reveals the mechanism of toyocamycin-induced apoptosis in triple-negative breast cancer organoids - Houshi Ma; Linlin Lu; Yuqing Tu; Xiaoran Chang; Huabin Jiang; Tianhang Yang; Shun Wang; Jinxian Wang; Jinbing Xue; Yan Chen; Gangyin Luo (Toxicology and Applied Pharmacology, 2026)

From association to mechanism: Prenatal PFAS Co-exposures induces fetal neural tube defects via autophagy-mediated ferroptosis - Yongyan Chen; Qianhui Cheng; Chen Yang; Sainan Li; Hai Lin; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Journal of Hazardous Materials, 2026)

Bias-aware learning for unbiased scene graph generation in remote sensing imagery - Tingzhu Wang; Linlin Wang; Junwei Luo; Kang Wu; Yansheng Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Comparative metabolomic analysis of spray- and freeze-dried Cornus officinalis microcapsules reveals temperature-dependent flavonoid retention and optimal encapsulation conditions - Wenchao Liu; Xinyu Wei; Lijuan Wang; Linlin Li; Weiwei Cao; Yilin Huang; Junliang Chen; Chung Lim Law; Qing Sun; Guangyue Ren; Xu Duan (Innovative Food Science & Emerging Technologies, 2026)

Inactivation of Penicillium ochrochloron spores by pulsed light: Mechanism and preservation efficacy in strawberries - Xiaozhen Cui; Anthony Pius Bassey; Fan Wang; Shudong Xie; Dongnan Li; Linlin Fan; Yongsheng Zhu; Li Bin; Xiaoli Liu (Food Control, 2026)

Humidity-regulating antibacterial trilayer Janus membrane of polyacrylonitrile/gelatin-potato starch/polycaprolactone-cinnamon essential oil for cherry tomato preservation - Mingyi Tian; Chenlong Liu; Zhiyuan Ge; Wei Ji; Yimeng Zhang; Linlin Li; Hualin Wang (Food Packaging and Shelf Life, 2026)

Synergistic DFT and experimental design of Ga/W Co-Doped SnS2 microspheres with enriched sulfur vacancies for enhanced NO2 sensing - Wei Zhao; Lanlan Guo; Xin Shi; Linlin Dong; Yingli Yang; Xueli Yang; Xiaolian Liu; Guodong Wang; Yan Wang (Chemical Engineering Journal, 2026)

Harnessing β-glucans for immune regulation: Bridging structural diversity, therapeutic potential, and functional food development - Xue Wang; Linlin Ma; Chen Chen; Lina Ma; Xian Qu; Ai Ren; Yifa Zhou; Hairong Cheng (Carbohydrate Polymers, 2026)

Bisphenol S and Neurological Health: An Integrated Overview of Neurotoxicity and Underlying Mechanisms - Xing Zhang; Linlin Wu; Dingqi Hua; Bin Zhang; Xi Wang; Linchang Li; Yi Wang; Jiangbo Zhu (Molecular Neurobiology, 2026)

The Key Role of Somatostatin Neurons in the Suprachiasmatic Nucleus in Anxiety-Depression Comorbidity Following Sleep Deprivation - Yifei Zhang; Yuxin Wang; Xinyue Liu; Chunlin Ren; Ming Chen; Linlin Bi (Molecular Neurobiology, 2026)

Deciphering Ferroptosis-Related Astrocyte Subpopulations and Diagnostic Biomarkers in Parkinson’s Disease through RNA Transcriptomics - Zhongying Gong; Dan Guo; Yufeng Lin; Zhiwei Liu; Mengdi Lv; Xinxin Liu; Mingshuo Sun; Linlin Wang; Tianman Zhao; Zhiyun Wang; Xue Xue (Molecular Neurobiology, 2026)

Biodiversity and biogeographic patterns of Nereididae (Annelida) across the Indo-Pacific Convergence Zone - Jieyang Weng; Xuwen Wu; Tiantian Wang; Chenrui Li; Linlin Zhang (Journal of Oceanology and Limnology, 2026)

Effect of cAMP concentration on apoptosis of sheep granulosa cells in vitro - Wenhao Wang; Linlin Pei; Peilin Guo; Andi Qiao; Shuyan Guo; Xin Xu; Chunjie Liu (In Vitro Cellular & Developmental Biology - Animal, 2026)

prepIMS: a robust data preprocessing workflow for ion mobility mass spectrometry imaging - Linlin Wang; Chengyi Xie; Lei Guo; Thomas Ka Yam Lam; Chris Kong Chu Wong; Mudassir Shah; Xiangnan Xu; Jianing Wang; Jingjing Xu; Jiyang Dong; Zongwei Cai (Analytica Chimica Acta, 2026)

Four new glycoside compounds from Sinapis alba L. and their cytotoxic activity - Degang Kong; Xinyu Shi; Linlin Ni; Xiaoni Kong; Meichao Cai; Honglei Zhou; Xiaoyu Wang (Natural Product Research, 2025)

Curvature sensing strategy for flexible gripper fingers during grasping deformation: enabling in-orchard online apple size grading - Guangze Zhao; Hongjian Zhang; Jingwei Sun; Huawei Yang; Shaowei Wang; Shuangxi Liu; Xinpeng Cao; Shenghui Fu; Yongxian Wang; Linlin Sun; Linlong Jing; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Apple diameter prediction during mechanical picking based on flexible force-sensing and CNN-BiLSTM-Attention method - Mingyang Lu; Linlin Sun; Haidi Chu; Mochen Liu; Jing Wang; Hongjian Zhang; Zhanhua Song; Yao Lu; Jinxing Wang; Yinfa Yan (Computers and Electronics in Agriculture, 2025)

HDC-Net: A hierarchical detection and counting framework for apple aphids with density-level classification - Bo Ma; Zhuo Ren; Shuangxi Liu; Linlin Sun; Junlin Mu; Qiaolin Chen; Jiawei Xu; Rongsen Xie; Xianliang Hu; Yongqiang Zheng; Hongjian Zhang; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Research hotspots and trends in Spartina alterniflora studies (1970–2023): A bibliometric analysis - Dandan Yan; Shanshan Wang; Peng Song; Yuqing Zhang; Yiming Huang; Yu Wang; Wenyan Zhu; Linlin Wu (Marine Pollution Bulletin, 2025)

Learning to reason over multi-granularity knowledge graph for zero-shot urban land-use mapping - Yansheng Li; Yu Wang; Lei Yu; Bo Dang; Gang Xu; Zhenyu Zhong; Yuning Wu; Xin Guo; Kang Wu; Zheng Li; Linlin Wang; Jian Wang; et al. (Remote Sensing of Environment, 2025)

June–September mean temperature variability in the eastern Qinghai-Tibet Plateau over the past 225 years based on high quality tree-ring records - Xinyue Li; Linlin Gao; Baolong Ma; Kai Wang; Yang Deng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A shift toward extensive utilization: The long-term relations between building volume and utilization intensity in China’s 267 natural cities - Kechao Wang; Linlin Ruan; Wu Xiao; Runjia Yang; Jiatong Zhou (Landscape and Urban Planning, 2025)

The role of water regime in soil organic carbon preservation in mangrove wetlands: “iron gate” vs. “enzyme latch” - Haixiao Zhao; Zhengang Wang; Wei Yang; Linlin Yao; Qian Tan (Journal of Hydrology, 2025)

Delayed algal blooms to runoff surges in low-runoff estuaries: hydrodynamic and nutrient driving mechanisms and early warning strategies - Linlin Wang; Zuoyi Chen; Gang Wang; Yike He; Lin Mu; Xianzhong Mao; Hongsheng Bi; Jiabo Zhang (Journal of Hydrology, 2025)

Electroenhanced organic pollutant adsorption by three - dimensional isolated electrodes: Investigation of the “short - plate effect” - Xinyu Wang; Xiaochen Zhang; Linlin Chen; Fei Yu; Jie Ma (Journal of Cleaner Production, 2025)

Zein/eugenol electrospun mats on gelatin/laponite substrate for developing bilayer functional food packaging - Minmin Chen; Linlin Li; Wei Ji; Wensheng Lu; Xiaochao Tang; Suwei Jiang; Hualin Wang (Food Research International, 2025)

Tracking Browning mechanistic pathway of postharvest pine resin using comparative metabolomics - Xin Li; Junsheng Lu; Junmei Ye; Yibin Qin; Xiaopeng Chen; Jiezhen Liang; Linlin Wang (Food Chemistry, 2025)

Effect of salt stress-induced germination technology on the phenolic composition, antioxidant capacity, and metabolic pathways of highland barley (Hordeum vulgare L.): A metabolomics insight - Shuyao Wen; Disheng Xiao; Linlin Ye; Shimin Liu; Miao Liu; Xiaoyi Hou; Hui Li; Na Deng; Jianhui Wang (Food Bioscience, 2025)

Transcriptomic analysis of mature biofilm and planktonic cells of Listeria monocytogenes under nutritional stress - Yuan Wang; Linlin Xiao; Jing Ji; Danial Hassani; Youzhi Wu; Hongmei Niu; Qingli Dong (Food Microbiology, 2025)

Mitochondria-targeted nanoparticles with whole-course-repair efficacy in therapy of myocardial ischemia reperfusion injury - Xiya Wang; Hang Chen; Pingyuan Sun; Linlin Zhao; Renxiang Gui; Xu Wang; Emeli Chatterjee; Jiahong Xu; Jianle Chen; Xuerui Chen (Chemical Engineering Journal, 2025)

Construction of temperature-responsive helical carbon nanofibers-based composites toward switchable microwave absorption - Yudi Li; Linlin Zhao; Wei Feng; Rongling Zhang; Xialong Cai; Zhiyong Chen; Hanjun Wei; Xulin Yang; Pan Wang; Giulio Cerullo; Nabil Kadhim Taieh; Fanbin Meng; et al. (Chemical Engineering Journal, 2025)

Superior bridging effect of Pt NPs in all-solid-state Z-scheme CdS QDs/NaTaO3 microcube heterojunction for highly efficient photocatalytic hydrogen evolution - Jiayi Meng; Juhua Zhang; Yamei Huang; Zizheng Wang; Yifan Liao; Quanmei Zhou; Yuchen Wei; Linlin Gao; Wei-Lin Dai (Chemical Engineering Journal, 2025)

Pilot-scale investigation of polyhydroxyalkanoates synthesis using mixed microbial cultures from fermented thermally hydrolyzed sludge - Yun He; Kuixiao Li; Yu Zhang; Gang Wang; Jing Chang; Shan Hao; Linlin Wei; Xu Xing (Bioresource Technology, 2025)

Impact of drought and root excision on root regeneration, xylem hydraulics and leaf physiological characteristics in Robinia pseudoacacia - Haoyan Wei; Xiaoyun Ding; Kechen Cao; Hengjian Lai; LinLin Wang; Min Li (Plant and Soil, 2025)

ViruSeg: Harnessing the Power of Large Language-Image Model for Enhanced Virus Image Segmentation - Shengxiang Wang; Xiangzheng Fu; Zhenya Du; Xinxin Liu; Qiaochu Mai; Linlin Zhuo; Boqia Xie; Quan Zou (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Evaluation of FY-4A/4B GIIRS Atmospheric Temperature Profile Products Using Radiosonde Observations through a Per-Level Collocation Method - Xiaoyue Zhang; Yuanyuan Wang; Qiang Gong; Ying Wang; Yudi Shi; Linlin Li; Guochun Li (Journal of Meteorological Research, 2025)

Does soil compaction affect the mobility and transformation behavior of Arsenic -A case study of an Alfisol - Xinjun Huang; Lanting Liu; Yali Wang; Yongqiang Yang; Linlin Zhao; Rainer Horn; Liping Li (Soil and Tillage Research, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

The influence of different emulsifiers on dotted gizzard Shad (Konosirus punctatus) oil emulsions - Ying Guo; Linlin Wang; Kaiyi Wang; Li Li; Mengting Wei; Xin Wang; Zhen Wang; Baojie Jiang; Juanjuan Shao; Jilu Sun (Food Chemistry, 2025)

Characterization of vB_SaRS_FS19–1, a newly isolated broad-host-range and virulent bacteriophage infecting Staphylococcus aureus and its application in foods - Xinyan Yao; Chaoxiang Jia; Ting Qin; Dai Peng; Linlin Huang; Yi Liu; Saiyu Zhang; Yingqian Han; Yanbin Yang; Heping Li; Hua Wu; Guoyu Yang; et al. (Food Chemistry, 2025)

A highly sensitive and specific immunochromatographic test strip for detecting p,p′-DDA in seawater and shellfish - Teng Zhang; Yunrui Xing; Jiale Yao; Zhuan Yang; Jucai Wang; Linlin Chen; Lunguang Yao (Food Chemistry, 2025)

Investigating the aroma transition during rapid mango ripening driven by dynamic catabolism of fatty acids - Yuanping Wang; Zhenjiang Zhou; Yonghao Liu; Rongli Pang; Xi Zhao; Qi Chen; Linlin Guo; Baiyi Lu (Food Chemistry, 2025)

Cornus officinalis polysaccharides nano-selenium exhibits anti-fatigue effects by regulating gut microbiota in mice - Jianrui Sun; Ruirui Ren; Jinglan Li; Jiaqi Fan; Linlin Yao; Shanshan Tie; Jie Zhang; Dahong Wang; Shaobin Gu (Food Bioscience, 2025)

Experimental study on mechanical properties of a new duplex stainless steel for structures under different temperature-stress combination paths - Shuobiao Li; Zhen Wang; Wenqi Ding; Qingzhao Zhang; Linlin Gu (Engineering Structures, 2025)

DHA sustains frozen-cell-induced efferocytosis by mitigating endoplasmic reticulum stress to promote inflammation resolution and bone repair - Boya Zhang; Hanze Du; Lei Huang; Lijun Liu; Jing Cui; Linlin Wen; Junguang Liu; Wenhao Zhai; Rongrong Ye; Yuhuan Li; Kexuan Liu; Wangni Xie; et al. (Chemical Engineering Journal, 2025)

Photocatalytic chitosan/hydroxypropyl methylcellulose-based multifunctional film incorporated with chlorophyll-TiO2@carbon sphere dual heterojunction and L-arginine for banana preservation - Haoran Wang; Wei Ji; Feng Xiao; Yewen Xiao; Linlin Li; Xia Shu; Hualin Wang; Jun Yin (Chemical Engineering Journal, 2025)

Chemical composition and mixing states of individual atmospheric particles in summer and winter: a micro-Raman spectroscopy study - Yan Huang; Qingcheng Li; Linlin Ye; Jingjing Wang; Yidan Zhang; Tong Zhu; Chengzhu Zhu; Mingjin Wang (Atmospheric Environment, 2025)

Salvianolic Acid B and Ginsenoside Rg1 Combination Attenuates Cerebral Edema Accompanying Glymphatic Modulation - Lingxiao Zhang; Yanan Shao; Zhao Fang; Siqi Chen; Yixuan Wang; Han Sha; Yuhan Zhang; Linlin Wang; Yi Jin; Hao Chen; Baohong Jiang (Neuroscience Bulletin, 2025)

Topographical differentiation characteristics of double high pollution of PM2.5 and ozone in the Beijing-Tianjin-Hebei region - Huan Zhang; Xiaohong Wang; Yiheng Liang; Liyi Qin; Jinlong Li; Linlin Jiao (Air Quality, Atmosphere & Health, 2025)

MitoQ reducing sevoflurane-induced cognitive dysfunction by modulating mitochondrial dysfunction - Hengjie Su; Zhibin He; Haotian Wu; Linlin Wang; Huan Zhang; Siyi Yan (Metabolic Brain Disease, 2025)

Atypical seasonal variability of the Kuroshio Current in 2018 - Fujun Wang; Linlin Zhang; Junqiao Feng; Qingye Wang; Dunxin Hu (Frontiers in Marine Science, 2025)
Introduction Using three moorings deployed at 122.7°E, 123°E, and 123.3°E along 18°N from January 2018 to May 2020, this study investigates the seasonal variability of the Kuroshio Current (KC). Methods Sensitive experiments were conducted with the Regional Ocean Modeling System (ROMS). Results In 2019, the KC exhibited a typical seasonal cycle, being relatively strong during spring, summer, and winter, with the weakest flow occurring in autumn. In contrast, the KC displayed an atypical seasonal cycle in 2018, characterized by two distinct intraseasonal intensification events in late September and early November. The ROMS experiments revealed that local winds within the region (120°E–125°E, 15°N–20°N) were the primary driver of this atypical cycle. During the two key periods, persistent negative wind stress curl anomalies east of the mooring stations induced integrated positive sea surface height anomalies and corresponding northward meridional velocity anomalies via geostrophic balance. Discussion In 2019, the wind stress curl anomaly phases reversed compared to 2018, leading to the absence of the two peaks observed in the previous year.

DBENet: dual-branch encoder network based on the visual state space model for semantic segmentation of remote sensing image - Hengyou Wang; Hao Liu; Lianzhi Huo; Linlin Chen; Qiang He (International Journal of Remote Sensing, 2025)

Enhancing the identification of malonylation sites using AlphaFold2 and ensemble learning - Linlin Xu; Yuting Qian; Jiayi Yang; Xiaowei Xu; Zhiqiang Li; Yanhan Wang; Enhui Lv; Xingxing Kang; Hongwei Zhang; Yaping Lu; Fei Wang; Xin Liu (Molecular Diversity, 2025)

Triboelectric force feedback-based fully actuated adaptive apple-picking gripper for optimized stability and non-destructive harvesting - Jingwei Sun; Linlin Sun; Guangze Zhao; Junsheng Liu; Zixu Chen; Linlong Jing; Xinpeng Cao; Hongjian Zhang; Wei Tang; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Spatial planning for dugong conservation: Assessing habitat suitability and conservation gaps in Indo-Pacific Convergence Zone - Bei Wang; Kaiyu Liu; Watchara Sakornwimon; Wenhao Huang; Tingting Li; Xianshui Lai; Chengcheng Li; Linlin Zhao; Bailin Cong; Shenghao Liu (Marine Policy, 2025)

Identifying hundredfold carbon emission gaps in multiple resource recycling routes of construction waste via process and hybrid life cycle assessment - Rui Chen; Haiyuan Wu; Junjie Li; Hao Wang; Lanxin Li; Linlin Sun; Fumin Ren (Waste Management, 2025)

Recent progress in hygroscopicity improvement strategies of protein-based films for edible food packaging - Yiyi Chen; Xiangren Meng; Linlin Zhao; Pei Peng; Ying Ma; Jing Wang (Trends in Food Science & Technology, 2025)

Comparative analysis of storage temperatures and forchlorfenuron treatment concentrations on physiological quality and primary metabolites in kiwifruit during storage - Xiaofan Qi; Chengkui Qiao; Lijun Han; Ming Zhuang; Mengyuan Cao; Caixia Wang; Linlin Guo (Postharvest Biology and Technology, 2025)

Experimental investigation on local scour around a cubic artificial reef in bidirectional tidal currents - Linlin Wang; Mingda Yang; Muk Chen Ong; Fenfang Zhao; Yujie Cui; Yanli Tang (Ocean Engineering, 2025)

Tetraether-based temperature record from Lake Xingyun in southwestern China since late MIS3 and implication for regional differences in temperature reconstruction - Haiyang Yu; Xu Wang; Ming Ji; Shihao Zhang; Gaochao Pan; Licheng Guo; Linlin Cui; Xueyun Ma; Wubiao Li; Dongsheng Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Phosphorus reward mechanisms of an arbuscular mycorrhizal fungus and a dark septate endophyte to plant carbon allocation: Synergism or competition? - Yinli BI; Linlin XIE; Xiao WANG; Yang ZHOU (Pedosphere, 2025)

Land use carbon emission projections in shared socioeconomic and representative concentration pathways: Relationship with urbanization in Chinese megacities - Yu Yao; Linlin Lu; Zongtang Fu; Fang Chen; Ran Wang; Qingting Li (Land Use Policy, 2025)

In silico profiling of bisphenol compounds for estrogenic effects via pharmacophore modeling, molecular docking, and dynamics simulations - Lifeng Wang; Ning Li; Linlin Wang; Zengfeng Li; Qiang Li; Jiaqi Tian; Lin Zhang (Journal of Hazardous Materials, 2025)

Superhydrophilic adsorptive nanofiber membranes for ultrafast and highly-efficient waterborne nanoplastic removal - Jingwen Zhou; Mi Zhou; Longjun Wang; Jiayu Tong; Xinhao Li; Jingru Zhou; Yuqian He; Linlin Yan; Xiquan Cheng (Journal of Hazardous Materials, 2025)

Simultaneous accelerating H2O2 generation and activation via construction of CuS/NiS2 heterostructures in heterogeneous electro-Fenton for sulfamerazine degradation - Chenlin Wang; Chunhui Yu; Yuhan Ma; Fan Yang; Xinyang Sun; Kexin Wei; Junpu An; Li Li; Linlin Han; Kuobo Wang; Yongfeng Li (Journal of Environmental Chemical Engineering, 2025)

Hematopoietic responses to metal-organic frameworks in adult mice following pulmonary exposure - Min Li; Linlin Yao; Yuanyuan Wang; Jie Gao; Junjie Ma; Yaquan Liu; Yun Ding; Xuehan Zheng; Liqun Chen; Runzeng Liu; Li Zeng; Guangbo Qu; et al. (Journal of Environmental Sciences, 2025)

Enhanced selective oxidation of 5-Hydroxymethylfurfural with a recyclable V34@Fe3O4/C catalyst Enriched with Mixed-valence polyoxovanadate active centers - Chunhui Zhang; Mengqi Wang; Changhao Zhao; Junpeng Wang; Yundong Cao; Linlin Fan; Hong Liu; Guang-Gang Gao (Fuel, 2025)

Molecular and physiological adaptations of Scartelaos histophorus to air exposure: Implications for amphibious fish survival - Dongdong Xiao; Ruizhi Wang; Peidong Zhang; Riyanti; Linlin Zhao; Na Song (Environmental Research, 2025)

Sources, temporal-spatial characteristics, exposure assessment and children health risk of phthalate esters (PAEs) in household dust in China from 2000 to 2023: a review and pool analysis - Wenying Zhang; Xiaotong Zhang; Xiaomin Xie; Tingting Liu; Fengjing Song; Chengyu Chen; Chao Wang; Linlin Jiang; Hang Du; Lin Fan; Xu Han; Yiming Sun; et al. (Environmental Pollution, 2025)

Microseismic criterion for dynamic risk assessment and warning of roadway rockburst induced by coal mine seismicity - Lianpeng Dai; Xin Zhao; Yishan Pan; Hao Luo; Yanan Gao; Aiwen Wang; Linlin Ding; Peng Li (Engineering Geology, 2025)

Sponge-like PNIPAM/Fe3O4/PPy composite hydrogel actuator with rapid response, self-sensing and multiple manipulating manners for complex application scenarios - Xingchen Cui; Bing Zhang; Pingzhi Shao; Linlin Li; Shunsheng Ye; Fuqiang Fan; Yu Fu; Fanbao Meng; Tieqiang Wang (Chemical Engineering Journal, 2025)

Waste asphalt-derived hard carbon assisted by biomass templating for sodium-ion batteries - Danqing Li; Xin He; Linlin Wang; Yinghao Zhang; Xingqiao Wu; Mei Ding; Chunhui Gao; Yang Gao; Chuankun Jia (Chemical Engineering Journal, 2025)

Double synergistic strategy: mechanism of acetone sensing performance enhancement by Pt@Cu3(HHTP)2 derivatives modifying three-dimensional inverse opal In2O3 - Lanlan Guo; Jiaru Yang; Yuying Cai; Linlin Dong; Yingli Yang; Xueli Yang; Xiaolian Liu; Guodong Wang; Yan Wang (Chemical Engineering Journal, 2025)

Bioleaching of valuable metals from spent lithium iron phosphate batteries using food-grade Lactobacillus acidophilus - Qiuli Xia; Danni Zhang; Zhong Li; Chuanwei Yang; Pan Liu; Hong Wang; Yuting Jin; Min Li; Jia Dong; Xianjun Guan; Linlin Tong; Yongqiang Fan; et al. (Chemical Engineering Journal, 2025)

Atmospheric boundary layer heat budget and its urban-rural differences in Beijing during a heatwave event - Qianyue Huang; Yuanjie Zhang; Jialing Xin; Yubin Li; Yue Qin; Linlin Wang (Atmospheric Research, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Advances in preclinical studies of ginsenoside Rh2 in antitumor therapy - Zheng Xu; Guanghuan Shen; Zhihua Xing; Jianghan Luo; Yu Zhu; Xuan Liu; ShiHao Li; Hao Wang; Linlin Cui (Medicinal Chemistry Research, 2025)

Embryonic and Larval Development of an Interspecific Grouper Backcross Between the Kelp Grouper (Epinephelus moara) ♀ and KGGG (E. moara ♀ × E. lanceolatus ♂) ♂ - Yidan Xu; Yongsheng Tian; Shihao Wang; Tangtang Ding; Linna Wang; Zhentong Li; Linlin Li; Yang Liu (Fishes, 2025)
Backcrossing serves as an effective tool for interspecific gene introgression, facilitating germplasm improvement. To develop superior grouper aquaculture varieties, in this study, a backcrossed breed was constructed by crossing a male hybrid grouper, KGGG (Epinephelus moara ♀ × E. lanceolatus ♂), with a female parent kelp grouper (KG; E. moara). Here, we observed embryonic, larval development, and morphological changes in KG × KGGG. Additionally, the total length and body weight of the backcrossed breed and maternal parent were compared at 160 d post hatching (dph). The results showed that fertilization and the hatching rate were 73.23 ± 4.23% and 51.74 ± 3.67%, respectively, and the egg size was 0.89 ± 0.03 mm. Hatching occurred 23:19 h after fertilization at 25 ± 1 °C, and the newly hatched larvae were 1.94 ± 0.13 mm in length. Furthermore, at 160 dph, the total length and body weight of the backcrossed breed were 1.2-fold and 1.9-fold greater, respectively, when compared with those of the maternal parent. Importantly, it is possible that backcrossed KG × KGGG could become a dominant strain in grouper aquaculture practices.

OA-based photo-Fenton system generates oxidizing and reducing radicals for the simultaneous removal of 1-NA and Cr (VI) in surface waters - Linlin Liang; Li Sun; Qiuwen Wang; Fuqiang Zhang; Huixue Li; Guoquan Liu; Pengfei Wang; Sihui Zhan (Water Research, 2025)

Non-destructive prediction of soluble solids content and firmness and maturity determination of guava fruit using color and fluorescence imaging - Shaozhen Lin; Kangting Yan; Zhilei Sun; Zhijie Zhang; Yubin Lan; Linlin Wang; Yali Zhang (Postharvest Biology and Technology, 2025)

Predicting and quantifying damage characteristics in mechanized harvesting: A collision-based study of apples - Zixu Chen; Linlin Sun; Linlong Jing; Xinpeng Cao; Yongxian Wang; Junsheng Liu; Hongjian Zhang; Jinxing Wang (Postharvest Biology and Technology, 2025)

Integrated transcriptome and metabolome analyses reveal regulatory mechanisms governing carbohydrate biosynthesis in Panax ginseng - Qiao Jin; Qiuxia Wang; Linlin Zhang; Yue Zhang; Zhengbo Liu (Plant Science, 2025)

Uranium immobilization by Brevundimonas vesicularis LWG1: A synergistic approach via biomineralization, biosorption, and bioreduction - Yanru Liang; Linlin Wang; Panpan Gao; Zichu Qiu; Zemin Qin; Risheng Xu; Yue Li; Wenjuan Shuai; Jimin Li; Xueqing Geng; Hailiang Dong; Yuheng Wang (Journal of Hazardous Materials, 2025)

Thermodynamic drivers of rice glutenin Assembly: Multiscale analysis of Hierarchical structure and intermolecular bonding - Wanshan Yang; Huining Zhang; Haoyu Li; Yuhan Jiang; Zhiqi Wang; Menglu Yang; Sitong Liu; Yinyuan He; Bing Wang; Linlin Liu; Yan Wang; Fenglian Chen; et al. (Journal of Cereal Science, 2025)

Melatonin protects dopaminergic neurons in paraquat-induced Parkinson in rats through PI3K/AKT/Nrf2 pathway - Yanhui Wang; Xin Zhang; Weiliang Zhang; Minging Han; Qiang Jia; Cunxiang Bo; Hua Shao; Linlin Sai; Cheng Peng (Food and Chemical Toxicology, 2025)

Melanoidins induced transformation of protein and polysaccharide during thermal hydrolysis-pyrolysis of sludge via non-covalent forces - Yimeng Jiao; Yifei Wu; Ziyang Dong; Jinxuan Ning; Jialin Wang; Lu Liu; Zhengda Lin; Yu Tian; Linlin Yin; Jun Zhang (Chemical Engineering Journal, 2025)

Manipulating the wastewater's ion composition to assist in the adsorption of organophosphate esters (OPEs) - Zhiqiang Li; Rongyue Wang; Wenting Jia; Linlin Shen; Pengge Ning; Hongbin Cao (Chemical Engineering Journal, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

An improved method for extracting cellulose from fossil wood and its paleoclimatic implications - Donghao Wu; Xin Wang; Yang Deng; Mi Wang; Gang Hu; Xuan Ding; Linlin Gao; Keyan Fang; Xiaohua Gou (Frontiers of Earth Science, 2025)

Dissolved organic matter sources in urban outfall water before and during rainfall, indicated via its fluorescence fingerprinting - Haojie Yin; Tao Huang; Bo Wang; Yingying Zhang; Jiawei Hu; Linlin Zhu; Kaining Chen (Applied Geochemistry, 2025)

Extending the Mutational Spectrum of SYNE1 Ataxia in Chinese Patients - Xin Huang; Zhao Chen; Qian Jiang; Panyan Liu; Yiqing Gong; Lijing Lei; Jia Chen; Chunrong Wang; Linlin Wan; Lang He; Linliu Peng; Rong Qiu; et al. (The Cerebellum, 2025)

Identifying spatially targeted organic fertilizer subsidies for water pollution control: An interactive hydro-economic model - Shuping Wang; Pan Yang; Qian Tan; Linlin Yao; Cangbai Li (Water Research, 2025)

Typical migration patterns and fates of microplastics with varying properties in bays and their impacts on coastal ecologically sensitive areas - Huaihao Shao; Qiankun Wang; Linlin Wang; Shuangliang Dai; Xin Ye; Xian-zhong Mao (Water Research, 2025)

Norgestrel shows androgenic properties and triggers reproductive neuroendocrine toxicity in the testes of Pacific oysters (Crassostrea gigas) - Yan Fang; Baojun Liu; Juan Wang; Haoyang Zhong; Linlin Fan; Yuchao Huang; Changkun Chen; Songtao Lu; Tao Zheng (Journal of Hazardous Materials, 2025)

Seasonal distribution patterns of P-cycling-related microbes and its association with internal phosphorus release in the eutrophic Lake Chaohu, China - Tingting Sun; Linlin Zhu; Tao Huang; Pengliang Tao; Yan Bao; Bo Wang; Qingye Sun; Kaining Chen (Journal of Environmental Sciences, 2025)

High-pressure homogenization treatment on yeast protein: Effect on structure and emulsifying properties - Zihuan Wang; Xiuli Xu; Zhaoli Liu; Tong Xu; Linlin Ma; Fuhang Song (Food Research International, 2025)

Effect of cyanobacterial bloom proliferation on antibiotic resistance genes in the sediments of a eutrophic lake - Bo Wang; Tao Huang; Linlin Zhu; Jiawei Hu; Shaodong Ma; Qingye Sun; Kaining Chen (Environmental Research, 2025)

Flexible electrochromic film for visualized meat freshness detection - Wenhui Zhang; Wuyuan Wang; Linlin Xia; Guanghong Zhou; Jie Wang (Chemical Engineering Journal, 2025)

SIMPLE: A One-Pot RPA-Cas12b Method for Single Nucleotide Variations Identification with an Expanded Scope and Clinical Applications - Kaiming Guo; Yongkang Lai; Yiru Han; Linlin Bai; Ting Wang; Shengzhou Wang; Ziqin Zhang; Dianwei Liu; Yanju Chen; Jiulong Zhao; Yanan Pang; Feng Qian; et al. (Phenomics, 2025)

Preclinical models in the study of lymph node metastasis - Liya Wei; Zizhan Li; Niannian Zhong; Leiming Cao; Guangrui Wang; Yao Xiao; Bo Cai; Bing Liu; Linlin Bu (Journal of Zhejiang University-SCIENCE B, 2025)

Monitoring of Larch Caterpillar (Dendrolimus superans) Infestation Dynamics Using Time-series Sentinel Images in Changbai Mountains National Nature Reserve, Northeast China - Linlin Wu; Mingchang Wang; Jiatao Du; Jingzheng Zhao; Fengyan Wang (Chinese Geographical Science, 2025)

Application Value of Chemiluminescence Immunoassay in Thyroid Function Biochemical Testing - Yiming Jin; Decheng Shi; Linlin Wang (Journal of Fluorescence, 2025)

circ_0000554 promotes macrophage M2 polarization mediated by glycolytic reprogramming and aggravates COPD injury - Yamei Song; SiQin Han; Linlin Liu; Lifeng Zheng; Jing Wang; Zhaobo Cui; Xixin Yan (Toxicology Letters, 2025)

Occupational exposure to amorphous silica nanoparticles alters lung function and metabolomic features - Xuemin Shi; Chen Liang; LinLin Wang; Xuefeng Bai; Ruiyang Ding; Zhiwei Sun (Toxicology Letters, 2025)

Cross-platform detection of microplastics in human biological tissues: Comparing spectroscopic and chromatographic approaches - Lin Zhang; Jiaqi Tian; Xiaodan Zhu; Linlin Wang; Xiang Yun; Liyang Liang; Shuyin Duan (Journal of Hazardous Materials, 2025)

Crassula perforata structured Ni3S2/NiTe electrodes enable efficient and robust seawater electrolysis at industrial-level current density - Xueling Wei; Xiangyu Zou; Qiguan Wang; Qiannan Liang; Youjun Huang; Taotao Ai; Wenhu Li; Linlin Dang; Sumin Wang (Fuel, 2025)

Elucidating the pattern of flavor evolution during the steaming process of fermented sausages in two dimensions: Strain fermentation and steaming time - Xuefei Shao; Huhu Wang; Xiangyu Song; Na Xu; Linlin Cai; Xinglian Xu (Food Chemistry, 2025)

Graphite-catalyzed carbonization of biowaste unlocks energy-dense, high-rate, and long-lifespan potassium-ion batteries - Jiale Chen; Lulu Tan; Chengye Lin; Yue Bai; Xiaogang Niu; Zhe Zhang; Nan Li; Linlin Wang; Ye Wang; Xiao Ji; Yujie Zhu (Chemical Engineering Journal, 2025)

Impacts of spatial resolutions of UAV-LiDAR-derived DEMs on erosion modelling in the hilly and gully Loess Plateau - Wenli Li; Pengfei Li; Lu Yan; Jinfei Hu; Leiqin Wang; Dou Li; Yang Dan; Linlin Huang; Guangju Zhao (CATENA, 2025)

Resin tapping in Masson pine (Pinus massoniana): Response of resin yield and its product quality to film mulching and chemical stimulation treatments - Jiaqi Liang; Xiaopeng Chen; Linlin Wang; Xiaojie Wei; Kewei Mo; Zehui Xiong; Jiezhen Liang (Biomass and Bioenergy, 2025)

Distribution of glucosinolates and antioxidants in different leaf-layers of Kale (Brassica oleracea var. acephala DC.) - Yafang Luo; Huixia Bai; Linlin Zhao; Qi Hu; Xinyuan Li; Zhenyu Fan; Yushu Wang (Physiology and Molecular Biology of Plants, 2025)

SagMSI: A graph convolutional network framework for precise spatial segmentation in mass spectrometry imaging - Mudassir Shah; Linlin Wang; Lei Guo; Chengyi Xie; Thomas Ka-Yam Lam; Lingli Deng; Xiangnan Xu; Jingjing Xu; Jiyang Dong; Zongwei Cai (Analytica Chimica Acta, 2025)

One-step narrow-thermal-cycling strand exchange amplification for sensitive detection of porcine reproductive and respiratory syndrome virus - Linlin Zhuang; Chunlei Song; Li Sun; Haiqiang Xie; Liqun Wang; Qingxin Liu; Hongjing Shi; Jianbo Yang; Qiuping Shen (Archives of Microbiology, 2025)

Label-Free Direct Detection of 4MU by Plasmon Enhanced Fluorescence Sensing Based on Ag@SiO2 NPs - Liqi Wang; Xin Lv; Ziheng Song; Linlin Tian; Xinyue Du; Dong Zhang; Qingru Wang (Journal of Fluorescence, 2025)

An automated river shoreline space type identification method using remote sensing data that considers space-channel attention multi-scale features - Shijiao Qiao; Wanlai Xue; Kun Jia; Jie Li; Mu Xia; Zhulin Chen; Haiying Jiang; Bo Yuan; Guofeng Tao; Yuran Cui; Linlin Zhao; Zihang Jiang; et al. (International Journal of Remote Sensing, 2025)

Insight into peroxidase-mediated Pinus massoniana resin browning, and browning inhibition strategy - Hanxiao Liu; Xiaopeng Chen; Dandan Yu; Siheng Zhang; Jiezhen Liang; Xin Li; Xiaojie Wei; Linlin Wang (Sustainable Chemistry and Pharmacy, 2025)

VAP27-1 interacts with KCS6 and CER2 to facilitate the biosynthesis of very- long-chain fatty acids - Haiyan Wang; Yifan Li; Qinyao Wang; Mengxia Wu; Ruiyuan Wang; Xinran Han; Lin Liu; Ting Liu; Chunmei Shi; Linlin Zhong; Hongyan Zhang; Yunjiang Cheng; et al. (Plant Science, 2025)

Explicit dynamics simulation study to determine the damage patterns of apples (Red Fuji) under impact loading - Zixu Chen; Linlin Sun; Linlong Jing; Yi Liu; Jingwei Sun; Junsheng Liu; Hongjian Zhang; Jinxing Wang (Journal of Stored Products Research, 2025)

Lactobacillus plantarum reduces polystyrene microplastic induced toxicity via multiple pathways: A potentially effective and safe dietary strategy to counteract microplastic harm - Liuting Shi; Changyin Wu; Yuye Wang; Linlin Wang; Peijun Tian; Ke-xin Shang; Jianxin Zhao; Gang Wang (Journal of Hazardous Materials, 2025)

One-step synthesis of K3PO4-activated phosphorus-enriched carbons for enhanced carbon capture - Yue Zhi; Yujia Yin; Quji Ciren; Qiang Xiao; Leihong Zhao; Muslum Demir; Utku Bulut Simsek; Xin Hu; Linlin Wang (Journal of Environmental Chemical Engineering, 2025)

Phospholipids and phosphoprotein-encapsulated silver nanoparticles: An eco-friendly and green antibacterial agent for killing bacteria and promoting chronic wound healing - Qian Cai; Wenting Chen; Haoying Zhang; Chuyu Tang; Songjing Zhong; Qinyu Zhao; Zhuo Wang; Chao Wu; Liugen Zheng; Yuanyuan Cheng; Linlin Li (Journal of Environmental Chemical Engineering, 2025)

Floated Bi4Ti3O12@MoS2 p-n heterojunction anti-fouling hydrogels for efficient seawater purification - Ying Liu; Bingyan Ni; Ruotong Ru; Linlin Zhang; Hongfei Sun; Jianjun Liao; Cheng Li; Dexin Wang; Xiaodong Zhang; Wei Zhou (Journal of Environmental Chemical Engineering, 2025)

The emulsion-filled gels with different fat contents exhibit various friction behavior and dynamic fat-related texture perception at different temperatures - Yueji Zeng; Sihan Zhang; Ke Fan; Shuo Mu; Yang Luo; Linlin Wang; Xiankang Fan; Fuqing Wang; Ran Wang; Jie Luo (Food Quality and Preference, 2025)

Screening of hypoglycemic and probiotic properties of Pediococcus acidilactici FM-Pa-JXM94 and exploring the potential hypoglycemic mechanism - Ying Wang; Hui Zhang; Xingna Wang; Yu Zhang; Linlin Fan; Yanhong Ma; Xiaoli Liu (Food Bioscience, 2025)

Differences in the distribution of exogenous nucleotide intake in the colon of neonatal rats and its impact on early-life metabolism, gut, gut microbiota, and skeletal development - Zhihao Qu; LiLi Zhu; Min Guo; Kexin Shang; Peijun Tian; Linlin Wang; Gang Wang; Heng Zhang; Wei Chen (Food Bioscience, 2025)

Dual-responsive gelatin/fucoidan-based membrane with colorimetric and control-released performance for meat freshness monitoring and preservation - Linlin Li; Haoran Wang; Yimeng Zhang; Wei Ji; Minmin Chen; Baocai Xu; Hualin Wang (Food Packaging and Shelf Life, 2025)

Glycyrrhizic acid alleviates gefitinib-induced liver injury by regulating the p53/p21 pathway and releasing cell cycle arrest - Min Li; Shuaijun Peng; Jingjing Bu; Siqi Quan; Liming Liu; Zhouli Yue; Linlin Wang; Yucheng Li (Food and Chemical Toxicology, 2025)

Nitrogen-rich carbon nitride activated peroxymonosulfate for the efficient photodegradation of 2, 4-dichlorophenol: Performance and mechanism insight - Tianyu Zhou; Siyi Wang; Meng Tai; Juan Du; Dongshu Sun; Guangbo Che; Linlin Liu; Chunhong Ma; Bo Hu (Environmental Research, 2025)

Synergizing lattice matching and transient N–Li bonds to boost sulfur redox kinetics and regulate uniform lithium deposition in practical Li–S batteries - Yantao Wang; Huiqin Chen; Wenjuan Wu; Jinlong Li; Guangxin Zhang; Chunyan Wei; Shiyu Wang; Linlin Zhang; Yanping Zheng; Huanhuan Li (Chemical Engineering Journal, 2025)

Performance and mechanism of tris(2-chloropropyl) phosphate (TCPP) removal in an iron-carbon microelectrolysis constructed wetland system - Yongqiang Wang; Linlin Li; Xiaochun Guo; Aiwen Wang; Yunhao Pan; Jun Ma; Shaoyong Lu; Dongmei Liu (Chemical Engineering Journal, 2025)

Polysaccharides from traditional Chinese medicine and their nano-formulated delivery systems for cancer immunotherapy - Linlin Sun; Yuting Liu; Qihui Sun; Guimei Wang; Baoxiang Du; Bodong Liu; Tian Gao; Pan Zhao; Yong Yang; Rong Rong (Carbohydrate Polymers, 2025)

Hydrological Connectivity Induces Changes in Macrobenthos Functional Feeding Groups in a Typical Tidal Creek System of the Yellow River Delta - Qinglu Fu; Li Chen; Debin Sun; Jiao Wang; Jing Chen; Baoquan Li; Linlin Chen (Wetlands, 2025)

MVPCR: Multiplex Visual Detection Strategy Based on Ultrafast PCR for Point-of-Care Pathogens Detection Within 10 Min - Ziqin Zhang; Cui Wu; Linlin Bai; Kaiming Guo; Ting Wang; Dianwei Liu; Mingrui Zhu; Feng Qian; Fang Zhang; Rui Wang (Phenomics, 2025)

Nine-year biochar history increases topsoil nitrogen stocks and reduces the refractory organic nitrogen fractions in deep soils - Di Wang; Shuai Liu; Liwei Hao; Qi Yue; Linlin Jiang; Yu Lan; Wenfu Chen (Journal of Soils and Sediments, 2025)

Combined toxicity of decabromodiphenyl ethane and Pb on earthworms (Eisenia fetida) based on multiple biomarker responses - Meiqing Jin; Yuanchao Sun; Bing Chai; Minghu Wang; Yuping Wu; Weihong Wu; Qingwei Zhou; Linlin Qiu; Jia Du; Li Fu (Journal of Soils and Sediments, 2025)

Optimized Soil Nitrogen Management for Enhanced Photosynthetic Efficiency and Yield in High-Quality Japonica Rice in the Taihu Lake Region - Yunsheng Song; Yulin Xie; Minghui Dong; Fei Chen; Xiuliang Jin; Yajie Hu; Junrong Gu; Peifeng Chen; Yongliang Zhu; Linlin Shi; Yixiao Wang (International Journal of Plant Production, 2025)

Inter-trophic networks reveal the central role of methanogens in deposited estuarine soils - Linlin Wang; Xiongfeng Du; Wenli Shen; Songsong Gu; Zhaojing Zhang; Zheng Zhang; Baohua Xie; Guangxuan Han; Ye Deng (Soil Ecology Letters, 2025)

Changes in intergranular air properties and fatty acid profile of wheat bulk in a large warehouse with air-conditioned oversummering - Mengya Wang; Minghui Zhao; Xuhui Zhuang; Jianzhang Wu; Xingjun Li; Linlin Song; Yushan Jiang (Journal of Stored Products Research, 2025)

Optimized immobilization of lead and cadmium in soil using dithiocarboxy functionalized silica: A long-term effectiveness study - Mingming Lian; Chaoran Li; Longfei Wang; Liyong Niu; Linlin Zhao; Dongdong Wu; Zongsheng Zhao; Xiaohong Li; Zhijun Zhang (Journal of Hazardous Materials, 2025)

The promotion mechanism of ammonia-based CO2 capture by hydroxyl and amine additives: A molecular dynamics and DFT study - Jiaxing Du; Wu Yang; Linlin Xu; Jiaming Chen; Zijian Song; Ben Wang; Lushi Sun (Fuel, 2025)

The influence of different drying methods on the molecular structure and digestive resistance of type 3 resistant starch (RS3) - Qing Su; Linlin Sun; Lirong Chen; Xingya Wang; Kaichang Liu; Kuijie Gong (Food Chemistry, 2025)

Low-molecular-weight carrageenan prepared by photocatalysis-freeze-thaw circle and its in vivo distribution after oral administration - Chen Song; Zhejin Chen; Linlin Wang; Nan Wang; Jie Tian; Chunqing Ai; Shuang Song (Food Hydrocolloids, 2025)

Inactivation activity and mechanism of natural antimicrobial agents against Alicyclobacillus spp. in apple juice - Rui Cai; Linlin Gao; Yuxiang Zhang; Lu Cui; Yahong Yuan; Zhouli Wang; Tianli Yue (Food Control, 2025)

Polystyrene microplastics (PS-MPs) harness copper presence and promote impairments in early zebrafish (Danio rerio) larvae: Developmental, biochemical, transcriptomic approaches and nontargeted metabolomics approaches - Liqiao Zhang; Dongqiu Guo; Xinrui Dong; Longxiao Liu; Mengqi Jiang; Linlin Song; Xia Wang (Environmental Research, 2025)

Spatiotemporal variations of dissolved nitrous oxide concentrations in small water bodies in a typical urban landscape in eastern China - Xuebing Chen; Yuye Shen; Yihong Liu; Fangfang Zhang; Linlin Tian; Jing Wang; Yanjiang Cai; Yan Li; Scott X. Chang (Environmental Pollution, 2025)

Size-dependent internalization of gold nanoparticles in individual Tetrahymena thermophila characterized by single-cell mass cytometry - Junjie Ma; Yaquan Liu; Liu Zhang; Linlin Yao; Yun Ding; Hua Qin; Ziniu Wang; Xuehan Zheng; Xinyue Yang; Haijiang Tian; Li Zeng; Liqun Chen; et al. (Environmental Pollution, 2025)

Effective remediation of benzo [a] anthracene contaminated soil by combination of low-temperature thermal desorption and advanced oxidation - Yangyang Ma; Chiquan He; Linlin Yang; Xiaoyan Liu; Feifei Wang (Chemical Engineering Journal, 2025)

Physical contraction strategy for large-scale fabrication of reduced graphene oxide-coated solid phase microextraction fibers - Linlin Wei; Jianyun Sun; Xingguo Wang; Ting Qi; Aiying Song; Rong Liu; Xinghe He (Analytica Chimica Acta, 2025)

The Use of Surrogate Matrix for Calibrators in the Analysis of Dried Blood Samples – A Feasibility Study - Dong Hun Lee; Iris Xie; Matthew Solomon; Ming Wang; Linlin Luo; Eric Woolf (The AAPS Journal, 2025)

Transcranial Magnetic Stimulation Alleviates Spatial Learning and Memory Impairment by Inhibiting the Expression of SARM1 in Rats with Cerebral Ischemia–Reperfusion Injury - Linlin Jiang; Yule Wang; Yingxi He; Ying Wang; Hao Liu; Yu Chen; Jingxi Ma; Ying Yin; Lingchuan Niu (NeuroMolecular Medicine, 2025)

Development and validation of a prediction model for the depressive symptom risk in commercial airline pilots - Jie Zhang; Xuhua Chen; Lin Zhang; Haodong Qi; Erliang Zhang; Minzhi Chen; Yiran Wang; Yunfei Li; Yan Chen; Qingqing Duan; Feng Shi; Linlin Wang; et al. (EPMA Journal, 2025)

Boosting catalytic performance of N doped porous carbon derived from coal tar pitch: The role of N species and the contribution of 1O2 - Linlin Huang; Xuwen Zhang; Lin Wang; Tingting Liu; Da Li; Tao Sheng; Caiyu Sun; Lixin Li (Journal of Water Process Engineering, 2025)

Estimating groundwater discharge in the dam-affected rivers using 222Rn - Linlin Kong; Fu Liao; Peijie Yang; Guangcai Wang; Hanxiao Wang; Shengda Ding; Zhihao Wang; Huyang Ai; Pengpeng Zhou; Zheming Shi (Journal of Hydrology, 2025)

Diffusion coefficients of water in CO2 under the condition of CO2 sequestration in saline aquifers - Zhe Wang; Linlin Lin; Huirong Guo; Wanjun Lu (Journal of Hydrology, 2025)

Convert iron tailings waste into a novel Mg-Fe-Al hybrid magnetic coagulant for enhanced pretreatment of swine wastewater - Linlin Hao; Jingshuang Yan; Jiaoying Guo; Nannan Wang; Ming Zeng (Journal of Environmental Chemical Engineering, 2025)

Innovative citric acid/polydopamine@sepiolite composites for efficient removal of Ni2+ and methylene blue in single and binary adsorption systems: Regulation and mechanism - Linlin Liang; Zefeng Ge; Wu Lei; Fengyun Wang; Mingzhu Xia; Zhihui Wang (Journal of Environmental Chemical Engineering, 2025)

Functionality-dependent removal efficiency and mechanisms of polystyrene microplastics by a robust magnetic biochar - Xiaotong Duan; Xian Chen; Linlin Shi; Yiran Cao; Yuechang Liang; Tianyu wang; Chen Huang; Yuxin Cao (Journal of Environmental Chemical Engineering, 2025)

Evaluation of the virulence characteristics of ST11 Salmonella enterica from different sources using a 2D cell model - Linlin Xiao; Yulin Long; Binru Gao; Ying Hu; Tantao Zhang; Qian Xiao; Xiaojie Qin; Xuejuan Xia; Xiang Wang; Zhuosi Li; Qingli Dong (International Journal of Food Microbiology, 2025)

Correlation between the physicochemical and bacteriological qualities of pickled chili pepper (Paojiao) and its nitrite degradation study - Jianhui Wang; Miao Liu; Linlin Ye; Xiaoyi Hou; Zhenyu Li; Linzhi Tang; Na Deng; Hui Li (Food Bioscience, 2025)

Tanshinone IIA@β-cyclodextrin encapsulated with Eucommia ulmoides rubber/acetylated starch film as novel oral delivery system for therapy of orthotopic colon cancer - Rui Zhao; Haoyu Wang; Shuyao Li; Lingling Wang; Xiaopeng Lei; Pai Peng; Linlin Du; Juane Dong (Carbohydrate Polymers, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Chaetocin inhibits the progression of neuroblastoma by targeting JAK2/STAT3 signaling pathway in SH-SY5Y cells - Ke Wang; Ye Li; Linlin Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

An adaptive session-incremental broad learning system for continuous motor imagery EEG classification - Yufei Yang; Mingai Li; Linlin Wang (Medical & Biological Engineering & Computing, 2025)

Association of Urinary Phthalate Metabolites with Lipid Profiles and the Mediating Role of Serum Globulin: A Repeated-Measures Study - Kun Huang; Linlin Liu; Lei Zhao; Miao Liu; Chongjian Wang; Wenting Guo; Huihua Yang; Rui Zhu; Xiaomin Zhang (Exposure and Health, 2025)

Environmental heterogeneity drives the spatial distribution of macrobenthos in the Yellow River Delta wetland - Qinglu Fu; Jiao Wang; Debin Sun; Jianyu Chi; Wenzheng Fan; Yu Li; Yilin Wang; Baoquan Li; Linlin Chen (Aquatic Sciences, 2025)

Exploring Boundary Layer Physics and Atmospheric Chemistry in Megacities: Insights from the Beijing 325 m Meteorological Tower - Yele Sun; Zifa Wang; Linlin Wang; Xueling Cheng; Weiqi Xu; Yu Shi; Wei Zhou; Yan Li; Fei Hu; Zhiqiu Gao; Zhongxiang Hong (Advances in Atmospheric Sciences, 2025)

Magnetic resonance spectroscopy for discriminating primary angiitis of the central nervous system from gliomas and lymphomas - Ping Lu; Lingyun Cui; Lulin Zhang; Huabing wang; Linlin yin; Decai Tian; Xinghu Zhang (Acta Neurologica Belgica, 2025)

An enhanced machine learning model for urban air quality forecasting under intense human activities - Yelin Wang; Feiyang Xia; Linlin Yao; Shunyu Zhao; Youjie Li; Yanpeng Cai (Urban Climate, 2025)

Current and future thermal effects and spatial optimization modelling of urban greenspace in megacity - Rundong Feng; Shenghe Liu; Fuyuan Wang; Bin Chen; Kaiyong Wang; Linlin Xu (Sustainable Cities and Society, 2025)

Identification and characterization of ClAPRR2, a key candidate gene controlling watermelon stripe color - Shuang Liang; Miaomiao Yang; Linlin Zhang; Xufeng Fang; Xian Zhang; Chunhua Wei; Zuyun Dai; Zhongzhou Yang; Chaonan Wang; Bin Liu; Feishi Luan; Shi Liu (Plant Science, 2025)

Hydrogen gas enhances Arabidopsis salt tolerance by modulating hydrogen peroxide-mediated redox and ion homeostasis - Linlin Xiao; Yueran Hu; Yiting Wang; Chengsi Lv; Na Zhan; Hongying Duan; Jiuchang Su (Plant Science, 2025)

Antifungal activity and active compound identification of Myrothecium spp. against grape anthracnose and gray mold - Linlin Gao; Yijie Zhai; Jiajia Wu; Yuwei Li; Yanchun Fan; Junqiang Guo; Xiping Wang; Zhi Li (Pesticide Biochemistry and Physiology, 2025)

An expert-demonstrated soft actor–critic based adaptive trajectory tracking control of Autonomous Underwater Vehicle with Long Short-Term Memory - Yuxuan Wang; Yaochun Hou; Zhounian Lai; Linlin Cao; Weirong Hong; Dazhuan Wu (Ocean Engineering, 2025)

Cyclic plasticity of hardened oil well cement paste: A nonlinear kinematic hardening perspective - Linlin Wang; Shuo Chen; Shuitao Zhang; Jiyun Shen; Rongwei Yang (Geomechanics for Energy and the Environment, 2025)

Volatile profile of postharvest hardy kiwifruits treated with chitosan-silica nanocomposite coatings - Mengyuan Cao; Chengkui Qiao; Lijun Han; Ming Zhuang; Shiyu Wang; Rongli Pang; Linlin Guo; Mingqin Yang; Momo Gui (Food Research International, 2025)

Residual behaviors and health risk assessment of dinotefuran, flonicamid, and their metabolites during apple growth, storage, and processing - Fajun Tian; Zhenzhen Zhou; Junfeng Lu; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie (Food Research International, 2025)

Enhancement of farinographic characteristics of rice dough and rice bread quality with combined chemical and enzymatic approaches - Huining Zhang; Wanshan Yang; Yuhan Jiang; Haoyu Li; Menglu Yang; Zhiqi Wang; Bing Wang; Linlin Liu; Hongchen Fan; Fenglian Chen; Ying Liu (Food Bioscience, 2025)

Fabrication and characterization of gelatin/carboxymethyl chitosan composite film incorporated with carvacrol and its preservation efficacy in Chinese mitten crab (Eriocheir sinensis) - Anthony Pius Bassey; Xiaozhen Cui; Isaiah Henry Ibeogu; Fan Wang; Mustapha Muhammad Nasiru; Hadiza Kabir Bako; Linlin Fan; Xiaoli Liu (Food Hydrocolloids, 2025)

Butyrylated modification of corn starch alleviates autism-like behaviors by modulating 5-hydroxytryptamine metabolism and gut-brain neural activity - Wentian Li; Qingmin Kong; Min Guo; Linlin Wang; Peijun Tian; Jingyu Lu; Jianxin Zhao; Wei Chen; Gang Wang (Carbohydrate Polymers, 2025)

TRIM21 Promotes Endothelial Cell Activation via Accelerating SOCS3 Ubiquitination Degradation in Atherosclerosis - Zhenxuan Hao; Yihuan Wang; Linlin Chen; Yanjun Zhou; Dezhou Fang; Wenxiang Yao; Lili Xiao; Yanzhou Zhang (Cardiovascular Toxicology, 2025)

Research on real-time monitoring and early warning of Tangshan road surface subsidence based on InSAR - Mingzhou Bai; Yanli Qi; Linlin Song; Qihao Wang; Zilun Zhang; Gang Tian (Advances in Space Research, 2025)

Bivariate Spatial Autocorrelation Analysis of Keshan Disease and Hair Selenium of Residents in Heilongjiang Province, China - Jiacheng Li; Guijin Li; Cheng Wang; Huixin Sun; Linlin Du; Shuxiu Hao; Qingyu Zeng; Cunqi Lv; Yu Zhang; Xinshu Wang; Zhifeng Xing; Tong Wang (Biological Trace Element Research, 2025)

Spatial Clusters of Low Serum Selenium: the Priorities of Selenium Supplementation to Residents of Keshan Disease Endemic Areas - Qingyu Zeng; Guijin Li; Ruixiang Wang; Cunqi Lv; Shuxiu Hao; Jiacheng Li; Huixin Sun; Linlin Du; Cheng Wang; Yu Zhang; Xinshu Wang; Yuehui Jia; et al. (Biological Trace Element Research, 2025)

The impact of energy metabolic pattern on household carbon emissions: A spatio-temporal perspective in Guangdong-Hong Kong-Macao Greater Bay Area - Lei Chen; Jiahan Luo; Guotian Cai; Linlin Xia; Yongyang Wang; Linyu Xu (Sustainable Cities and Society, 2025)

Experimental and numerical investigation of flow field characteristics and local scour around trapezoidal artificial reefs - Mingda Yang; Yanli Tang; Linlin Wang; Fenfang Zhao; Shuyue He (Ocean Engineering, 2025)

The role of telomere shortening in ambient ozone exposure-related insulin resistance - Ruiying Li; Gongbo Chen; Wei Liao; Yinghao Yuchi; Xiaohuan Yang; Ziyuan Zhang; Xiaotian Liu; Zhenxing Mao; Linlin Li; Jiahui Zhao; Huijun Li; Wenqian Huo; et al. (Journal of Hazardous Materials, 2025)

Improvement of 3D printing and subsequent microwave freeze-drying solidification accuracy of pineapple gel-based inks: Infill percentage control and internal models design - Yunfei Bao; Wenchao Liu; Linlin Li; Guangyue Ren; Chung Lim Law; Weiwei Cao; Jiayao Wang; Zhenjiang Luo; Junliang Chen; Xu Duan (Journal of Food Engineering, 2025)

Failure and post-failure kinematic disaster processes of columnar rock masses based on 3D discontinuous deformation analysis - Ke Ma; Shengze Zhao; Guoyang Liu; Jianbin Miao; Jiashuo Kang; Linlin Wang; Qun Yu (International Journal of Rock Mechanics and Mining Sciences, 2025)

About 868 cal. yr BP tsunami event at the northern South China Sea revealed from offshore sediments - Yuming Wang; Xiaohong Chen; Adam D. Switzer; Linlin Li; Yang Xu; Yukun Wang; Elaine Tan; Peizhen Zhang (Global and Planetary Change, 2025)

Characterization and genome analysis of Pseudomonas phages isolated from various sources related to chilled chicken - Haijing Hu; Linlin Cai; Liangting Shao; Xinglian Xu; Huhu Wang; Guanghong Zhou (Food Research International, 2025)

Ecological restoration orientated application and modification of constructed wetland substrates - Jiapeng Yang; Shuiping Cheng; Yongqiang Wang; LinLin Li; Shaoyong Lu (Environmental Research, 2025)

Lactic acid bacteria reduce polystyrene micro- and nanoplastics-induced toxicity through their bio-binding capacity and gut environment repair ability - Liuting Shi; Xin Teng; Changyin Wu; Tengxun Zhang; Xing Jin; Linlin Wang; Peijun Tian; Ke-xin Shang; Jianxin Zhao; Chitong Rao; Gang Wang (Environmental Pollution, 2025)

Earthquake-induced Submarine Landslides (EQISLs) and a comparison with their Terrestrial Counterparts: Insights from a New Database - Peng Du; Linlin Li; Achim Kopf; Dawei Wang; Kejie Chen; Huabin Shi; Weitao Wang; Xiaoyi Pan; Gui Hu; Peizhen Zhang (Earth-Science Reviews, 2025)

Spatiotemporal evolution of wildfire activity during the Paleocene-Eocene Thermal Maximum in China - Xue-Ting Wang; Zuoling Chen; Linlin Cui; Xu Wang (Science China Earth Sciences, 2025)

Ferroptosis-Related Gene Signatures in Epilepsy: Diagnostic and Immune Insights - Xueying Li; Lei Wu; Linlin Sun; Han Liu; Xuezhu Qiao; Na Mi; Shi Yan; Xinyu Zhang; Kun Wang; Pusheng Quan; Fan Yang; Lifen Yao (Molecular Neurobiology, 2025)

Chromosome-Level Genome Assembly and Comparative Genomic Analysis of Planiliza haematocheilus: Insights into Environmental Adaptation and Hypoxia Tolerance Mechanisms - Ruizhi Wang; Na Song; Linlin Zhao (Marine Biotechnology, 2025)

Provincial localization framework for SDGs in China: Enhancing support for sustainable governance - Wen Song; Shisong Cao; Mingyi Du; Linlin Lu; Huadong Guo; Sirui Wang; Yue Liu; Xiaoxuan Li (Applied Geography, 2025)

RBM15 Knockdown Impairs the Malignancy of Cervical Cancer by Mediating m6A Modification of Decorin - Huimin Wang; Chun Li; Qiong Wei; Enjing Zhang; Yi Yang; Linlin Sha; Dan Wang (Biochemical Genetics, 2025)

Effect of Feeding Mice Soluble Metals and Heavy Metal Contaminated Soil on Feces Metal Concentrations - Ningning Xu; Liping Li; James A. Ippolito; Weiqin Xing; Yale Wang; Baozhong Zhang; Yongqiang Yang; Ling Bai; Linlin Zhao (Biological Trace Element Research, 2025)

Lactic acid bacteria in relieving constipation: mechanism, clinical application, challenge, and opportunity - Tong Zhang; Wenxu Liu; Huimin Lu; Ting Cheng; Linlin Wang; Gang Wang; Hao Zhang; Wei Chen (Critical Reviews in Food Science and Nutrition, 2025)

Contribution of mitochondria to postmortem muscle tenderization: a review - Feng Huang; Zhenjiang Ding; Jinsong Chen; Bing Guo; Linlin Wang; Chunmei Liu; Chunhui Zhang (Critical Reviews in Food Science and Nutrition, 2025)

A comprehensive review on iron‒carbon microelectrolysis constructed wetlands: Efficiency, mechanism and prospects - Yongqiang Wang; Linlin Li; Xiaochun Guo; Aiwen Wang; Yunhao Pan; Jun Ma; Shaoyong Lu; Dongmei Liu (Water Research, 2025)

Salmonella enterica serovar typhimurium effectors spiA and spiC promote replication by modulating iron metabolism and oxidative stress - Keyuan Chen; Jing Wang; Ting Hu; Yiqing Zhao; Yi Wu; Xue Wang; Wei Li; Guiyan Yang; Linlin Zhang; Jiufeng Wang; Yaohong Zhu (Veterinary Microbiology, 2025)

Indian summer monsoon variations since late MIS3: A perspective from multiproxy evidence from Lake Xingyun in southwestern China - Haiyang Yu; Linlin Cui; Xu Wang; Xueyun Ma; Bing Xu; Wubiao Li; Xueting Wang (Quaternary International, 2025)

Corrigendum to “The latest activity of the slope fault zone (Pearl River Mouth) in northern South China Sea and implications for earthquake hazard assessments” [166 (2024) 106937] - Liangwei Lv; Zhigang Li; Dawei Wang; Weitao Wang; Xiangming Dai; Fanchang Zeng; Linlin Li; Hao Liang; Gege Hui; Weiwang Long; Peizhen Zhang (Marine and Petroleum Geology, 2025)

Global distribution pattern and conservation of the cosmopolitan cold-water coral species Desmophyllum dianthus under climate change - Wenhao Huang; Zongling Wang; Fangyuan Qu; Chang Zhao; Miaozhuang Zheng; Zhaohui Zhang; Shenghao Liu; Qinzeng Xu; Xuelei Zhang; Linlin Zhao (Journal of Environmental Management, 2025)

Efficient and low resistance multi-functional UV resistant polyphenylene sulfide non-woven hollow membrane - Mengen Zhang; Qiyang Xi; Linlin Wang; Qinxing Xie; Zhenhuan Li; Maliang Zhang (Journal of Environmental Management, 2025)

Optimization model for co-pyrolytic synergy: A case study in starch sludge with chicken manure and comprehensive investigation combining kinetics, bio-products characterization, and DFT-based decomposition pathways - Hairong Mo; Xiaopeng Chen; Tongxi Mo; Chenghong Wu; Wanbin Wei; Yuanjie Wu; Qinxin Li; Jiezhen Liang; Linlin Wang (Fuel, 2025)

Dietary nucleotides drive changes in infant fecal microbiota in vitro and gut microbiota-gut-brain development in neonatal rats: A potential “nitrogen source” for early microbiota growth - Zhihao Qu; Bo Zhang; Guopeng Lin; Min Guo; Peijun Tian; Linlin Wang; Wei Chen; Heng Zhang; Gang Wang (Food Chemistry, 2025)

Enhanced dechlorination for multi-source solid wastes using gas-pressurized torrefaction and its removal mechanism - Jia Fu; Linlin Yi; Kaiyuan Li; Yan Zhang; Tong Zhang; Aijun Li; Tianrun Wang; Yanyan Zou; Xian Li; Hong Yao (Chemical Engineering Journal, 2025)

Bimetallic RuCo anchored CoFe2O4 nanosheets to realize in-depth electronic modulation for boosted structural reconstruction and efficient seawater electrolysis - Xueling Wei; Youjun Huang; Qiguan Wang; Linlin Dang; Kai Zhang; Qing Guo; Wenhu Li; Taotao Ai; Sumin Wang (Chemical Engineering Journal, 2025)

Sulfur-vacancy-enriched ZnIn2S4 mediates efficient charge transfer for hydrogen evolution from lignocellulose photoreforming - Jiang He; Zhongqing Yang; Ziqi Wang; Linlin Gu; Jiaqi Qiu; Jingyu Ran (Chemical Engineering Journal, 2025)

Plant extracellular vesicles contribute to the amplification of immune signals during systemic acquired resistance - Wenjing Wang; Junsong Zhang; Liying Pan; Zijia Liu; Weiwei Yi; Xiaolong Xing; Linlin Bai; Qiao Liu; Qingbin Chen; Lingyu Mi; Qingfeng Zhou; Dongli Pei; et al. (Plant Cell Reports, 2025)

BI1 Activates Autophagy and Mediates TDP43 to Regulate ALS Pathogenesis - Yu Wang; Yuxiang Wang; Hanlan Yin; Zixuan Xiao; Zhichao Ren; Xueting Ma; Jingtian Zhang; Xueqi Fu; Fuqiang Zhang; Linlin Zeng (Molecular Neurobiology, 2025)

BDNF-VGF Pathway Aggravates Incision Induced Acute Postoperative Pain via Upregulating the Neuroinflammation in Dorsal Root Ganglia - Wenjing Zhao; Lulin Ma; Daling Deng; Linlin Han; Feng Xu; Tianhao Zhang; Yafeng Wang; Shiqian Huang; Yuanyuan Ding; Shaofang Shu; Xiangdong Chen (Molecular Neurobiology, 2025)

Pharmacokinetics of seven major components in Aβ1-42-treated rats after oral administration of an aqueous extract of Curculiginis Rhizoma and Epimedii Folium - Junzuo Zheng; Jun Wang; Linlin Chen; Xuelian Jiang; Xuesong Zhang; Wenqi Ai; Yuman Xie; Ping Wang; Zhou Lan; Xiaoping Ding (Journal of Natural Medicines, 2025)

Comprehensive host cell proteins profiling in biopharmaceuticals by a sensitivity enhanced mass spectrometry strategy using TMT-labeling and signal boosting - Andong Xue; Linlin Kong; Jialin Li; Yuxin Jiao; Zhishang Hu; Bin Fu; Guibin Wang; Wanjun Zhang; Jianheng Li; Weijie Qin (Analytica Chimica Acta, 2025)

Study on strengthened the Cd(II) adsorption based on co-culture of fungi and cyanobacteria - Linlin Cui; Junjun Wang; Xueling Wu; Jiaokun Li; Weimin Zeng; Guanzhou Qiu; Li Shen (Algal Research, 2025)

Towards a dialectical understanding of rural resilience and rural sustainability: bibliometric analysis and evidence from existing literature and China - Huan Li; Tao Xu; Chen Yang; Yang Fu; Changyan Wu; Linlin Zhang; Guoliang Xu; Wei Wang (Environment, Development and Sustainability, 2024)

Temperature related to the spatial heterogeneity of wetland soil total nitrogen content in a frozen zone - Linlin Wu; Mingchang Wang; Dehua Mao; Xiaoyan Li; Zongming Wang (Soil and Tillage Research, 2024)

Transfer dynamics of antimicrobial resistance among gram-negative bacteria - Bangjuan Wang; Muhammad Haris Raza Farhan; Linlin Yuan; Yuxin Sui; Jinhua Chu; Xiaohan Yang; Yuxin Li; Lingli Huang; Guyue Cheng (Science of The Total Environment, 2024)

Organotin exposure and DNA methylation in non-syndromic cleft lip and palate: Integrating findings from case-control studies and animal experiments - Yongyan Chen; Qianhui Cheng; Sainan Li; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Science of The Total Environment, 2024)

N18 ring: A building block for constructing 1D and 2D polymeric nitrogen frameworks - Yuxiang Gao; Ying Zhang; Shuang Liu; Bo Jin; Linlin Guo; Xu Guo; Zhen Yao; Peng Wang; Bingbing Liu (Science Bulletin, 2024)

Individual tree species classification using low-density airborne multispectral LiDAR data via attribute-aware cross-branch transformer - Lanying Wang; Dening Lu; Linlin Xu; Derek T. Robinson; Weikai Tan; Qian Xie; Haiyan Guan; Michael A. Chapman; Jonathan Li (Remote Sensing of Environment, 2024)

The mediating role of abnormal ZEB1 methylation in the association between nickel exposure and non-syndromic orofacial cleft - Yongyan Chen; Yaquan Pan; Lijun Liu; Yingnan Guo; Lei Jin; Aiguo Ren; Linlin Wang (Reproductive Toxicology, 2024)

NIR spectroscopy for quality assessment and shelf-life prediction of kiwifruit - Hongbo Li; Linlin Zhu; Na Li; Zhenbin Liu; Liheng Wang; Bimal Chitrakar; Dan Xu; Zhenkun Cui; Yanhua Tang; Liangbin Hu; Haizhen Mo (Postharvest Biology and Technology, 2024)

Total water level prediction at continental scale: Coastal ocean - Linlin Cui; Fei Ye; Y. Joseph Zhang; Haocheng Yu; Zhengui Wang; Saeed Moghimi; Gregory Seroka; Jack Riley; Shachak Pe'eri; Soroosh Mani; Edward Myers; Kyungmin Park; et al. (Ocean Modelling, 2024)

High mechanical property, hydrophobic and fire-retardant cellulose film derived from kenaf degumming wastewater - Shixing Wang; Xiaolong Qiao; Linlin Li; Hailong Lu; Yuanming Zhang; Guangting Han; Haoxi Ben; Wei Jiang (Journal of Environmental Chemical Engineering, 2024)

Simulation of diffusion of combustible refrigerants R1234yf and R290 leakage in automotive air conditioning - Linlin Wang; Yu He; Jiabao Ren; Dan Wang; Baomin Dai; Zhe Zhang (International Journal of Refrigeration, 2024)

The role of probiotics in the treatment of non-alcoholic fatty liver disease (NAFLD): New insights based on meta-analysis and subgroup analysis - Rui Xiao; Yang Cao; Linlin Wang; Peijun Tian; Qixiao Zhai; Jianxin Zhao; Gang Wang; Yu Zhu (Food Bioscience, 2024)

Low level exposure to BDE-47 facilitates the development of prostate cancer through TOP2A/LDHA/lactylation positive feedback circuit - Linlin Tian; Nan Zhou; Ning Zhao; Mengkai Qiao; Min He; Ziqing Mao; Wenjiong Xu; Dandan Xu; Yan Wang; Yan Xu; Tong Chen (Environmental Research, 2024)

Elementomics of 32 elements in cord serum depicts the risk of orofacial clefts: A case-control study in Shanxi, China - Jing Wei; Dezheng Fu; Siyu Guo; Tian Tian; Yun Huang; Zhiwen Li; Linlin Wang; Lei Jin; Weiping Ye; Aiguo Ren; Shengju Yin (Environmental Pollution, 2024)

Prenatal co-exposure to phthalate metabolites and bisphenols among non-syndromic cleft lip and/or palate in offspring - Sainan Li; Haiyan Zhu; Chen Yang; Chengrong Wang; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Environmental Pollution, 2024)

Constructing multi-functional carbon-based aerogels for highly efficient photo-thermal desalination and water purification - Yuqian He; Linlin Yan; Mi Zhou; Kai Wang; Yingjie Zhang; Enrico Drioli; Jun Ma; Xi Quan Cheng (Desalination, 2024)

Closed-loop recylcing of thermoset poly(vinylogous urethane) foams - Shihao Ji; Linlin Wang; Shengyu Feng; Lei Li (Chemical Engineering Journal, 2024)

Precise fabrication and superior combustion properties of n-B pomegranate microspheres based on a new dissolution-dispersion-coating method - Yushu Xiong; Baoxuan Li; Yinghong Wang; Linlin Liu; Jie Huang; Suhang Chen; Fengqi Zhao; Kangzhen Xu (Chemical Engineering Journal, 2024)

Effects of nitrogen fertilization on nitrogen metabolism and grain protein in premium-tasty japonica rice - Yunsheng Song; Minghui Dong; Yajie Hu; Linlin Shi; Junrong Gu; Yuxuan Wang; Shikun Wang; Penghui Cao; Yajie Yu; Yongliang Zhu; Yulin Xie; Zhongying Qiao; et al. (Cereal Research Communications, 2024)

Evaluating the phase evolution of CMIP GCMs for agricultural climate-change impact assessments in China - Linlin Yao; Qian Tan; Guanhui Cheng; Shuping Wang; Bingming Chen (Agricultural and Forest Meteorology, 2024)

Biocontrol potential of plant growth-promoting rhizobacteria against plant disease and insect pest - Qinhao Jian; Tongrui Zhang; Yingying Wang; Li Guan; Linlin Li; Longna Wu; Shiyan Chen; Yumei He; Hong Huang; Shugang Tian; Hu Tang; Litang Lu (Antonie van Leeuwenhoek, 2024)

Prospective study on the joint effect of persistent organic pollutants and glucose metabolism on chronic kidney disease: Modifying effects of lifestyle interventions - Dandan Wei; Jiayu Shi; Haoran Xu; Yao Guo; Xueyan Wu; Zhiwei Chen; Taimeng Chen; Huilin Lou; Erbao Han; Guozhen Han; Yumeng Yan; Xiaotian Liu; et al. (Science of The Total Environment, 2024)

Source identification of microplastics in highly urbanized river environments and its implications for watershed management - Huaihao Shao; Qiankun Wang; Linlin Wang; Xiaoyu Lei; Shuangliang Dai; Tian Li; Xiaoshan Zhu; Xian-zhong Mao (Science of The Total Environment, 2024)

The role of trade policy uncertainty on contemporaneous and lagged connectedness between critical raw materials and high-tech markets: Evidence from China - Wang Gao; Linlin Zhang; Haizhen Zhang; Hongwei Zhang (Resources Policy, 2024)

Artificial river flow regulation triggered spatio-temporal changes in marine macrobenthos of the Yellow River Estuary - Debin Sun; Jiao Wang; Qinglu Fu; Linlin Chen; Jing Chen; Teng Sun; Baoquan Li (Marine Environmental Research, 2024)

Migration of depleted uranium from a corroded penetrator in soil vadose zone in Bosnia and Herzegovina - Cui Li; Yanru Liang; Yin Ye; Fan Chen; Markus Astner; David J. Paterson; Yanlong Chen; Linlin Wang; Paul Guagliardo; Matvei Aleshin; Mario Burger; Peter M. Kopittke; et al. (Journal of Hazardous Materials, 2024)

Exosomal miR-129-2-3p promotes airway epithelial barrier disruption in PM2.5-aggravated asthma - Caihong Wang; Zeyu Niu; Yan Zhang; Nannan Liu; Xiaotong Ji; Jiayu Tian; Linlin Guan; Dongxing Shi; Huiqiu Zheng; Yuhui Gao; Lifang Zhao; Wenping Zhang; et al. (Journal of Environmental Management, 2024)

Insights of using microbial material in fluoride removal from wastewater: A review - Linlin Cui; Junjun Wang; Hao Zhou; Shiyu Shao; Jue Kang; Xinyi Yu; Hongbo Zhao; Li Shen (Journal of Environmental Management, 2024)

Molecular epidemiological investigation of Salmonella isolated from the environment, animals, foods and patients in China - Linlin Xiao; Xiaojie Qin; Hu Xiao; Yuehua Gao; Tanmei Sun; Xiaolu Dong; Yulin Long; Xuejuan Xia; Zhuosi Li; Xiang Wang; Qingli Dong (Food Research International, 2024)

Decreased formulation pH and protein preheating treatment enhance the interaction, storage stability, and bioaccessibility of caseinate-bound lutein/zeaxanthin - Gang Zhang; Linlin He; Xin Qi; Xiao Wang; Yanna Zhao; Qingpeng Wang; Min Liu; Zhuang Ding; Zhengping Wang; Sangeeta Prakash (Food Research International, 2024)

The casein in sheep milk processed by cold plasma technology: Phosphorylation degree, functional properties, oxidation characteristics, and structure - Jiaying Zhang; Jiaqing Song; Shuangshuang Wang; Yangyu Su; Linlin Wang; Wupeng Ge (Food Chemistry, 2024)

Fabrication, characterization, and antibacterial properties of sodium alginate/chito-oligosaccharide gel beads - Nan Wang; Jie Tian; Linlin Wang; Chen Song; Chengrong Wen; Yinghuan Fu; Shuang Song (Food Hydrocolloids, 2024)

Rational design of pulse-electrolysis protocols promotes molten-salt electrorefining - Leyang Li; Ruiyang Sun; Rui Yuan; Manpeng Lin; Linlin Wang; Qi Wang; Jiguo Tu; Handong Jiao; Shuqiang Jiao (Chemical Engineering Journal, 2024)

Construction of covalent electrode/solid electrolyte interface for stable flexible solid-state lithium batteries - Junlong Zou; Linlin Wang; Jun Zhang; Qiyue Sun; Yongyin Wang; Mingtao Zheng; Yong Xiao; Hang Hu; Yingliang Liu; Yeru Liang (Chemical Engineering Journal, 2024)

High-value multilayer graphene oxide prepared by catalytic pyrolysis of petroleum tar and applications: Trash to treasure - Lu Liu; Jialin Wang; Yifei Wu; Linlin Yin; Wei Zuo; Yu Tian; Jun Zhang (Chemical Engineering Journal, 2024)

A metal-quercetin-histidine co-coordinated nanoparticle enhances cancer photothermal therapy via reshaping immunosuppressive tumor microenvironment - Shaobo Wang; Shuncheng Yao; Quanhong Hu; Zhuo Wang; Yunchao Zhao; Linlin Li (Chemical Engineering Journal, 2024)

Quantifying the changes in solute transport caused by human influence on river connectivity in inland river basins - Wenhao Zhang; Guofeng Zhu; Ling Zhao; Lei Wang; Dongdong Qiu; Linlin Ye; Siyu Lu; Xinrui Lin (CATENA, 2024)

The Environmental Niche of the Light Purse Seine Fleet in the Northwest Pacific Ocean Based on Automatic Identification System Data - Shenglong Yang; Lijun Wan; Linlin Yu; Jiashu Shi; Weifeng Zhou; Shengmao Zhang; Fei Wang; Zuli Wu; Yang Dai; Keji Jiang; Wei Fan (Journal of Marine Science and Engineering, 2024)
Ecosystem-based fisheries management requires high-precision fisheries information to provide relevant data for natural resource management, assessment, and marine spatial planning. This study utilizes Automatic Identification System (AIS) data from light purse seine vessels from the Chinese mainland that were collected from May to November between 2020 and 2022, along with the corresponding environmental data. By applying boosted regression trees (BRTs) and generalized additive models (GAMs), this study establishes nonlinear relationships between fishing intensity and predictor variables and explores the ecological and environmental drivers behind the spatial distribution of light purse seine vessels from the Chinese mainland in the Northwest Pacific. This research identifies the key influencing factors and reveals significant seasonal preferences for different marine environments in various months, with chlorophyll-a being the primary influencing factor. The predicted fishing effort closely resembles observed data, providing valuable information to support fisheries resource management and planning.

New Insights into Fish Diversity in the Yellow and Bohai Seas Based on Environmental DNA Technology - Xiaolin Wang; Li Wang; Aiyong Wang; Linlin Zhao (Fishes, 2024)
Marine biodiversity is increasingly threatened by overfishing and marine pollution. A comprehensive understanding of the biodiversity in the Yellow and Bohai Seas is essential for resource conservation. This study conducted a large-scale survey of fishery resources in the Yellow and Bohai Seas to investigate fish community structure and diversity using eDNA technology. The results showed that 57 and 65 fish species were recorded in spring and summer, respectively, with 46 species identified in both seasons. A total of nine dominant species were identified in spring, mainly belonging to Perciformes, while seven dominant species were identified in summer, primarily from Clupeiformes. In different regions, no significant differences in fish α diversity were observed between spring and summer. However, significant seasonal differences were found in both α and β diversity. At the spatial level, fish species in the Yellow and Bohai Seas occupied similar ecological niches. However, at the temporal level, there are certain differences in the ecological niches of fish communities between seasons. Phylogenetic diversity showed no significant differences at the spatial scale, yet notable seasonal variations were observed at the temporal scale, with spring (661.46) significantly exceeding summer (540.30). The Mantel test indicated that nitrate and salinity were key environmental factors influencing α diversity. RDA analysis revealed that the dominant species in spring were mainly influenced by chlorophyll-a and water temperature, while those in summer were mainly affected by water depth, nitrite, water temperature, and salinity.

Decadal variation and temporal stability of the macrobenthic community in the Bohai Sea, China - Shaoyu Jiang; Jiao Wang; Wenzheng Fan; Linlin Chen; Jing Chen; Baoquan Li (Marine Pollution Bulletin, 2024)

Exploring the paradox of densification and greening in China’ s old cities - Wenqi Chen; Yuxuan Qiu; Linlin Ruan; Chun Ren; Chunfeng Zhou; Sucheng Xu; Kechao Wang; Tingting He; Wu Xiao (Urban Forestry & Urban Greening, 2024)

Environmental exposure patterns to 94 current-use pesticides in women of reproductive age who are preparing for pregnancy - Tian Tian; Fang Liu; Yu Fu; Junjie Ao; Shujian Lin; Qianhui Cheng; Kalbinur Kayim; Fei Kong; Linlin Wang; Xiaoyu Long; Yuanyuan Wang; Jie Qiao (Science of The Total Environment, 2024)

Ultrasensitive monitoring of PCB77 in environmental samples using a visible-driven photoelectrochemical sensing platform coupling with exonuclease I assisted in target recycling - Lining Su; Guizhen Wang; Linlin Zhao; Yuan Deng; Yujing Guo; Yong Xiao; Huanwen Wang; Chuan Dong; Lifang Fan (Science of The Total Environment, 2024)

Effect of silicon on the distribution and speciation of uranium in sunflower (Helianthus annuus) - Linlin Wang; Yanru Liang; Song Liu; Fan Chen; Yin Ye; Yanlong Chen; Jingjing Wang; David J. Paterson; Peter M. Kopittke; Yuheng Wang; Cui Li (Journal of Hazardous Materials, 2024)

Iron-nitrogen coupling mediates soil microbial community composition and gene expression during the formation of rusty root in Panax ginseng from three northeast provinces in China - Qiao Jin; Linlin Zhang; Keming Cao; Xiaoxi Pan; Zhengbo Liu; Yiming Guan; Xiangxi Zuo; Yayu Zhang; Qiuxia Wang (Journal of Environmental Chemical Engineering, 2024)

Effects of storage and processing on the residual distribution and behavior of five preservatives and their metabolites in pomegranate - Fajun Tian; Junfeng Lu; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie (Food Chemistry, 2024)

Characterization of low-molecular-weight fucoidan prepared by photocatalysis degradation and its regulation effect on metabolomics of LPS-stimulated macrophages - Lilong Wang; Linlin Wang; Jinhe Tian; Chunhong Yan; Chen Song; Shuangcai Xiao; Shuang Song (Food Bioscience, 2024)

Changes of 22 pesticide residues and 3 metabolites during the common processing of Auricularia auricula-judae - Mingqin Yang; Fayi Qin; Lijun Han; Chengkui Qiao; Ming Zhuang; Mengyuan Cao; Shiyu Wang; Rongli Pang; Linlin Guo (Food Control, 2024)

Source characteristics of the 2006 Pingtung earthquake doublet off southern Taiwan and the possible contribution of submarine landslides to the Tsunami - Gui Hu; Linlin Li; Kenji Satake; Tso-Ren Wu; Peitao Wang; D.J. Doong; Philip L.-F. Liu (Earth and Planetary Science Letters, 2024)

Provincial emission inventory of atmospheric polycyclic aromatic hydrocarbons (PAHs) in China - Jianbing Wang; Linlin Xia; Ruwei Wang (Atmospheric Environment, 2024)

Effect of sodium selenite on the synthesis of glucosinolates and antioxidant capacity in Chinese cabbage (Brassica rapa L.ssp.pekinensis) - Yafang Luo; Shuang Zhao; Huan Wang; Huixia Bai; Qi Hu; Linlin Zhao; Tianyi Ma; Zhenyu Fan; Yushu Wang (Physiology and Molecular Biology of Plants, 2024)

Turnover structures in macrobenthic communities rather than nestedness in the Yellow River Delta wetland, China - Jiao Wang; Shaoyu Jiang; Debin Sun; Jing Chen; Baoquan Li; Linlin Chen (Aquatic Sciences, 2024)

SLAM-PYE: Tightly coupled GNSS-binocular-inertial fusion for pitaya positioning, counting, and yield estimation - Hongjie Wang; Xiangyu Hong; Linlin Qin; Chun Shi; Gang Wu (Computers and Electronics in Agriculture, 2024)

The impact of block morphology on urban microclimates: A case study of three cities in cold regions of China - Linlin Guo; Xiaohua Guo; Baofeng Li; Endong Wang (Urban Climate, 2024)

An adaptive PID controller for path following of autonomous underwater vehicle based on Soft Actor–Critic - Yuxuan Wang; Yaochun Hou; Zhounian Lai; Linlin Cao; Weirong Hong; Dazhuan Wu (Ocean Engineering, 2024)

Association between spectrum of mycotoxins and semen quality: A cross-sectional study in Beijing, China - Chen Yang; Xiao Ning; Baojun Wang; Tian Tian; Yongyan Chen; Le Ma; Linlin Wang (Journal of Hazardous Materials, 2024)

Degradation of mycotoxins by pulsed light and evaluation of the safety of degradation products - Lige Qi; Xinyi Zhong; Linlin Gao; Rui Cai; Tianli Yue; Yahong Yuan; Zhouli Wang; Xubo Zhao (Journal of Food Engineering, 2024)

Transformation and environmental risk of 90Sr and 137Cs under extreme rainstorm at a proposed nuclear facility site in China - Jun Zhu; Ying Hao; Chao Chen; Ting Wang; Ke Chen; Linlin Zhang; Aiming Zhang; Tian Xie; Qiulan Zhang (Journal of Environmental Radioactivity, 2024)

Influence of mountain orientation on precipitation isotopes in the westerly belt of Eurasia - Longhu Chen; Guofeng Zhu; Qin Qin Wang; Linlin Ye; Xinrui Lin; Siyu Lu; Yinying Jiao; Rui Li; Gaojia Meng; Yuhao Wang; Jiangwei Yang; Chen Jia (Global and Planetary Change, 2024)

Immobilization of pancreatin based on ultrasound-assisted polydopamine functionalized magnetic porous chitosan for the detoxification of ochratoxin A in wine - Saiqun Wang; Tianmin Guo; Xiaoxue Mei; Xinyi Zhong; Linlin Gao; Rui Cai; Tianli Yue; Yahong Yuan; Zhenpeng Gao; Zhouli Wang (Food Chemistry, 2024)

Fabrication of polysaccharide-coated oleanolic acid-curcumin-coassembled nanoparticles (OA/Cur NPs): Enhancement of colloidal stability and water solubility - Linlin Yan; Han Liu; Yuhui Wang; Lulu Zhang; Chao Ma; A.M. Abd El-Aty (Food Chemistry, 2024)

Intelligent multi-colorimetric cellulose acetate/cobalt-based metal-organic framework antibacterial film and its application to pork preservation - Qianlan Tao; Yewen Xiao; Xuan Hu; Huaiting Pang; Feng Xiao; Linlin Li; Minmin Chen; Hualin Wang (Food Packaging and Shelf Life, 2024)

Association between concentrations of rare earth elements in chorionic villus and risk for unexplained spontaneous abortion - Meng Lin; Lailai Yan; Xiaoye Wang; Yutong Wang; Ying Zhou; Linlin Wang; Chan Tian (Environmental Research, 2024)

Experimental study and design methodology of sacrificial-energy dissipation beam-column joint - Xinzheng Lu; Xinlei Jin; Yuan Tian; Linlin Xie; Yixing Wang (Engineering Structures, 2024)

Constructing efficient lithium salt dissociation solid-state electrolytes with high conductivity and transference number of Li ions for stable all-solid-state lithium batteries - Zengcai Guo; Shimin Liao; Feng Li; Linlin Shi; Bihai Su; Jingbo Mu; Yanming Wang; Zhongkai Huang; Feng Xu; Chaowen Guan (Chemical Engineering Journal, 2024)

Boosting TNBC immune checkpoint blockade with an imaging-therapy coupled ozone delivery nano system - Linlin Song; Zhihui Liu; Xiujing He; Tianyue Xu; Meixu Chen; Zihan Xu; Haina Zhao; Jiaojiao Suo; Hong Wang; Zhankun Yang; Shenglan You; Xiaoting Chen; et al. (Chemical Engineering Journal, 2024)

Anti-cancer effects of nitazoxanide in epithelial ovarian cancer in-vitro and in-vivo - Xiangqun Yang; Zhenyan Liu; Xin Wang; Wenda Tian; Taoyu Zhao; Qiaoling Yang; Wenliang Li; Linlin Yang; Hongying Yang; Yue Jia (Chemico-Biological Interactions, 2024)

Dietary Potassium and Magnesium Intake with Risk of Type 2 Diabetes Mellitus Among Rural China: the Henan Rural Cohort Study - Jia Li; Yuqian Li; Chongjian Wang; Zhenxing Mao; Tianyu Yang; Yan Li; Wenguo Xing; Zhuoyang Li; Jiaoyan Zhao; Linlin Li (Biological Trace Element Research, 2024)

From trajectories to network: Delineating the spatial pattern of recreational walking in Guangzhou - Haochen Shi; Linlin Yao; Qiqi Liu; Yankai Wang; Zongcai Wei; Miaoxi Zhao; Ding Ma (Applied Geography, 2024)

A bibliometric analysis of blue carbon (1993–2023): evolution of research hot topics and trends - Shanshan Wang; Dandan Yan; Chenhao Wang; Linlin Wu; Yiming Huang (Frontiers in Marine Science, 2024)
Blue carbon refers to the carbon fixed in marine ecosystems such as mangroves, salt marshes, and seagrass beds. Considered a treasure house for capturing and storing carbon dioxide, it can alleviate environmental issues linked to climate change and positively influence the environments where people live. Thus, to clarify the hotspots and development trends of blue carbon research, bibliometric analysis incorporating ScientoPy and VOSviewer software were used to quantitatively analyze 4,604 blue carbon publications from Web of Science and Scopus databases between 1993 and 2023. The results indicate a rapidly growing number of published studies on blue carbon, with blue carbon research being multifaceted and gradually becoming an interdisciplinary and international topic. This study on blue carbon, which is based on keyword clustering analysis, comprises three stages. The analysis of the strength of the cooperative connections between scholars in various countries who have published work on blue carbon. found that the cooperation networks of developed countries are strong and those of developing countries are relatively weak. Quantitative trend analysis reveals a growing focus on the restoration and conservation of blue carbon ecosystems, with remote sensing being the predominant technology used in the blue carbon research field in recent years. In blue carbon research, increasing carbon sequestration capacity, climate change mitigation, and carbon sequestration in macroalgae remain potential hotspots for research and development.

Response of a Coral Reef Sand Foundation Densified through the Dynamic Compaction Method - Linlin Gu; Weihao Yang; Zhen Wang; Jianping Wang; Guanlin Ye (Journal of Marine Science and Engineering, 2024)
Dynamic compaction is a method of ground reinforcement that uses the huge impact energy of a free-falling hammer to compact the soil. This study presents a DC method for strengthening coral reef foundations in the reclamation area of remote sea islands. Pilot tests were performed to obtain the design parameters before official DC operation. The standard penetration test (SPT), shallow plate-load test (PLT), and deformation investigation were conducted in two improvement regions (A1 and A2) with varying tamping energies. During the deformation test, the depth of the tamping crater for the first two points’ tamping and the third full tamping was observed at two distinct sites. The allowable ground bearing capacity at two disparate field sites was at least 360 kPa. The reinforcement depths were 3.5 and 3.2 m in the A1 and A2 zones, respectively. The DC process was numerically analyzed by the two-dimensional particle flow code, PFC2D. It indicated that the reinforcement effect and effective reinforcement depth were consistent with the field data. The coral sand particles at the bottom of the crater were primarily broken down in the initial stage, and the particle-crushing zone gradually developed toward both sides of the crater. The force chain developed similarly at the three tamping energies (800, 1500, and 2000 kJ), and the impact stress wave propagated along the sand particles primarily in the vertical direction.

N-Doped Carbon Dots for Selective Detection of Fe3+ and Degradation of Fe3+/Basic Red 9 Complexes in Water Samples - Caixia Wang; Chengkui Qiao; Fajun Tian; Linlin Guo; Ruiping Wang; Jun Li; Tao Pang; Rongli Pang; Hanzhong Xie (Journal of Fluorescence, 2024)

Unlocking enhanced photocatalytic power: Donor-acceptor synergy in non-metallic g-C3N4 hollow nanospheres - Xinhua He; Xiandi Guo; Zijie Xia; Linlin Wang; Zheng Jiao (Chemosphere, 2024)

Determining toxicity of europium oxide nanoparticles in immune cell components and hematopoiesis in dominant organs in mice: Role of lysosomal fluid interaction - Min Li; Jie Gao; Linlin Yao; Liu Zhang; Danyang Li; Zikang Li; Qi Wu; Shunhao Wang; Jie Ding; Yaquan Liu; Minghao Wang; Gang Tang; et al. (Science of The Total Environment, 2024)

The latest activity of the slope fault zone (Pearl River Mouth) in northern South China Sea and implications for earthquake hazard assessments - Liangwei Lv; Zhigang Li; Dawei Wang; Weitao Wang; Xiangming Dai; Fanchang Zeng; Linlin Li; Hao Liang; Gege Hui; Weiwang Long; Peizhen Zhang (Marine and Petroleum Geology, 2024)

Ecological restoration for eutrophication mitigation in urban interconnected water bodies: Evaluation, variability and strategy - Linlin Wang; Huaihao Shao; Yuehua Guo; Hongsheng Bi; Xiaoyu Lei; Shuangliang Dai; Xianzhong Mao; Kai Xiao; Xiaomei Liao; Hao Xue (Journal of Environmental Management, 2024)

Spatial distribution and regional tectonic significance of the newly discovered Kalawenguquan fault in the interior of the Tian Shan Mountain Range, Western China - Xingao Li; Zhongtai He; Zhikun Ren; Linlin Li; Lei Wang; Haomin Ji; Xiaoxiao Zhu; Long Guo; Liangliang Wu (Journal of Asian Earth Sciences, 2024)

An integrated investigation combining network pharmacology and computer simulation dissects the potential mechanism of anti-obesity of Monascus pigments (MPs) - Jiaxing Li; Huijing Zhang; Linlin Xu; Huiqian Liu; Chenchen Qi; Chengtao Wang; Wei Chen (Food Bioscience, 2024)

Promoting the systematic utilization of reclaimed asphalt pavement (RAP) through waste asphalt-derived carbon in batteries applications - Danqing Li; Xin He; Hu Fu; Wenqi Tan; Shigang Lu; Linlin Wang; Mei Ding; Chunhui Gao; Chuankun Jia (Chemical Engineering Journal, 2024)

A novel multifunctional photocatalytic membrane based on ternary heterojunction TiO2@PDA@BiOBr for biochemical oily wastewater purification - Wei Ji; Yewen Xiao; Feng Xiao; Linlin Li; Minmin Chen; Hualin Wang (Chemical Engineering Journal, 2024)

Intermittent irrigation as a solution for reduced emissions and increased yields in ratoon rice systems - Lang Zhang; Linlin Li; Qiyuan Tang; Huaqin Xu; Huabin Zheng; Faming Wang; Jianwu Tang (Plant and Soil, 2024)

Myosin Va-dependent Transport of NMDA Receptors in Hippocampal Neurons - Ru Gong; Linwei Qin; Linlin Chen; Ning Wang; Yifei Bao; Wei Lu (Neuroscience Bulletin, 2024)
N-methyl-D-aspartate receptor (NMDAR) trafficking is a key process in the regulation of synaptic efficacy and brain function. However, the molecular mechanism underlying the surface transport of NMDARs is largely unknown. Here we identified myosin Va (MyoVa) as the specific motor protein that traffics NMDARs in hippocampal neurons. We found that MyoVa associates with NMDARs through its cargo binding domain. This association was increased during NMDAR surface transport. Knockdown of MyoVa suppressed NMDAR transport. We further demonstrated that Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) regulates NMDAR transport through its direct interaction with MyoVa. Furthermore, MyoVa employed Rab11 family-interacting protein 3 (Rab11/FIP3) as the adaptor proteins to couple themselves with NMDARs during their transport. Accordingly, the knockdown of FIP3 impairs hippocampal memory. Together, we conclude that in hippocampal neurons, MyoVa conducts active transport of NMDARs in a CaMKII-dependent manner.

Elevated [CO2] reduces CH4 emissions from rice paddies under in situ straw incorporation - Ting Bao; Ling Wang; Yuanfa Huang; Huixin Li; Lanying Qiu; Jiujie Liu; Linlin Shi; Yunlong Liu; Haoyu Qian; Yanfeng Ding; Yu Jiang (Agriculture, Ecosystems & Environment, 2024)

Dissipation behavior and risk assessment of imidacloprid and its metabolites in apple from field to products - Fajun Tian; Junfeng Lu; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie (Chemosphere, 2024)

Low energy-consumption oriented membrane fouling control strategy in anaerobic fluidized membrane bioreactor - Lu Liu; Ze Guo; Yihe Wang; Linlin Yin; Wei Zuo; Yu Tian; Jun Zhang (Chemosphere, 2024)

From tissue lesions to neurotoxicity: The devastating effects of small-sized nanoplastics on red drum Sciaenops ocellatus - Zhicheng Sun; Xin Peng; Linlin Zhao; Yi Yang; Yugui Zhu; Linlong Wang; Bin Kang (Science of The Total Environment, 2024)

An engineered DNA aptamer-based PROTAC for precise therapy of p53-R175H hotspot mutant-driven cancer - Lingping Kong; Fanlu Meng; Ping Zhou; Ruixin Ge; Xiaoshan Geng; Zhihao Yang; Guo Li; Linlin Zhang; Jing Wang; Jinfeng Ma; Cheng Dong; Jun Zhou; et al. (Science Bulletin, 2024)

Integrative proteomic-metabolomics strategy reveals the regulators and mechanism of enhancing cyclic lipopeptides in the high-cell-density fermentation of Bacillus subtilis S1702 - Bo Zhang; Linlin Xu; Hui Yang; Zhengjun Pang; Wenshuo Zhang; Fenghuan Wang; Huilin Liu; Junfeng Fan; Bolin Zhang (Process Safety and Environmental Protection, 2024)

MdWRKY45 contributes to resistance against Botryosphaeria dothidea in apple - Xue Wang; Xiangyue Kong; Linlin Qiu; Wei Kuang; Jun Leng; Yongzhang Wang; Qiang Zhao (Postharvest Biology and Technology, 2024)

Provenance signature and tectono–sedimentary setting of the Permian Shihezi formation (Ordos basin, China): Insights from geochemistry and detrital zircon U–Pb dating - Shuyue Zhu; Lei Liu; Linlin Wang; Zhiwei Wang; Jianling Hu; Jingqi Zhang; Chenggong Zhang; Junxing Zhao; Hongde Chen (Marine and Petroleum Geology, 2024)

Mitigation measures of storm surge inundation at an onshore aquaculture farm - Linlin Wang; Shikun Hu; Jing-Cheng Han; Peng Hu; Xuan Yu (Journal of Hydrology, 2024)

Chromium levels in placental tissue and neural tube defects: Association and mechanistic study - Yongyan Chen; Yingnan Guo; Chengrong Wang; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Environmental Pollution, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

Mechanistic approach of tannery wastewater and sulfadiazine mutual toxicity in wheat (Triticum aestivum L.) and mitigation through exogenous application of gallic acid. - Muhammad Nafees; Muhammad Azhar Ali; Linlin Qiu; Ying Yin; Meiling Xu; Guobing Wang; Shafaqat Ali; Hongyan Guo (Chemosphere, 2024)

Evidence and causes of recent decreases in nitrogen deposition in temperate forests in Northeast China - Yingying Wang; Feifei Zhu; Jin Li; Geshere Abdisa Gurmesa; Shaonan Huang; Xiaoming Fang; Dongwei Liu; Abubakari Said Mgelwa; Wenchao Wang; Kai Huang; Yihang Duan; Linlin Song; et al. (Science of The Total Environment, 2024)

Experimental and theoretical studies on effective synergistic low-temperature removal of NO and typical volatile organic compounds (VOCs) from flue gas based on Cu@VWTi catalyst - Siyuan Lei; Lele Wang; Linlin Xu; Ben Wang; Lushi Sun (Journal of Cleaner Production, 2024)

Recent progress in the antidegradation strategies of two-dimensional transition metal carbides (MXenes) - Ying Li; Yudi Li; Linlin Zhao; Siyu Chen; Siren Guo; Xulin Yang; Pan Wang; Kui Li; Fan Lei; Wei Feng; Zihao Mou; Hanjun Wei (Journal of Environmental Chemical Engineering, 2024)

Copper-doped ZIF-67/wood aerogel for effective peroxymonosulfate activation - Linlin Zhao; Wanning Xiong; Ziheng Wang; Jie Ouyang; Mengyao Li; Gonggang Liu; Yongfeng Luo (Journal of Environmental Chemical Engineering, 2024)

Antimicrobial photodynamic inactivation pH-responsive films based on gelatin/chitosan incorporated with aloe-emodin - Linlin Li; Li Xia; Feng Xiao; Yewen Xiao; Wei Ji; Baocai Xu; Hualin Wang (Food Chemistry, 2024)

A novel metal–organic framework based electrochemical immunosensor for the rapid detection of Salmonella typhimurium detection in milk - Ke Zhan; Linlin Chen; Shanshan Li; Qiuying Yu; Zheng Zhao; Junwei Li; Yunrui Xing; Hongtao Ren; Na Wang; Gaiping Zhang (Food Chemistry, 2024)

Determination of chloropropanol esters and glycidyl esters in instant noodles based on solid-phase microextraction with chitosan-β-cyclodextrin coated fiber - Linlin Bian; Xue Ge; Senwei Feng; Guangxuan Chen; Kefeng Li; Xu Wang (Food Chemistry, 2024)

A randomised double-blind placebo-controlled trial of a probiotic combination for manipulating the gut microbiota and managing metabolic syndrome - Rui Xiao; Ying Chen; Xiaofeng Zhu; Linlin Wang; Peijun Tian; Xing Jin; Ming Liang; Zehua Chen; Ting Zhang; Long Qian; Qun Wang; Jianxin Zhao; et al. (Food Bioscience, 2024)

Imbalances in the gut microbiota and metabolome are associated with functional constipation in pregnancy - Ruili Pan; Ying Chen; Guopeng Lin; Haojue Wang; Xiaopeng Xu; Linlin Wang; Peijun Tian; Jianxin Zhao; Wei Chen; Gang Wang (Food Bioscience, 2024)

Cellulose-based magnetic nanomaterials immobilized esterases as a reusable and effective detoxification agent for patulin in apple juice - Xiaoshuang Liu; Linlin Gao; Shiqi Li; Leran Wang; Rui Cai; Tianli Yue; Yahong Yuan; Xubo Zhao; Zhouli Wang (Food Control, 2024)

Energetics of eddy-mean flow interactions in the western tropical Pacific Ocean - Yuchao Hui; Linlin Zhang; Xiaomei Yan; Mengmeng Li; Fan Wang; Dunxin Hu (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Activatable theranostic nanoprobes for Fluorescence/MR imaging and microenvironment remodeling of early cartilage degeneration - Xiuli Zhang; Manman Xie; Linlin Li; Wenlou Liu; Peng Xu; Zuohui Zhang; Yue Dai; Dongxu Wang; Li Lu; Kai Xu; Jingjing Li (Chemical Engineering Journal, 2024)

An end-capping strategy for shape memory phthalonitrile resins via annealing enables conductivity and wave-absorption - Rongxiang Hu; Fenghua Zhang; Lan Luo; Linlin Wang; Yanju Liu; Jinsong Leng (Chemical Engineering Journal, 2024)

Island-based GNSS-IR network for tsunami detecting and warning - Linlin Li; Qiang Qiu; Mai Ye; Dongju Peng; Ya-Ju Hsu; Peitao Wang; Huabin Shi; Kristine M. Larson; Peizhen Zhang (Coastal Engineering, 2024)

Response of photosynthetic characteristics and antioxidant system in the leaves of safflower to NaCl and NaHCO3 - Linlin Song; Yongliang Yu; Hongzhi Chen; Yuwei Feng; Shuo Chen; Huihui Zhang; Haijia Zhou; Li Meng; Yue Wang (Plant Cell Reports, 2024)

Effects of Nitrogen Fertilizer Reduction Combined with Foliar Fertilizer Application on the Physiological Characteristics and Yield of High-Quality Japonica Rice - Yunsheng Song; Minghui Dong; Fei Chen; Yajie Hu; Yongliang Zhu; Junrong Gu; Peifeng Chen; Yulin Xie; Caiyong Yuan; Zhongying Qiao; Yajie Yu; Penghui Cao; et al. (International Journal of Plant Production, 2024)

Measurement of Elastic Bi-modulus of Rock-type Materials: Insight from comparative and parallel tests - Yan Zhang; Hao Zheng; Huiling He; Peng Sha; Linlin Wang; Shengwen Qi; Xiaolin Huang; Jianhong Ye (Bulletin of Engineering Geology and the Environment, 2024)

Characterization of Nutrients, Heavy Metals, Petroleum and Their Impact on Phytoplankton in Laizhou Bay: Implications for Environmental Management and Monitoring - Kai Wang; Linlin Zhao; Yugui Zhu; Liqiang Yang; Yunfeng Wang; Xuguang Hong (Journal of Ocean University of China, 2024)

Exploring Seasonal Variations in Fish Communities: A Study of the Yellow River Estuary and Its Adjacent Waters Using eDNA and Trawl Surveys - Xiaoyang Wang; Fan Li; Fei Shao; Hongjun Song; Na Song; Xiaomin Zhang; Linlin Zhao (Fishes, 2024)
The Yellow River Estuary and its adjacent waters serve as crucial spawning, foraging, and nursery areas for marine organisms, possessing abundant biological resources. Monitoring fish communities provides a baseline for implementing the sustainable utilization of marine resources. In this study, data were collected from 15 spring surface and bottom sites and 17 summer surface sites using eDNA and trawl surveys. The results showed that 37, 40, and 35 fish species were detected using eDNA in the spring (surface and bottom) and summer (surface), respectively, with 38 fish species caught during summer trawling. The dominant species mainly belonged to Engraulidae of Clupeiformes in the spring and Gobiidae of Perciformes in the summer, characterized by smaller-sized, short-lived, and pelagic fish species. The summer surface communities exhibited higher diversity than the spring surface and bottom communities. NMDS analysis revealed a degree of seasonal differences in fish communities and that there may be a lack of vertical stratification in the spring communities. The pH and DO were identified as the key environmental factors affecting the fish community. Additionally, the combination of eDNA and trawl surveys was regarded as a superior survey method. Our study provides valuable information for understanding seasonal fish communities in the Yellow River Estuary and its adjacent waters, contributing to fishery resource management and conservation in the region.

EB-Net: an efficient balanced network for accuracy and speed of remote sensing detection - Dehua Zhang; Dechen Wang; Changcheng Yu; Xinyuan Hao; Linlin Liang (International Journal of Remote Sensing, 2024)

Airborne ARGs/MGEs from two sewage types during the COVID-21: Population, microbe interactions, cytotoxicity, formation mechanism, and dispersion - Yanjie Wang; Song Zhang; Lin Li; Qiao Zhang; Liying Yang; Kai Yang; Yang Liu; Haoran Zhu; Bisheng Lai; Jian Wu; Linlin Hua (Water Research, 2024)

Spatiotemporal distribution, interactions and toxic effect of microorganisms and ARGs/MGEs from the bioreaction tank in hospital sewage treatment facility - Yanjie Wang; Song Zhang; Liying Yang; Kai Yang; Yang Liu; Haoran Zhu; Bisheng Lai; Lin Li; Linlin Hua (Science of The Total Environment, 2024)

Towards robust classification of multi-view remote sensing images with partial data availability - Maofan Zhao; Qingyan Meng; Lifeng Wang; Linlin Zhang; Xinli Hu; Wenxu Shi (Remote Sensing of Environment, 2024)

Change characteristics, bacteria host, and spread risks of bioaerosol ARGs/MGEs from different stages in sewage and sludge treatment process - Yanjie Wang; Kai Yang; Lin Li; Liying Yang; Song Zhang; Fangfang Yu; Linlin Hua (Journal of Hazardous Materials, 2024)

Prenatal exposure to poly/perfluoroalkyl substances and risk for congenital heart disease in offspring - Sainan Li; Chengrong Wang; Chen Yang; Yongyan Chen; Qianhui Cheng; Jufen Liu; Yali Zhang; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Journal of Hazardous Materials, 2024)

Preparation of core-shell structure Ag@TiO2 plasma photocatalysts and reduction of Cr(VI): Size dependent and LSPR effect - Jiwen Li; Yaqian Duan; Linlin Wang; Jingjun Ma (Environmental Research, 2024)

Review on post-combustion CO2 capture by amine blended solvents and aqueous ammonia - Jiaxing Du; Wu Yang; Linlin Xu; Lei Bei; Siyuan Lei; Wei Li; Haitao Liu; Ben Wang; Lushi Sun (Chemical Engineering Journal, 2024)

Bioaerosols in deodorization covers of wastewater treatment plants: Emission characteristics and health risks - Shan Zhao; Yang Liu; Jiang Chang; Jiawei Wang; Hao Peng; Baocong Cui; Jin Bai; Yanjie Wang; Linlin Hua (Chemosphere, 2024)

Dual-objective control of braced steel frame using asynchronized parallel two-stage yielding BRB - Cantian Yang; Linlin Xie; Qiang Liu; Aiqun Li; Qianmin Liu; Xinyu Wang (Soil Dynamics and Earthquake Engineering, 2024)

Microdrop-confined synthesis and regulation of porous hollow Ir-based catalysts for the mass transfer-enhanced electrolysis of pure water - Li Liu; Ting Huang; Xiaoliang Yang; Shoujie Liu; Shunsheng Wang; Linlin Xiang; Gongming Wang; Long Kuai (Science Bulletin, 2024)

Mapping Chinese plastic flows from 2001 to 2040 based on dynamic probabilistic material flow analysis and scenario projection - Linlin Xia; Yuhan Ke; Zihao Wu; Jianbing Wang; Ruwei Wang; Yanpeng Cai; Zhifeng Yang (Resources, Conservation and Recycling, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Quantifying the environmental synergistic effect of cooling-air purification-carbon sequestration from urban forest in China - Rundong Feng; Shenghe Liu; Fuyuan Wang; Kaiyong Wang; Ping Gao; Linlin Xu (Journal of Cleaner Production, 2024)

Machine learning reveals the selection pressure exerted by nonantibiotic pharmaceuticals at environmentally relevant concentrations on antibiotic resistance genotypes - Shaojing Sun; Yan Sun; Jialu Geng; Linlin Geng; Fan Meng; Qing Wang; Hong Qi (Journal of Environmental Management, 2024)

Influence of meteorological factors on open biomass burning at a background site in Northeast China - Yulong Wang; Linlin Liang; Wanyun Xu; Chang Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Xiaobin Xu; Dajiang Yu; Peng Wang; Qingli Song; Jiumeng Liu; et al. (Journal of Environmental Sciences, 2024)

Melatonin alleviates di-butyl phthalate (DBP)-induced ferroptosis of mouse leydig cells via inhibiting Sp2/VDAC2 signals - Si Yang; Meiwei Chen; Jiahui Meng; Chaoju Hao; Linlin Xu; Jinglei Wang; Jiaxiang Chen (Environmental Research, 2024)

Bisphenol F exposure induces depression-like changes: Roles of the kynurenine metabolic pathway along the “liver-brain” axis - Zheng Yu; Yuxin Lin; Linlin Wu; Luyao Wang; Yichun Fan; Liuting Xu; Linwei Zhang; Weilan Wu; Jingxian Tao; Fei Huan; Wenwei Liu; Jun Wang; et al. (Environmental Pollution, 2024)

Mild low-temperature photothermal therapy demonstrated a distinctive 'hot spring' effect in the multichannel regulation of atherosclerosis instead of inducing foam cell apoptosis - Jie Sheng; Ziyue Zu; Jianchen Qi; Yugang Zhang; Haoguang Wu; Zhicheng Wang; Yu Miao; Tao Zheng; Sheng Wang; Linlin Zhang; Guangming Lu; Longjiang Zhang (Chemical Engineering Journal, 2024)

Automatic identification of factor profiles can be achieved by improved machine learning model - Bo Xu; Junbo Huang; Yi Ge; Chun Zhang; Han Xu; Feng Wang; Huan Zhao; Linlin Zhang; Jinxing Liu; Yinchang Feng; Guoliang Shi (Atmospheric Environment, 2024)

In Utero Exposure to Lead is Associated with Neural Tube Defects via Disturbing the Expression of Endocannabinoid Retrograde Signaling-Related Genes - Tian Tian; Huijun Dong; Shengju Yin; Mengyuan Liu; Yongyan Chen; Kuanhui Xiang; Linlin Wang; Jie Qiao; Aiguo Ren (Exposure and Health, 2024)

Clinical epidemiology of adenovirus pneumonia among Chinese hospitalized children - Jiao Tian; Xinyu Wang; Qi Li; Linlin Zhang; Junhong Ai; Guoshuang Feng; Yueping Zeng; Ran Wang; Zhengde Xie (Archives of Microbiology, 2024)

Medium optimization and dust suppression performance analysis of microbial-based dust suppressant compound by response surface curve method - Xiangming Hu; Zhiyuan Yang; Yanyun Zhao; Yue Dong; Chengcheng Wang; Linlin Zhang; Yiyun Yu; Kai Wu; Liyan Ren (Environmental Science and Pollution Research, 2024)

Estimating the methane flux of the Dajiuhu subalpine peatland using machine learning algorithms and the maximal information coefficient technique - Xue Li; Jiwen Ge; Ziwei Liu; Shiyu Yang; Linlin Wang; Ye Liu (Science of The Total Environment, 2024)

Influence paradigms of soil moisture on land surface energy partitioning under different climatic conditions - Xiao Chen; Zhihua Pan; Binxiang Huang; Ju Liang; Jialin Wang; Ziyuan Zhang; Kang Jiang; Na Huang; Guolin Han; Buju Long; Zhenzhen Zhang; Jingyu Men; et al. (Science of The Total Environment, 2024)

Subsurface eddies east of the Philippines: Geographic characteristics, vertical structures, volume and thermohaline transport - Linlin Zhang; Weiqi Song; Yuchao Hui; Zhenxiao Wang; Dunxin Hu (Progress in Oceanography, 2024)

Tissue-specific distribution and bioaccumulation of perfluoroalkyl acids, isomers, alternatives, and precursors in citrus trees of contaminated fields: Implication for risk assessment - Zhaoyang Liu; Shun Liu; Feng Xiao; Andrew J. Sweetman; Qianqian Cui; Hao Guo; Jiayi Xu; Ziyao Luo; Mingxia Wang; Linlin Zhong; Jay Gan; Wenfeng Tan (Journal of Hazardous Materials, 2024)

Deterioration of single-use biodegradable plastics in high-humidity air and freshwaters over one year: Significant disparities in surface physicochemical characteristics and degradation rates - Lingling Hu; Linlin He; Li Cai; Yumeng Wang; Gang Wu; Daoyong Zhang; Xiangliang Pan; Yu-Zhong Wang (Journal of Hazardous Materials, 2024)

Quantitative distribution and quantized ecological threat of microplastics in farmland: Shanghai as an example - Zhengwen Li; Zhaofeng Song; Linlin Qiu; Yan Cao; Hairong Gu; Zhenqi Wang; Xiang Liu; Xiaoyong Qian (Journal of Hazardous Materials, 2024)

Influence of polysaccharide-based co-encapsulants on efficiency, stability, and release of vitamins B12 and D3 in multilayered microcapsules - Linlin He; Shihong Hu; Gang Zhang; Xiao Wang; Yanna Zhao; Qingpeng Wang; Min Liu; Zhengping Wang; Prakash Sangeeta; Zhuang Ding (Journal of Food Engineering, 2024)

Kinetics and debromination studies on the pyrolysis of waste printed circuit boards with the addition of copper and copper oxides - Tao Chen; Chuan Ma; Ben Wang; Linlin Xu; Wu Yang; Lushi Sun (Journal of Cleaner Production, 2024)

Microbiological hazards in infant and toddler food in China: A comprehensive study between 2004 and 2022 - Lin Teng; Linlin Huang; Haiyang Zhou; Baikui Wang; Min Yue; Yan Li (Food Research International, 2024)

Preparation and characterization of zein-tannic acid nanoparticles/chitosan composite films and application in the preservation of sugar oranges - Shuangjian Li; Xiaoli Liu; Xiaoqian Zhang; Linlin Fan; Fan Wang; Jianzhong Zhou; Hongzhi Zhang (Food Chemistry, 2024)

UV-B application during the aeration process improves the aroma characteristics of oolong tea - Xiaohui Wang; Jingjie Cao; Xin Cheng; Xuyang Liu; Wenfeng Zhu; Yan Li; Xiaochun Wan; Shengkeng Chen; Linlin Liu (Food Chemistry, 2024)

Impact analysis of hydraulic residence time and dissolved oxygen on performance efficiency and microbial community in N, N-dimethylformamide wastewater treated by an AnSBR-ASBR - Yuchen Wang; Linlin Cao; Yiying Lu; Junjie Liao; Yuxiang Lu; Chengyuan Su; Shu Gao (Environmental Pollution, 2024)

Photocatalytic chitosan-based bactericidal films incorporated with WO3/AgBr/Ag and activated carbon for ethylene removal and application to banana preservation - Feng Xiao; Yewen Xiao; Wei Ji; Linlin Li; Yimeng Zhang; Minmin Chen; Hualin Wang (Carbohydrate Polymers, 2024)

Observational insights into the environmental effect for secondary inorganic aerosol formation in the Northeast China: Influence of biomass burning - Yulong Wang; Linlin Liang; Wanyun Xu; Chang Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Xiaobin Xu; Dajiang Yu; Peng Wang; Qingli Song; Jiumeng Liu; et al. (Atmospheric Research, 2024)

The mediation effect of asprosin on the association between ambient air pollution and diabetes mellitus in the elderly population in Taiyuan, China - Lulu Song; Yuhui Gao; Jiayu Tian; Nannan Liu; Halimaimaiti Nasier; Caihong Wang; Huiqiu Zhen; Linlin Guan; Zeyu Niu; Dongxing Shi; Hongmei Zhang; Lifang Zhao; et al. (Environmental Science and Pollution Research, 2024)

Analysis of Flow Instability and Mechanical Energy Loss of Fluid Field in Fluid Momentum Wheel - Kedong Zhang; Wenhua Wang; Yihua Liu; Linlin Wang; Yazhen Du; Hongxia Li; Yi Huang (Journal of Marine Science and Engineering, 2024)
A new type of anti-rolling device denoted as a fluid momentum wheel (FMW) is proposed to address the limitations of traditional gyrostabilizers in reducing the roll responses of floating platforms in waves. The proposed device is based on the same gyroscope theorem, which differs from a rigid gyrostabilizer in that the internal fluid generates secondary flow in the cross-section under the combined effects of inertial centrifugal force and a radial pressure gradient, and the streamwise velocity exhibits a non-uniform distribution. These instability phenomena may cause mechanical energy loss in the flow field, which is critical for selecting the driving device and the anti-roll control performance of offshore platforms. In the study, different turbulence models are compared with the results of a Direct Numerical Simulation (DNS) and experiments to ensure the accuracy of the numerical method, and the spatiotemporal distribution characteristics of the flow field in FMW are analyzed. Therein, the SST k-ω model accurately verifies the flow instability phenomenon of the FMW observed in the Particle Image Velocimetry (PIV) experiment. Next, this paper proposes corresponding evaluation parameters to assess the impact of typical parameters on the flow field instability. The results show that the flow instability increases with an increase in the typical parameters of FMWs (such as the pipe diameter, curvature radius, and velocity). Furthermore, the paper discusses the relationship between dimensionless mechanical factors (Reynolds number, curvature ratio) and the spatiotemporal instability of the flow field, revealing the essential effects of the curvature ratio and Reynolds number on the loss coefficient.

The miR-34b/MEK/ERK pathway is regulated by NR5A1 and promotes differentiation in primary bovine Sertoli cells - Qibing Tao; Linlin Zhang; Yun Zhang; Mingming Liu; Jie Wang; Qian Zhang; Jiancheng Wu; Aihua Wang; Yaping Jin; Keqiong Tang (Theriogenology, 2024)

Construction of a methodology framework to characterize dynamic full-sector land-use carbon emissions embodied in trade - Yuhan Ke; Linlin Xia; Ruwei Wang; Sai Liang; Zhifeng Yang (Science of The Total Environment, 2024)

A novel method of identifying estuary high-nutrient zones for water quality management - Linlin Wang; Xiaoyu Lei; Guo Yuehua; Yang Zhou; Jing-Cheng Han; Yuefei Huang; Bing Li; Xian-zhong Mao; Zhaozhao Tang (Science of The Total Environment, 2024)

Spatio-temporal variability of fishing habitat suitability to tuna purse seine fleet in the Western and Central Pacific Ocean - Shenglong Yang; Lijun Wang; Yingjie Fei; Shengmao Zhang; Linlin Yu; Heng Zhang; Fei Wang; Yumei Wu; Zuli Wu; Wei Wang; Jiayu Shi; Keji Jiang; et al. (Regional Studies in Marine Science, 2024)

The pollution of airborne ARGs and microorganisms during wastewater treatment process and their UV mediated removal mechanism - Yanjie Wang; Hao Chen; Liying Yang; Song Zhang; Kai Yang; Linlin Hua (Journal of Water Process Engineering, 2024)

A comprehensive study on the co-removal of Cr (VI) and ciprofloxacin via microbial-photocatalytic coupling: Mechanistic insights and performance evaluation - Yilin Dong; Qiuwen Wang; Jinyu Zhu; Linlin Liang; Dongyu Xu; Xueyue Mi; Zhijun Ren; Pengfei Wang (Journal of Environmental Management, 2024)

Effects of chitosan and its oligosaccharide on gut microbiota and metabolites disturbed by excessive protein consumption in vivo and in vitro - Linlin Wang; Lilong Wang; Nan Wang; Chen Song; Chengrong Wen; Shuang Song (Food Bioscience, 2024)

Cu-hierarchical porous carbon anodes derived from metal-organic frameworks for long-lasting and high-energy lithium storage - Bing Zhu; Manshu Zhang; Yangai Liu; Yicen Liu; Xi Zhang; Yahui Song; Linlin Wang; Ruiyu Mi (Chemical Engineering Journal, 2024)

Selective fluoride removal from groundwater using CNT-CeO2 electrodes in capacitive deionization (CDI) - Xun Liu; Danyal Rehman; Yufei Shu; Bei Liu; Li Wang; Li Li; Mengxia Wang; Kunkun Wang; Qi Han; Linlin Zang; John H. Lienhard; Zhongying Wang (Chemical Engineering Journal, 2024)

Colorimetric microneedle sensor using deep learning algorithm for meat freshness monitoring - Jie Wang; Linlin Xia; Han Liu; Chong Zhao; Siyu Ming; Jingyi Wu (Chemical Engineering Journal, 2024)

Vertical distribution of intraseasonal variation signals in the Kuroshio Current source area during 2018–2020 - Haobo Gong; Fujun Wang; Feng Liu; Linlin Zhang; Dunxin Hu (Frontiers in Marine Science, 2024)
In the Kuroshio Current (KC) source area, intraseasonal variation (ISV) plays a significant role in dynamic oceanic processes. This study used data collected from three moorings (122.7°E, 123°E, 123.3°E) along 18°N from January 2018 to May 2020 to investigate the ISVs of meridional velocities. Notably, our findings reveal that the ISV above 200 m has a period of approximately 56 days and its intensity exhibits a gradual increase toward the west. For the 500–800 m depth interval, the ISV period is 73 days at 122.7°E/18°N and 60 days at 123.3°E/18°N. This discrepancy indicates that the ISVs have different vertical structures and frequencies at 122.7°E and 123.3°E along 18°N. In particular, at 122.7°E/18°N, the distinctiveness of two different periods of ISVs in surface and subsurface layers was more pronounced in 2018 than in 2019. The analyses of eddy kinetic energy distribution and eddy tracking indicate a connection between ISV in stratification and locally generated mesoscale eddies in the KC source area. Specifically, the stronger eddy activity in 2018, in contrast with that in 2019, correlates with a more pronounced ISV. Energy analysis demonstrates a distinct positivity in the baroclinic conversion rate (BC) in the surface layer (upper 200 m) of the KC source region, surpassing the absolute value of the barotropic conversion rate (BT). This finding indicates a notable shift of energy from eddy available potential energy to eddy kinetic energy, strengthening the high-frequency ISV signals in this area. In the subsurface layer, a strong negative BT is observed west of 122.8°E, with its absolute value exceeding the BC. This finding indicates that the energy is converted from eddy kinetic energy into mean kinetic energy, resulting in the appearance of the Luzon Undercurrent (LUC) at mooring station 122.7°E/18°N, characterized by a low frequency of ISV. Contrastingly, a positive BT plays a dominant role at 123.3°E/18°N, leading to the disappearance of the LUC amid an apparent presence of high-frequency ISV.

Comprehensive analyses of annexins in naked carp (Gymnocypris przewalskii) unveil their roles in saline-alkaline stress - Linlin A; Yujing Zhang; Baoke Xu; Haichen Zhang; Yixin Li; Le Wang; Jian Liang; Weiguo Zhou; Zhaohui Feng; Hong Zhang (Aquaculture, 2024)

Comparative transcriptome analysis of hybrid Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) and Epinephelus fuscoguttatus under temperature stress - Pengfei Duan; Yongsheng Tian; Zhentong Li; Shuai Chen; Linlin Li; Xinyi Wang; Linna Wang; Yang Liu; Jieming Zhai; Wensheng Li; Qingbin Wang; Wenhui Ma; et al. (Aquaculture, 2024)

Duck Tembusu virus infection activates the MKK3/6-p38 MAPK signaling pathway to promote virus replication - Yuting Cheng; Linlin Jiao; Jinying Chen; Peiyao Chen; Fang Zhou; Jilin Zhang; Mixue Wang; Qingguo Wu; Shinuo Cao; Huipeng Lu; Zhi Wu; Anping Wang; et al. (Veterinary Microbiology, 2024)

Seismic behavior of embedded rubberized concrete-filled corrugated steel tube column-to-foundation connections: Experimental, numerical modelling, and design - Mingyang Feng; Baodong Liu; Linlin Zhang; Yaoyao Wang; Haibo Sun (Soil Dynamics and Earthquake Engineering, 2024)

GhFB15 is an F-box protein that modulates the response to salinity by regulating flavonoid biosynthesis - Zhao Geng; Haikuan Dou; Jianguang Liu; Guiyuan Zhao; Zetong An; Linlin Liu; Ning Zhao; Hanshuang Zhang; Yongqiang Wang (Plant Science, 2024)

Dynamic behaviors of cavitation bubbles near biomimetic surfaces: A numerical study - Hongbo Shi; Hang Zhang; Linlin Geng; Sen Qu; Xikun Wang; Petr A. Nikrityuk (Ocean Engineering, 2024)

How the subsurface wastewater infiltration systems with iron‑carbon micro-electrolytic substrate achieve high pollutants removal: A metabolomic view - Yinghua Li; Linlin Peng; Yiyan Wang; Yue Zhang; Fei Su; Jie Qian (Journal of Water Process Engineering, 2024)

Heat stress reduces brown adipose tissue activity by exacerbating mitochondrial damage in type 2 diabetic mice - Penghua Lai; Linlin Zhang; Yan Qiu; Jie Ren; Xue Sun; Ting Zhang; Liuyi Wang; Sijie Cheng; Sijia Liu; Hongli Zhuang; Daiwei Lu; Shaoliang Zhang; et al. (Journal of Thermal Biology, 2024)

Identification of optimal organic fertilizer subsidy policies under dual uncertainty via a self-calibrated fuzzy-boundary interval programming method - Shuping Wang; Pan Yang; Qian Tan; Linlin Yao (Journal of Cleaner Production, 2024)

China's economic restructuring reduced emissions of polycyclic aromatic hydrocarbons (PAHs) in the post-global financial crisis era - Linlin Xia; Jianbing Wang; Ruwei Wang; Sai Liang; Zhifeng Yang (Journal of Cleaner Production, 2024)

Patterns and drivers of atmospheric inorganic nitrogen deposition in Northeast Asia - Abubakari Said Mgelwa; Feifei Zhu; Dan Huang; Linlin Song; Yingying Wang; Geshere Abdisa Gurmesa; Ang Wang; Miao Liu; Shaonan Huang; Qingyan Qiu; Hiroyuki Sase; Weixing Zhu; et al. (Journal of Environmental Management, 2024)

Sulfur-Doped porous carbon Adsorbent: A promising solution for effective and selective CO2 capture - Jiali Bai; Jiawei Shao; Qiyun Yu; Muslum Demir; Bilge Nazli Altay; Turgunov Muhammad Ali; Yongfu Jiang; Linlin Wang; Xin Hu (Chemical Engineering Journal, 2024)

Angiotensin II type 2 receptor agonist attenuates LPS-induced acute lung injury through modulating THP-1-derived macrophage reprogramming - Liangzhi Chen; Ping Gong; Yue Su; Linlin Meng; Muyun Wang; Wei Gao; Qinghua Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Grey matter structural alterations in anxiety disorders: a voxel-based meta-analysis - Han Liu; Zeqi Hao; Shasha Qiu; Qianqian Wang; Linlin Zhan; Lina Huang; Youbin Shao; Qing Wang; Chang Su; Yikang Cao; Jiawei Sun; Chunjie Wang; et al. (Brain Imaging and Behavior, 2023)

Dissipation, residues, and evaluation of processing factor for spirotetramat and its formed metabolites during kiwifruit growing, storing, and processing - Fajun Tian; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie (Environmental Science and Pollution Research, 2023)

Full-scale experimental study on seismic performance of repaired precast shear walls - Xinyu Wang; Linlin Xie; Qianmin Liu (Soil Dynamics and Earthquake Engineering, 2023)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

S doped g-C3N5 for highly efficient photocatalytic H2O2 production and PPCPs degradation via directional transfer of electrons - Wenjuan Wang; Nan Zhou; Yakun Li; Zhengqiaoruo Zhu; Xiguo Chen; Linlin Zhang (Journal of Environmental Chemical Engineering, 2023)

A novel lateral epitaxial Bi2O3@BiOCl heterostructure for photocatalytic antibiotic degradation in an internal circulation fluidized bed reactor - Yilin Dong; Shaoxuan Pang; Fuqiang Zhang; Dongyu Xu; Qiuwen Wang; Kang Wang; Lijun Zhang; Linlin Liang; Zhijun Ren; Pengfei Wang (Chemical Engineering Journal, 2023)

State-of-the-art analysis of the fuel desulphurization processes: Perspective of CO2 utilization in coal biodesulphurization - Muhammad Ahmad; Maryam Yousaf; Jing-Cheng Han; Shafeeq Ur Rahman; Hafiz Muhammad Adeel Sharif; Linlin Wang; Zhaozhao Tang; Yang Zhou; Yuefei Huang (Chemical Engineering Journal, 2023)

Multidimensional cross-linked network strategies for Rapidly, Reconfigurable, refoldable shape memory polymer - Lan Luo; Fenghua Zhang; Linlin Wang; Yanju Liu; Jinsong Leng (Chemical Engineering Journal, 2023)

Stable precipitation isotope records of cold wave events in Eurasia - Xinrui Lin; Guofeng Zhu; Dongdong Qiu; Linlin Ye; Yuwei Liu; Longhu Chen; Jiawei Liu; Siyu Lu; Lei Wang; Kailiang Zhao; Wenhao Zhang; Rui Li; et al. (Atmospheric Research, 2023)

Phase Transition in Geomaterials Under Unsaturated Conditions - Jiuhui Cheng; Xuanzhe Xia; Zhiqiang Liu; Linlin Wang (Rock Mechanics and Rock Engineering, 2023)

Centennial-scale monsoon collapses during Marine Isotope Stage (MIS)7e detected in a northern Chinese stalagmite record - Wuhui Duan; Ming Tan; Lisheng Wang; Xuefeng Wang; Zhibang Ma; Linlin Cui; Zhengyi Xiao (Science China Earth Sciences, 2023)

Hippocampal subfield volumes in mild cognitive impairment and alzheimer’s disease: a systematic review and meta-analysis - Jinhuan Zhang; Linlin Xie; Changjiang Cheng; Yongfeng Liu; Xiaodong Zhang; Haoyu Wang; Jingting Hu; Haibo Yu; Jinping Xu (Brain Imaging and Behavior, 2023)

Green bond financing, environmental regulation, and long-term value orientation: evidence from Chinese-listed companies - Hailin Wang; Linlin Duan; Hao Zeng (Environmental Science and Pollution Research, 2023)

PM2.5-bound metals and blood metals are associated with pulmonary function and Th17/Treg imbalance: A panel study of asthmatic adults - Nannan Liu; Dan Wang; Jiayu Tian; Xin Wang; Hao Shi; Caihong Wang; Yi Jiang; Min Pang; Xiaozhou Fan; Jing Zhao; Liangpo Liu; Hongyan Wu; et al. (Chemosphere, 2023)

Investigating the influence of bentonite colloids on strontium sorption in granite under various hydrogeochemical conditions - Fangfei Cai; Funing Ma; Xiaoying Zhang; Paul Reimus; Linlin Qi; Yu Wang; Di Lu; Hung Vo Thanh; Zhenxue Dai (Science of The Total Environment, 2023)

Strategies for the coordinated control of particulate matter and carbon dioxide under multiple combined pollution conditions - Zhenyu Wang; Huan Zhao; Han Xu; Jie Li; Tong Ma; Linlin Zhang; Yinchang Feng; Guoliang Shi (Science of The Total Environment, 2023)

Associations among bisphenol A, its analogs, and chlorinated derivatives in placenta and risk for neural tube defects: A case-control study - Haiyan Zhu; Qianhui Cheng; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Science of The Total Environment, 2023)

Hydrophobic electrospun membrane of peppermint oil loaded zein with coating of methyltriethoxysilane for active packaging - Li Xia; Linlin Li; Yewen Xiao; Feng Xiao; Wei Ji; Min Pang; Hualin Wang (Food Hydrocolloids, 2023)

Depth investigation of the regulation mechanism of SiO2 on the denitrification performance and sulfur resistance of MnCe/Ti SCR catalyst - Mengxia Qing; Linlin Zhang; Liang Liu; Yaxin Chen; Yunda Su; Sheng Su; Song Hu; Yi Wang; Jun Xiang (Chemical Engineering Journal, 2023)

The effect of commercial β-glucosidase and its immobilization on quality of red wine production - Jun Wang; Linlin Ma; Hengfang Gao; Xia Li; Zhigang Dong (Biocatalysis and Agricultural Biotechnology, 2023)

A lipidomic approach to bisphenol F-induced non-alcoholic fatty liver disease-like changes: altered lipid components in a murine model - Xinjing Wang; Linlin Wu; Jingxian Tao; Heyong Ye; Jun Wang; Rong Gao; Wenwei Liu (Environmental Science and Pollution Research, 2023)

Solar forcing and ENSO regulated rates of change of ecosystems in Northeast China since the last deglaciation - Guizai Gao; Honghao Niu; Lina Song; Jiangyong Wang; Meng Meng; Zhuo Yang; Linlin Liu; Yuanxiang Wei; Niankang Chen; Jihuai Yu; Dongmei Jie (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Reaction pathways control of long-chain alkanes hydroisomerization and hydrocracking via tailoring the metal-acid sites intimacy - Wenli Zhao; Linlin Liu; Xiaopo Niu; Xinyue Yang; Jiuyi Sun; Qingfa Wang (Fuel, 2023)

Effect of Na+ and Ca2+ on the texture, structure and microstructure of composite protein gel of mung bean protein and wheat gluten - Ruqi Guo; Linlin Liu; Yuyang Huang; Mingshou Lv; Ying Zhu; Zihan Wang; Xiuqing Zhu; Bingyu Sun (Food Research International, 2023)

An ultra-stable high entropy metal nitride for aerobic oxidative desulfurization and source recovery of aromatic sulfides from fuel oils - Peiwen Wu; Chang Deng; Penghui Liu; Feng Liu; Linlin Chen; Bangzhu Wang; Wenshuai Zhu; Chunming Xu (Chemical Engineering Journal, 2023)

Novel electron donor boosting the electron supply capacity of hierarchical structure carbon nitride for efficient photocatalytic hydrogen peroxide production - Linlin Sun; Xiaoshuo Liu; Huiling Ji; Xunlei Ding; Nan Jiang; Jigang Wang (Chemical Engineering Journal, 2023)

Construction of CoTiO3/TiO2/Ti composite catalytic membrane for degradation of tetracycline via peroxymonosulfate activation: Reactive oxygen species and electron transfer pathways - Yi Li; Linlin Wang; Longfei Wang; Weijie Wu; Fangjie Zhang; Haijiao Xie (Chemical Engineering Journal, 2023)

Li-intercalation chemistry of few-layer borophene with ultrahigh capacity and fast kinetics - Linlin Guo; Huili Wang; Zhonghan Wu; Xinru Yang; Ruoxuan Ma; Yanfang Hu; Geng Li; Dongjie Shi; Wei Xie; Wei Zhang; Fujun Lan; Limin Zhou; et al. (Chemical Engineering Journal, 2023)

Gas-pressurized torrefaction of lignocellulosic solid wastes: Low-temperature deoxygenation and chemical structure evolution mechanisms - Liu Shi; Zhenzhong Hu; Xian Li; Shuo Li; Linlin Yi; Xiaohua Wang; Hongyun Hu; Guangqian Luo; Hong Yao (Bioresource Technology, 2023)

Multi-valent mRNA vaccines against monkeypox enveloped or mature viron surface antigens demonstrate robust immune response and neutralizing activity - Niubing Zhang; Xiang Cheng; Yilong Zhu; Ouyang Mo; Huiqing Yu; Liqi Zhu; Juan Zhang; Linlin Kuang; Ying Gao; Ruiyuan Cao; Xiaozhen Liang; Haikun Wang; et al. (Science China Life Sciences, 2023)

Turbulence behaviors underlying the sensible heat and water vapor flux dissimilarity in a stably stratified flow - Xiaofeng Guo; Wei Yang; Jinkyu Hong; Linlin Wang; Zhiqiu Gao; Degang Zhou (Environmental Fluid Mechanics, 2023)

Application of carbon dots in food preservation: a critical review for packaging enhancers and food preservatives - Linlin Zhao; Min Zhang; Arun S. Mujumdar; Haixiang Wang (Critical Reviews in Food Science and Nutrition, 2023)

Construction of a novel ferrihydrite/MoS2 heterogeneous Fenton-like catalyst for efficient degradation of organic pollutants under neutral conditions - Da Chang; Juanjuan Sun; Chang Wang; Linlin Hao; Ming Zeng (Environmental Science and Pollution Research, 2023)

A novel framework for combining polarimetric Sentinel-1 InSAR time series in subsidence monitoring - A case study of Sydney - Alex Hay-Man Ng; Ziyue Liu; Zheyuan Du; Hengwei Huang; Hua Wang; Linlin Ge (Remote Sensing of Environment, 2023)

Effect of non-permeable cryoprotectant sucrose on the development of spotted knifejaw (Oplegnathus punctatus) embryos - Linlin Li; Yongsheng Tian; Zhentong Li; Pengfei Duan; Xinyi Wang; Shuai Chen; Linna Wang; Yang Liu; Qingbin Wang; Wensheng Li; Xia Zhao; Wenhui Ma; et al. (Cryobiology, 2023)

Synergistic strategy based on mild phototherapy and deep tumor hypoxia reversal comprehensively remodels the tumor microenvironment for improved immunotherapy - Linlin Tao; Gang Cheng; Fangnan Lv; Ruiqi Wang; Nan Yang; Zuhang Xing; Boyu Gu; Siyuan Meng; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2023)

Schemes for enhanced antioxidant stability in frying meat: a review of frying process using single oil and blended oils - Ju Shen; Min Zhang; Linlin Zhao; Arun S. Mujumdar; Haixiang Wang (Critical Reviews in Food Science and Nutrition, 2023)

Exploration on the reasons for low efficiency of arable land protection policy in China: an evolutionary game theoretic model - Linlin Wang; Zhuo Li; Chengcheng Yuan; Liming Liu (Environment, Development and Sustainability, 2023)

Development of a double-stage-yield dissipative beam-to-column joint: Experimental study and application for structural response control - Cantian Yang; Linlin Xie; Aiqun Li; Xinyu Wang (Soil Dynamics and Earthquake Engineering, 2023)

Anthropogenic heat variation during the COVID-19 pandemic control measures in four Chinese megacities - Qingyan Meng; Jiangkang Qian; Uwe Schlink; Linlin Zhang; Xinli Hu; Jianfeng Gao; Qiao Wang (Remote Sensing of Environment, 2023)

Paleoproterozoic skarn mineralization events and geodynamic background in the Jiao-Liao-Ji Belt: Geological, geochemical and chronological evidence from the Daqinggou Fe–Cu polymetallic deposit in Ji'an, NE China - YanPeng Liu; JingGui Sun; LinLin Wang; ZhiKai Xu; ChengLin Bai; Xiang Chang; TingTing Zhang (Precambrian Research, 2023)

Inequality and its driving forces in residential CO2 emission: Perspective of energy use pattern - Lei Chen; Linyu Xu; Yongyang Wang; Linlin Xia; Zhifeng Yang (Journal of Cleaner Production, 2023)

The lysosome-phagosome pathway mediates immune regulatory mechanisms in Mesocentrotus nudus against Vibrio coralliilyticus infection - Yanxia Wang; Quanchao Wang; Linlin Chen; Baoquan Li (Fish & Shellfish Immunology, 2023)

A parallel Python-based tool for meshing watershed rivers at continental scale - Fei Ye; Linlin Cui; Yinglong Zhang; Zhengui Wang; Saeed Moghimi; Edward Myers; Greg Seroka; Alan Zundel; Soroosh Mani; John G.W. Kelley (Environmental Modelling & Software, 2023)

Strong and continuous MXene/sodium alginate composite fibers prepared by immersion rotary jet spinning process with outstanding electromagnetic interference shielding performance - Guoxin Zhao; Chao Sui; Linlin Miao; Junjiao Li; Lei Wen; Gong Cheng; Chenxi Zhao; Weizhe Hao; Yuna Sang; Jiaxuan Li; Zhuochao Zhang; Yushun Zhao; et al. (Chemical Engineering Journal, 2023)

Recognize enhanced temporal-spatial-spectral features with a parallel multi-branch CNN and GRU - Linlin Wang; Mingai Li; Liyuan Zhang (Medical & Biological Engineering & Computing, 2023)

On the effects of rheological behavior on landslide motion and tsunami hazard for the Baiyun Slide in the South China Sea - Zhiyuan Ren; Hua Liu; Linlin Li; Yuchen Wang; Qiliang Sun (Landslides, 2023)

Prognostic value of the WT-1 gene combined with recurrent cytogenetic genes in acute myeloid leukemia - Qing Zhang; Linlin Liu; Haotian Yan; Xiyang Ren; Mei Zhou; Shudao Xiong; Huiping Wang; Qianshan Tao; Zhimin Zhai (Immunogenetics, 2023)

Pathogenicity and immune response of the sea urchin Mesocentrotus nudus to Vibrio coralliilyticus infection - Yanxia Wang; Quanchao Wang; Linlin Chen; Ruxin Ding; Zirui Peng; Baoquan Li (Aquaculture, 2023)

High-pressure synthesis of fully sp2-hybridized polymeric nitrogen layer in potassium supernitride - Minghong Sui; Shuang Liu; Peng Wang; Nianlong Zou; Qing Dong; Miao Zhou; Shifeng Niu; Lei Yue; Zitong Zhao; Linlin Guo; Bo Liu; Ran Liu; et al. (Science Bulletin, 2023)

Corrigendum to “Self-assembly of Fe3O4 with natural tannin as composites for microalgal harvesting” [Fuel 321 (2022) 124038] - Xiaoyu Wang; Chuang Liu; Linlin Qin; Wenyan Liang (Fuel, 2023)

Dissipation and movement of soil water in artificial forest in arid oasis areas: Cognition based on stable isotopes - Dongdong Qiu; Guofeng Zhu; Xinrui Lin; Yinying Jiao; Siyu Lu; Jiatong Liu; Jiawei Liu; Wenhao Zhang; Linlin Ye; Rui Li; Qinqin Wang; Longhu Chen (CATENA, 2023)

Genetic diversity and population structure of the sea star Asterias amurensis in the northern coast of China - Quanchao Wang; Ying Liu; Zirui Peng; Linlin Chen; Baoquan Li (Journal of Oceanology and Limnology, 2023)

Hair Selenium of Residents in Keshan Disease Endemic and Non-endemic Regions in China - Yuehui Jia; Ruixiang Wang; Guijin Li; Chen Feng; Lei Qi; Yuanyuan Wang; Shengqi Su; Yuanjie Zou; Xu Liu; Yanan Wang; Yiyi Zhang; Linlin Du; et al. (Biological Trace Element Research, 2023)

Strategies for mapping protein hydrolysate profiles and pharmacokinetics based on non-targeted proteomics combining skyline-aided quantitative techniques - Shuying Mao; Wei Jin; Sisi Fu; Keanqi Liu; Feng Xu; Linlin Wu; Yexin Xu; Huizhu Yang; Huafang Liu; Guangji Wang; Yan Liang (Analytica Chimica Acta, 2023)

Seasonal distribution of the early life stages of the small yellow croaker ( Larimichthys polyactis ) and its dynamic controls adjacent to the Changjiang River Estuary - Min Xu; Yihe Wang; Zunlei Liu; Yong Liu; Yi Zhang; Linlin Yang; Fei Wang; Hui Wu; Jiahua Cheng (Fisheries Oceanography, 2023)
The distribution of the early life stages of Larimichthys polyactis indicates the availability of suitable spawning and nursing grounds and enables a better understanding of the distribution of its geographic subpopulations and isolation. Large‐scale quantitative ichthyoplankton surveys of L. polyactis were performed from March to July 2018, and a numerical hydrodynamic model was applied to explore the spatiotemporal distribution and habitats of L. polyactis early life stages adjacent to the Changjiang River Estuary. Two distinct early life stage distribution patterns were found. One occurred during March and April in the deep waters seaward of the Changjiang River bottom plume front, to the east and southeast of the Changjiang River Estuary. The other occurred in May and June throughout the entire water column in coastal waters to the east and north of the Changjiang River Estuary. Rising seasonal temperatures, and the local dynamic processes such as the Changjiang River plume, determined the transitions between the two distribution patterns. A potential fish larval migration route from the southern deep shelf waters to the northern coastal waters within the motor‐trawl prohibition line was suggested. This study contributes to our understanding of the mixture of habitats used by the two L. polyactis subpopulations in the southern Yellow Sea and the East China Sea.

Estimation of urban-scale photovoltaic potential: A deep learning-based approach for constructing three-dimensional building models from optical remote sensing imagery - Longxu Yan; Rui Zhu; Mei-Po Kwan; Wei Luo; De Wang; Shangwu Zhang; Man Sing Wong; Linlin You; Bisheng Yang; Biyu Chen; Ling Feng (Sustainable Cities and Society, 2023)

A preliminary study to explain how Streptomyces pactum (Act12) works on phytoextraction: soil heavy metal extraction, seed germination, and plant growth - Nina Wang; Jie Ren; Linlin Wang; Yuheng Wang; Ze Wang; Di Guo (Environmental Monitoring and Assessment, 2023)

Elevation-dependent tree growth response to recent warming and drought on eastern Tibetan Plateau - Dingcai Yin; Xiaohua Gou; Haijiang Yang; Kai Wang; Jie Liu; Yiran Zhang; Linlin Gao (Climatic Change, 2023)

Influence Mechanism of New-type Urbanization on Urban Land Use Efficiency in the Yangtze River Delta, China - Qingke Yang; Linlin Ding; Lei Wang; Chao Liu; Yeting Fan; Ying Li; Yazhu Wang (Chinese Geographical Science, 2023)

Sources and historical records of metal(loid)s in river sediments from an agricultural tributary of Tuojiang river: Evidence from geochemical analyses and Pb isotope - Fen Xu; Rui Yang; Hong Wang; Xiaoxia He; Weiwei Li; Yao Wei; Linlin Bao; Jianfei Yuan; Hongjin Tong (Chemosphere, 2023)

Upscaling dispersivity for conservative solute transport in naturally fractured media - Sida Jia; Zhenxue Dai; Zhichao Zhou; Hui Ling; Zhijie Yang; Linlin Qi; Zihao Wang; Xiaoying Zhang; Hung Vo Thanh; Mohamad Reza Soltanian (Water Research, 2023)

Role of local climate zones and urban ventilation in canopy urban heat island–heatwave interaction in Nanjing megacity, China - Weishou Tian; Yuanjian Yang; Linlin Wang; Lian Zong; Yanhao Zhang; Duanyang Liu (Urban Climate, 2023)

Atomic-level chemical reaction promoting external quantum efficiency of organic photomultiplication photodetector exceeding 108% for weak-light detection - Linlin Shi; Yizhi Zhu; Guohui Li; Ting Ji; Wenyan Wang; Ye Zhang; Yukun Wu; Yuying Hao; Kaiying Wang; Jun Yuan; Yingping Zou; Beng S. Ong; et al. (Science Bulletin, 2023)

Self-powered energy harvesting and implantable storage system based on hydrogel-enabled all-solid-state supercapacitor and triboelectric nanogenerator - Zhuo Wang; Shuncheng Yao; Shaobo Wang; Zhirong Liu; Xingyi Wan; Quanhong Hu; Yunchao Zhao; Cheng Xiong; Linlin Li (Chemical Engineering Journal, 2023)

Unevenly spatiotemporal distribution of urban excess warming in coastal Shanghai megacity, China: Roles of geophysical environment, ventilation and sea breezes - Yuanjian Yang; Min Guo; Linlin Wang; Lian Zong; Duanyang Liu; Wenjie Zhang; Mengya Wang; Bingcheng Wan; Yide Guo (Building and Environment, 2023)

Applying correlation analysis to electrode optimization in source domain - Yuxin Dong; Linlin Wang; Mingai Li (Medical & Biological Engineering & Computing, 2023)

Influence of monsoon anomalies on intra-annual density fluctuations of Chinese pine in the Loess Plateau - Shuangjuan Wang; Yang Deng; Linlin Gao; Yuhang Zhang; Xingying Shi; Xiaohua Gou (International Journal of Biometeorology, 2023)

Nanophytoplankton and microphytoplankton in the western tropical Pacific Ocean: its community structure, cell size and carbon biomass - Wenzhuo Yan; Zhuo Chen; Linlin Zhang; Feng Wang; Guicheng Zhang; Jun Sun (Frontiers in Marine Science, 2023)
Phytoplankton, as a crucial component of the marine ecosystem, plays a fundamental role in global biogeochemical cycles. This study investigated the composition and distribution of phytoplankton in the western Tropical Pacific Ocean using the Utermöhl method and carbon volume conversion. We identified four primary groups of phytoplankton: dinoflagellates (181 species), diatoms (73 species), cyanobacteria (4 species), and chrysophyceae (2 species). The clustering analysis classified phytoplankton into four groups based on their composition, which were found to be closely related to ocean currents. Diatoms were highly abundant in areas influenced by current-seamount interaction. In contrast, areas with little influence from ocean currents were dominated by Trichodesmium . The majority of phytoplankton had an equivalent spherical diameter (ESD) of 2-12 μm, with a few exceeding 25 μm. Although nanophytoplankton (ESD = 2-20 µm) dominated cell abundance, microphytoplankton (ESD = 20-200 µm) contributed significantly to carbon biomass (792.295 mg m -3 ). This study yielded valuable insights into the distribution and composition of phytoplankton in the western tropical Pacific Ocean, shedding light on the relationship between species distribution and ocean currents. In addition, it provided fundamental information regarding cell size and carbon biomass within the region.

Singlet oxygen generation in light-assisted peroxymonosulfate activation by carbon nitride: Role of elevated crystallinity - Beizhao Chen; Xun Liu; Bei Liu; Qi Han; Li Li; Li Wang; Yufei Shu; Linlin Zang; Wenlei Zhu; Zhongying Wang (Chemosphere, 2023)

Accumulation and speciation of arsenic in Eisenia fetida in sodium arsenite spiked soils - A dynamic interaction between soil and earthworms - Weiqin Xing; Hongpei Geng; Yali Wang; Linlin Zhao; Yongqiang Yang; Yale Wang; Shuhang Tian; Yongxin Cao; Zhe Zhang; Liping Li (Chemosphere, 2023)

Environmental DNA metabarcoding reveals the influence of human activities on microeukaryotic plankton along the Chinese coastline - Zheng Zhang; Jiang Li; Hongjun Li; Linlin Wang; Yuqi Zhou; Shuzhen Li; Zhaojing Zhang; Kai Feng; Ye Deng (Water Research, 2023)

Global analysis of gene expression profiles and gout symptoms in goslings infected with goose astrovirus - Chenggang Liu; Linlin Li; Jiawen Dong; Junqin Zhang; Yunzhen Huang; Qi Zhai; Yong Xiang; Jin Jin; Xianshe Huang; Gang Wang; Minhua Sun; Ming Liao (Veterinary Microbiology, 2023)

Simultaneous oxidation and absorption of nitric oxide and sulfur dioxide by peroxymonosulfate activated by bimetallic metal-organic frameworks - Zhaoxin Wan; Xiude Hu; Chengbo Li; Jiawei Zhang; Qi Wang; Long Fang; Linlin Zhang; Qingjie Guo; Deshuai Sun (Journal of Environmental Chemical Engineering, 2023)

Bimetal Cu and Fe modified g-C3N4 sheets grown on carbon skeleton for efficient and selective photocatalytic reduction of CO2 to CO - Songyuan Bian; Xueyan Li; Long Zhang; Libin Wang; Jingzhen Wang; Qing Xu; Linlin Zang; Yanhong Zhang; Liguo Sun (Journal of Environmental Chemical Engineering, 2023)

Water/acid/reductive biomass leaching of Cr(VI) in chromium ore processing residue (CORP) for safe discharge of effluent and to recover Cr(III) and gypsum - Zhenan Jin; Baoren Wang; Feixian Zheng; Linlin Tong; Jiafeng Li; Qianfei Zhao; Liuhan Jin (Hydrometallurgy, 2023)

Interactions between zein and anthocyanins at different pH: Structural characterization, binding mechanism and stability - Shuangjian Li; Xiang Wang; Xiaoqian Zhang; Hui Zhang; Siyuan Li; Jianzhong Zhou; Linlin Fan (Food Research International, 2023)

Spatial distribution patterns across multiple microbial taxonomic groups - Xiongfeng Du; Songsong Gu; Zheng Zhang; Shuzhen Li; Yuqi Zhou; Zhaojing Zhang; Qi Zhang; Linlin Wang; Zhicheng Ju; Chengliang Yan; Tong Li; Danrui Wang; et al. (Environmental Research, 2023)

MOF-templated fabrication of Ni@C/g-C3N4 catalyst with high-dense accessible active sites achieving dicyclopentadiene hydrogenation at ambient conditions and comprehensive mechanism insight - Chenghong Wu; Xiaopeng Chen; Jiezhen Liang; Jiawei Fu; Zhongyao Zhang; Xiaojie Wei; Linlin Wang (Chemical Engineering Journal, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

A Tiered Ecological Risk Assessment of Caffeine by Using Species Sensitivity Distribution Method in the Nansi Lake Basin - Lei Zheng; Juan Zhang; Yinan Wu; Linlin Li; Junhong Ling; Sai Wang; Wenlong Yang; Yezhu Yin; Liang Dong; Yizhang Zhang (Bulletin of Environmental Contamination and Toxicology, 2023)

A rapid and sensitive single-cell proteomic method based on fast liquid-chromatography separation, retention time prediction and MS1-only acquisition - Wei Fang; Zhuokun Du; Linlin Kong; Bin Fu; Guibin Wang; Yangjun Zhang; Weijie Qin (Analytica Chimica Acta, 2023)

Use of iron-loaded biochar to alleviate anammox performance inhibition under PFOA stress conditions: Integrated analysis of sludge characteristics and metagenomics - Linqin Tang; Chengyuan Su; Qing Wang; Linlin Cao; Yunchuan Xian; Shitong Wen; Yijie Zhou; Shu Gao (Science of The Total Environment, 2023)

Long-term non-phosphorus application increased paddy methane emission by promoting organic acid and methanogen abundance in Tai Lake region, China - Chen Xu; Susu Shen; Beibei Zhou; Yuanyuan Feng; Zhu He; Linlin Shi; Yu Wang; Haihou Wang; Tripti Mishra; Lihong Xue (Science of The Total Environment, 2023)

Efflux pumps activation caused by mercury contamination prompts antibiotic resistance and pathogen's virulence under ambient and elevated CO2 concentration - Linlin Qiu; Yabo Wang; Wenchao Du; Fuxun Ai; Ying Yin; Hongyan Guo (Science of The Total Environment, 2023)

Global, regional, and national deaths, disability-adjusted life years, years lived with disability, and years of life lost for the global disease burden attributable to second-hand smoke, 1990–2019: A systematic analysis for the Global Burden of Disease Study - Chunxia Zhai; Dingtao Hu; Guanghui Yu; Wanqin Hu; Qiqun Zong; Ziye Yan; Yuhua Wang; Linlin Wang; Tingyu Zhang; Hongyu Sun; Ling Cai; Liangyu Cui; et al. (Science of The Total Environment, 2023)

Pre-monsoon drought variability in the southeastern Loess Plateau over the past 246 years - Yongkang Duan; Shuangjuan Wang; Yang Deng; Linlin Gao; Shuhua Qiao; Xiaohua Gou (Quaternary International, 2023)

Bioimmobilization and transformation of chromium and cadmium in the fungi-microalgae symbiotic system - Junjun Wang; Qinghua Tian; Linlin Cui; Jinju Cheng; Hao Zhou; Yejuan Zhang; Anan Peng; Li Shen (Journal of Hazardous Materials, 2023)

Recent advances of plasmonic elemental Bi based photocatalysts in environmental remediation and energy conversion - Cailiang Yue; Linlin Zhu; Yixing Qiu; Zhiling Du; Jinli Qiu; Fuqiang Liu; Fenghe Wang (Journal of Cleaner Production, 2023)

Nitrogen-doped porous carbons from polyacrylonitrile fiber as effective CO2 adsorbents - Changdan Ma; Jiali Bai; Xin Hu; Zhuohan Jiang; Linlin Wang (Journal of Environmental Sciences, 2023)

Rhizobacteria helps to explain the enhanced efficiency of phytoextraction strengthened by Streptomyces pactum - Linlin Wang; Nina Wang; Di Guo; Zhengzheng Shang; Yiying Zhang; Song Liu; Yuheng Wang (Journal of Environmental Sciences, 2023)

Origins of black carbon from anthropogenic emissions and open biomass burning transported to Xishuangbanna, Southwest China - Xuyan Liu; Siwen Wang; Qianqian Zhang; Chunlai Jiang; Linlin Liang; Shihao Tang; Xingying Zhang; Xiuzhen Han; Lin Zhu (Journal of Environmental Sciences, 2023)

Colorimetric active carboxymethyl chitosan/oxidized sodium alginate-Oxalis triangularis ssp. papilionacea anthocyanins film@gelatin/zein-linalool membrane for milk freshness monitoring and preservation - Linlin Li; Li Xia; Feng Xiao; Yewen Xiao; Lanhua Liu; Shaotong Jiang; Hualin Wang (Food Chemistry, 2023)

Enhanced antihypertensive potential of fermented pomegranate juice: The contribution of phenolic compounds biotransformation and the resultant angiotensin-I-converting enzyme inhibition mechanism - Li Chen; Linlin Wang; Guowei Shu; Jiaojiao Yuan; Jiying Zhang; Shan Qin; Jianke Li (Food Chemistry, 2023)

Improving effect of disaccharides and maltodextrin on preparation of egg yolk powder by microwave-assisted freeze-drying: Functional properties, structural properties, and retention rate of active IgY - Zhe Wang; Xu Duan; Guangyue Ren; Jingfang Guo; Jiangtao Ji; Yiming Xu; Weiwei Cao; Linlin Li; Mengyue Zhao; Yuan Ang; Xin Jin; Bhesh Bhandari; et al. (Food Chemistry, 2023)

Preparation of PLGA/ε-polylysine nanofibers and their application for pork preservation - Minmin Chen; Linlin Li; Li Xia; Yaqiong Kong; Suwei Jiang; Xiaoju Chen; Hualin Wang (Food Packaging and Shelf Life, 2023)

Selective recovery of lithium from spent LiFePO4 battery via a self-catalytic air oxidation method - Hao Jin; Jialiang Zhang; Cheng Yang; Linlin Ma; Yongqiang Chen; Chengyan Wang (Chemical Engineering Journal, 2023)

Arsenic Exposure, Periconceptional Folic Acid Supplementation, and the Risk for Neural Tube Defects: A Case–Control Study - Xin Pi; Chengrong Wang; Shengju Yin; Lei Jin; Zhiwen Li; Linlin Wang; Jufen Liu; Yali Zhang; Aiguo Ren (Exposure and Health, 2023)

A High Concentration of Polycyclic Aromatic Hydrocarbons in Umbilical Cord Tissue is Associated with an Increased Risk for Fetal Neural Tube Defects - Shengju Yin; Ying Sun; Jinhui Yu; Zaiming Su; Mingkun Tong; Yali Zhang; Jufen Liu; Linlin Wang; Zhiwen Li; Aiguo Ren; Lei Jin (Exposure and Health, 2023)

Straw type and returning amount affects SOC fractions and Fe/Al oxides in a rice-wheat rotation system - Linlin Dong; Haihou Wang; Yuan Shen; Lingqing Wang; Haidong Zhang; Linlin Shi; Changying Lu; Mingxing Shen (Applied Soil Ecology, 2023)

Impact of diurnal temperature range on other infectious diarrhea in Tongcheng, China, 2010–2019: a distributed lag non-linear analysis - Linlin Wang; Jian Cheng; Guanghui Yu; Qiqun Zong; Chunxia Zhai; Wanqin Hu; Yuhua Wang; Ziye Yan; Tingyu Zhang; Junwu Wang; Chengye Zhang; Hong Su; et al. (Environmental Science and Pollution Research, 2023)

Correction to: Cl-amidine attenuates lipopolysaccharide-induced inflammation in human gingival fibroblasts via the JNK/MAPK, NF-κB, and Nrf2 signalling pathways - Jianxin Du; Ning Wang; Hui Sun; Linlin Zheng; Xiangqin Qi (Human Cell, 2023)

Contribution of the TGFβ signaling pathway to pigmentation in sea cucumber (Apostichopus japonicus) - Linlin Yao; Bin Zhao; Qi Wang; Xuyang Jiang; Sha Han; Wei Hu; Chenglin Li (Frontiers in Marine Science, 2023)
Pigmentation mediated by the transforming growth factor β (TGFβ) signaling pathway is a key trait for understanding environmental adaptability and species stability. In this study, TGFβ signaling pathway members and their expression patterns in different color morphs of the sea cucumber Apostichopus japonicus were evaluated. Using a bioinformatics approach, 22 protein sequences of TGFβ signaling pathway members in A. japonicus were classified, including 14 that were identified for the first time in the species, including 7 ligands, 6 receptors, and 1 R-Smad. We further evaluated mRNA expression data for different color morphs and pigmentation periods. These results support the hypothesis that both subfamilies of the TGFβ superfamily, i.e., the TGFβ/activin/Nodal and BMP/GDF/AMH subfamilies, are involved in the regulation of pigmentation in A. japonicus . The former subfamily was complete and contributes to the different color morphs. The BMP/GDF/AMH subfamily was incomplete. BMP2/4-induced differentiation of white adipocytes was regulated by the BMP2/4–ACVR2A–Smad1 signaling pathway. These findings provide insight into the TGFβ family in early chordate evolution as well as the molecular basis of color variation in an economically valuable species.

Understanding the N-acylated homoserine lactones(AHLs)-based quorum sensing for the stability of aerobic granular sludge in the aspect of substrate hydrolysis enhancement - Zhiming Zhang; Linlin Wang; Yatong Ji; Runjuan Cao; Jiaheng Zhou; Mengyan Li; Liang Zhu; Xiangyang Xu (Science of The Total Environment, 2023)

Insight into the design and construction of Cr substituted Co-based columnar activated coke catalysts for effective and reliable removal of methylbenzene and Hg0 concurrently - Lei Gao; Lei Yi; Dong Xie; Hanqing Wang; Caiting Li; Linlin Li; Yijin Liu; Jinke Xie; Yihui Zhou; Yingyun Liu (Fuel, 2023)

Convolutional neural networks (CNNs)-based multi-category damage detection and recognition of high-speed rail (HSR) reinforced concrete (RC) bridges using test images - Lingkun Chen; Wenxin Chen; Lu Wang; Chencheng Zhai; Xiaolun Hu; Linlin Sun; Yuan Tian; Xiaoming Huang; Lizhong Jiang (Engineering Structures, 2023)

Multi-scale ocean dynamical processes in the Indo-Pacific Convergence Zone and their climatic and ecological effects - Yan Du; Fan Wang; Tianyu Wang; Weiwei Liu; Linlin Liang; Ying Zhang; Yunfan Chen; Jiaxing Liu; Wei Wu; Kefu Yu; Jing Zhang (Earth-Science Reviews, 2023)

H2O2-TiO2 photocatalytic degradation of chondroitin sulfate and in vivo absorption and excertion of its product - Weigong Tian; Ying You; Xiaona Sun; Linlin Wang; Lilong Wang; Songtao Wang; Chunqing Ai; Shuang Song (Carbohydrate Polymers, 2023)

Metagenomic and extracellular polymeric substances analysis reveals the mechanism of exogenous N-hexanoyl-L-homoserine lactone in alleviating the inhibition of perfluorooctanoic acid on anammox process - Linqin Tang; Chengyuan Su; Cuiping Fan; Linlin Cao; Zhu Liang; Yufeng Xu; Zhengpeng Chen; Qing Wang; Menglin Chen (Bioresource Technology, 2023)

Chinese consensus guidelines for therapeutic drug monitoring of polymyxin B, endorsed by the Infection and Chemotherapy Committee of the Shanghai Medical Association and the Therapeutic Drug Monitoring Committee of the Chinese Pharmacological Society - Xiaofen Liu; Chenrong Huang; Phillip J. Bergen; Jian Li; Jingjing Zhang; Yijian Chen; Yongchuan Chen; Beining Guo; Fupin Hu; Jinfang Hu; Linlin Hu; Xin Li; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Development of effective expanded vermiculite flocculant for enhanced primary treatment of swine wastewater: Lab-scale investigations - Linlin Hao; Juanjuan Sun; Ming Zeng; Chang Wang (Applied Clay Science, 2023)

Otus scops adenovirus: the complete genome sequence of a novel aviadenovirus discovered in a wild owl - Weibo Zheng; Tingshu Jiang; Zhe Zhang; Dong Pan; Wenli Tang; Youzhi Li; Linlin Jiang; Hongwei Zhu; Xin Yu; Guozhong Chen; Jiao Wang; Jianlong Zhang; et al. (Archives of Virology, 2023)

The Environmental Niche of the Tuna Purse Seine Fleet in the Western and Central Pacific Ocean Based on Different Fisheries Data - Shenglong Yang; Linlin Yu; Fei Wang; Tianfei Chen; Yingjie Fei; Shengmao Zhang; Wei Fan (Fishes, 2023)
Understanding the spatial pattern of human fishing activity is very important for fisheries resource monitoring and spatial management. The environmental preferences of tropical tuna purse seine fleet in the Western and Central Pacific Ocean (WCPO) were constructed and compared at different spatial scales based on the fishing effort (FE) data from the available automatic identification system (AIS) and commercial fishery data compiled from the Western and Central Pacific Fisheries Commission (WCPFC), using maximum entropy (MaxEnt) methods. The MaxEnt models were fitted with FE and commercial fishery data and remote sensing environmental data. Our results showed that the area under the curve (AUC) value each month based on the commercial fishery data (1°) and FE at 0.25° and 0.5° spatial scales was greater than 0.8. The AUC values each month based on the FE data at a 1° scale ranged from 0.775 to 0.829. The AUC values based on commercial fishing data at the 1° scale were comparable to the model results based on FE data at the 0.5° scale and inferior to the model results based on FE data at the 0.25° scales. Overall, the sea surface temperature (SST), temperature at 100 metres (T100), oxygen concentration at 100 metres (O100) and total primary production (PP) had the greatest influence on the distribution of the purse seine tuna fleet. The oxygen concentration at 200 metres (O200), distance to shore (DSH), dissolved oxygen (Dox), EKE, mixed layer depth (Mld), sea surface salinity (SSS), salinity at 100 metres (S100) and salinity at 200 metres (S200) had moderate influences, and other environmental variables had little influence. The suitable habitat areas varied in response to environmental conditions. The purse seine tuna fleet was mostly present at locations where the SST, T100, O100, O200 and PP were 28–30 °C, 27–29 °C, 150–200 mmol/m3 and 5–10 mg/m−3, respectively. The MaxEnt models enable the integration of AIS data and high-resolution environmental data from satellite remote sensing to describe the spatiotemporal distribution of the tuna purse seine fishery and the influence of environmental variables on the distribution, and can provide forecasts for fishing ground distributions based on future remote sensing environmental data.

Heterosis in growth and low temperature tolerance in Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) - Shuai Chen; Yongsheng Tian; Zhentong Li; Yang Liu; Ziqi Li; Pengfei Duan; Linlin Li; Xinyi Wang; Linna Wang; Xinlei He; Xia Zhao; Wensheng Li; et al. (Aquaculture, 2023)

RETRACTED: Study on the effect of SDBS and SDS on deep coal seam water injection - Lianman Xu; Yajing Li; Linlin Du; Fengshuo Yang; Runjie Zhang; Hao Wei; Gang Wang; Zhe Hao (Science of The Total Environment, 2023)

Current recycling strategies and high-value utilization of waste cotton - Linlin Lu; Wei Fan; Xue Meng; Lili Xue; Shengbo Ge; Chen Wang; Shin Ying Foong; Cindy S.Y. Tan; Christian Sonne; Mortaza Aghbashlo; Meisam Tabatabaei; Su Shiung Lam (Science of The Total Environment, 2023)

Exploratory study on the potential regulating role of Peroxiredoxin 6 on proteolysis and relationships with desmin early postmortem - Xinyi Wang; Linlin Huang; Yimin Zhang; Lixian Zhu; Xiaoyin Yang; Huixin Zuo; Xin Luo; Yanwei Mao; David L. Hopkins (Meat Science, 2023)

Sustainable estuarine governance based on artificial island scheme for a highly anthropogenic influenced Shenzhen Bay, China - Wanrong Wu; Linlin Wang; Xiaoyu Lei; Yang Zheng; Jie Wei; Xian-zhong Mao (Journal of Hydrology, 2023)

Different nitrogen fertilizer application in the field affects the morphology and structure of protein and starch in rice during cooking - Shijie Shi; Gaoyu Zhang; Linlin Chen; Wenhui Zhang; Xiaodong Wang; Keqiang Pan; Lina Li; Jing Wang; Juan Liu; Cougui Cao; Yang Jiang (Food Research International, 2023)

Forecasting GHG emissions for environmental protection with energy consumption reduction from renewable sources: A sustainable environmental system - Jiaqing Huang; Linlin Wang; Abu Bakkar Siddik; Zulkiflee Abdul-Samad; Arpit Bhardwaj; Bharat Singh (Ecological Modelling, 2023)

Pseudo-isotopic substituted (Co0.5Ni0.5)S2 anchoring on V4C3T MXene as an efficient anode for full sodium-ions batteries - Yilin Li; J.M. Cao; Linlin Li; Zeyu Yuan; Dongdong Li; Junzhi Li; Yuming Zhang; Hao Xu; Wei Han; Lili Wang (Chemical Engineering Journal, 2023)

Engineered anti-cancer nanomedicine for synergistic ferroptosis-immunotherapy - Xinyu Zhang; Haiyan Ge; Yanling Ma; Linlin Song; Yansong Ma; Guanglong Tian; Lei Wang; Qingwei Meng; Xiao Sun (Chemical Engineering Journal, 2023)

Flexible and highly piezoelectric nanofibers with organic–inorganic coaxial structure for self-powered physiological multimodal sensing - Xingyi Wan; Zhuo Wang; Xinyang Zhao; Quanhong Hu; Zhou Li; Zhong Lin Wang; Linlin Li (Chemical Engineering Journal, 2023)

Ethylene-vinyl alcohol copolymer/gelatin/cellulose acetate bionic trilayer fibrous membrane for moisture-adjusting - Li Xia; Linlin Li; Yewen Xiao; Feng Xiao; Wei Ji; Shaotong Jiang; Hualin Wang (Carbohydrate Polymers, 2023)

Whether increased water‐use efficiency of Picea crassifolia promotes radial growth of trees in the eastern Qilian Mountains - Kai Wang; Xiaohua Gou; Linlin Gao; Wenhuo Liu; Haowen Fan; Weiguo Zhang; Haijiang Yang (International Journal of Climatology, 2022)
Global change, characterized by elevated atmospheric CO 2 concentrations and warming, is profoundly affecting terrestrial forests. However, whether the increasing atmospheric CO 2 concentration has a fertilizer effect on tree growth and whether intrinsic water use efficiency (iWUE) promotes tree growth in semi‐arid regions is not entirely clear. In this study, we evaluated the relationships between tree‐ring widths, δ 13 C values and iWUE of Qinghai Spruce ( Picea crassifolia Kom.) in the eastern Qilian Mountains, northwestern China. We found that the iWUE is significantly consistent with the δ 13 C of rings in the high‐frequency signal, and the relationship between iWUE and tree‐ring width is unstable. The first‐order difference correlation analysis with meteorological data showed that both the iWUE and tree‐ring width were drought‐limited. The radial growth was mainly regulated by water availability in current April and July, while annual variation of iWUE was primarily controlled by that in current July. In the early stage of trees growth, there was a positive relationship between iWUE and radial growth due to the CO 2 fertilization. During the 1970s–2000s, the effect of water availability in July on radial growth increases because of the decreased precipitation in July. This has decreased stomatal conductance, intercellular CO 2 concentration, carbon uptake and growth, contributing to the negatively significant correlation between tree‐ring widths and iWUE ( p

Structural and functional analysis of a potent human neutralizing antibody against enterovirus A71 - Zhe Chen; Linlin Bao; Bin Zhu; Hua Fu; Shuangli Zhu; Tianjiao Ji; Ying Xue; Chuan Liu; Xurong Wang; Fengdi Li; Qi Lv; Feifei Qi; et al. (Science China Life Sciences, 2022)

Talaromyces marneffei Infections in 8 Chinese Children with Inborn Errors of Immunity - Linlin Wang; Ying Luo; Xiaolin Li; Yixian Li; Yu Xia; Tingyan He; Yanyan Huang; Yongbin Xu; Zhi Yang; Jiayun Ling; Ruohang Weng; Xiaona Zhu; et al. (Mycopathologia, 2022)
Purpose Talaromyces marneffei (TM) is an opportunistic fungus leading to multi-organ damages and poor prognosis in immunocompromised individuals. TM infections in children are rare and our knowledge to TM infection is insufficient. To investigate the clinical characteristics of TM-infected children and to explore the underlying mechanisms for host against TM, we analysed TM-infected patients diagnosed in our hospital. Methods Eight patients with TM infections have been identified in Shenzhen Children’s Hospital during 2017–2021. Clinical data were collected from medical records. Immunological features were evaluated by flow cytometry. Literatures were also reviewed to summarize the reported inborn errors of immunity (IEIs) with TM infections. Results All 8 children were HIV-negative. The most common symptom of TM infections was fever (8/8), followed by weight loss (7/8), pneumonia (7/8), hepatomegaly (7/8), splenomegaly (6/8), anemia (6/8), lymphadenopathy (5/8), thrombocytopenia (3/8), diarrhea (3/8), rashes or skin lesions (3/8), and osteolytic lesions (1/8). Five children died during the follow-ups. CD3+ T cells were decreased in 6 patients. Eight patients had reduced natural killer cells. All patients went gene sequencing and were finally diagnosed as IEIs, including STAT1 gain-of-function, IL-2 receptor common gamma chain deficiency, adenosine deaminase deficiency, CD40 ligand deficiency, and STAT3 deficiency. Another 4 types of IEIs (CARD9, IFN- γ receptor 1, RelB, and NFKB2 deficiency), have been reported with TM infections based on literature review. Conclusion TM infections resulted in systemic injuries and high mortality. The spectrum of IEIs underlying TM infections indicated that T cell-mediated immunity, IFN- γ , IL-17 signalings and NF-κB pathways were important for host responses against TM infection. In reverse, for HIV-negative children without other secondary immunodeficiencies, IEIs should be considered in TM-infected children.

Increased Expression of CD95 in CD4+ Effector Memory T Cells Promotes Th17 Response in Patients with Myasthenia Gravis - Xiaoyu Huang; Jie Zhu; Tan Liu; Fengzhan Li; Tingting Yang; Hao Li; Fei Chen; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; Deqin Geng (Journal of Neuroimmune Pharmacology, 2022)

The atypical functional connectivity of Broca’s area at multiple frequency bands in autism spectrum disorder - Lulu Cheng; Linlin Zhan; Lina Huang; Hongqiang Zhang; Jiawei Sun; Guofeng Huang; Yadan Wang; Mengting Li; Huayun Li; Yanyan Gao; Xize Jia (Brain Imaging and Behavior, 2022)

Core rhizosphere microbiome of Panax notoginseng and its associations with belowground biomass and saponin contents - Guangfei Wei; Guozhuang Zhang; Mengzhi Li; Congsheng Liu; Fugang Wei; Yong Wang; Zhixin Huang; Zhongjian Chen; Yuqing Zheng; Shilin Chen; Linlin Dong (Environmental Microbiology, 2022)
The core rhizosphere microbiome is critical for plant fitness. However, its contribution to the belowground biomass and saponin contents of Panax notoginseng remains unclear. High‐throughput sequencing of amplicon and metagenome was performed to obtain the microbiome profiles and functional traits in P. notoginseng rhizosphere across a large spatial scale. We obtained 639 bacterial and 310 fungal core OTUs, which were mainly affected by soil pH and organic matter (OM). The core taxa were grouped into four ecological clusters (i.e. high pH, low pH, high OM and low OM) for sharing similar habitat preferences. Furthermore, structural equation modelling (SEM) and correlation analyses revealed that the diversity and composition of core microbiomes, as well as the metagenome‐derived microbial functions, were related to belowground biomass and saponin contents. Key microbial genera related to the two plant indicators were also identified. In short, this study explored the main driving environmental factors of core microbiomes in the P. notoginseng rhizosphere and revealed that the core microbiomes and microbial functions potentially contributed to the belowground biomass and saponin contents of the plant. This work may enhance our understanding of interactions between microbes and perennial plants and improve our ability to manage root microbiota for the sustainable production of herbal medicine.

Prenatal exposure to silver is associated with an elevated risk for neural tube defects: a case–control study - Xin Pi; Chengrong Wang; Di Wang; Shengju Yin; Lei Jin; Zhiwen Li; Linlin Wang; Wentao Yue; Chenghong Yin; Aiguo Ren (Environmental Science and Pollution Research, 2022)

Cl-amidine attenuates lipopolysaccharide-induced inflammation in human gingival fibroblasts via the JNK/MAPK, NF-κB, and Nrf2 signalling pathways - Jianxin Du; Ning Wang; Hui Sun; Linlin Zheng; Xiangqin Qi (Human Cell, 2022)

LaeA regulates morphological development and ochratoxin A biosynthesis in Aspergillus niger - Mengwei Zhang; Yan Yang; Linlin Li; Shuwen Liu; Xianli Xue; Qiang Gao; Depei Wang; Ying Zhang; Jian Zhang (Mycotoxin Research, 2022)

Identification and functional analysis of two GJA8 variants in Chinese families with eye anomalies - Linlin Zhou; Xuejiao Sun; Xinyao Wang; Kangyu Liu; Zilin Zhong; Jianjun Chen (Molecular Genetics and Genomics, 2022)

Seasonal variability of the North Equatorial Current–Kuroshio Current–Mindanao Current based on observations - Fujun Wang; Linlin Zhang; Junqiao Feng; Dunxin Hu (Frontiers in Marine Science, 2022)
Utilizing the direct mooring observation along 130°E (10.5°N, 13°N, 15.5°N, and 18°N), 18°N (122.7°E, 123°E, and 123.3°E), and 8°N (127°E) and satellite data, the seasonal variabilities of the North Equatorial Current (NEC), Kuroshio Current (KC), and Mindanao Current (MC) were investigated. The southern part of the NEC along 130°E, the KC along 18°N, and the MC along 8°N featured similar seasonal cycles: that is, the currents were strong in spring and weak in autumn, while the KC along 18°N featured another peak in winter. Moreover, the seasonal phase of the NEC along 130°E was latitude-dependent; it advanced slightly from 10°N to 14°N and delayed poleward. The seasonal variabilities of the three currents were mainly controlled by local winds and Rossby waves via a geostrophic relationship, as the mooring observation was consistent with satellite data. The calculation shows that the local wind was dominant in the above mentioned in-phase areas (i.e., the southern part of the NEC, KC, and MC), while Rossby waves played an important role in the northern part of the NEC. The results indicate that the NEC–KC–MC system had the same zonal dynamics but different meridional dynamics across seasons.

Abnormal Level of Manganese, Iron, Iodine, and Selenium in the Hair of Children Living in Kashin–Beck Disease Endemic Areas - Feng’e Zhang; Cuiyan Wu; Pan Zhang; Xi Wang; Peilin Meng; Sijia Tan; Linlin Yuan; Xiong Guo (Biological Trace Element Research, 2022)

Urban Land Use Efficiency and Contributing Factors in the Yangtze River Delta Under Increasing Environmental Restrictions in China - Qingke Yang; Lei Wang; Xianhong Qin; Yeting Fan; Yazhu Wang; Linlin Ding (Chinese Geographical Science, 2022)

Interannual variations of the North Equatorial Current/Undercurrent from mooring array observations - Ying Huang; Linlin Zhang; Fujun Wang; Fan Wang; Dunxin Hu (Frontiers in Marine Science, 2022)
Interannual variability of the North Equatorial Current (NEC)/Undercurrent (NEUC) in the northwestern Pacific was investigated with the mooring array measurements at 130°E during 2014-2021, in combination with the satellite altimetry. Mooring observations indicate that the velocity of the NEC/NEUC in the upper 900 m exhibits significant variations on the interannual time scale. The westward-flowing NEC strengthens when the underlying eastward-flowing NEUC weakens, and the NEUC branch at 8.5°N is intensified during the mature phase of El Niño and reaches the maximum velocity during the decay phase of El Niño. The phase of the interannual variation of the currents delays with the increasing latitude, with the signal at 15°N lagging that at 8.5°N by about one year. Based on a 1.5 layer reduced gravity model, the interannual variation is suggested to be controlled mainly by the westward propagating baroclinic Rossby wave induced by the wind stress curl forcing in the central Pacific. Different propagating speed of the baroclinic Rossby wave at different latitudes explains the meridional phase lag of the interannual signal. Empirical Orthogonal Function and vertical mode decomposition analysis suggest that the interannual variation of the NEC/NEUC velocity in the northern part is dominated by surface-intensified signals with a vertical structure of the first baroclinic mode, while that in the southern part is dominated by subsurface-intensified signals which is associated with the combination of the first two baroclinic modes. The low-order mode baroclinic response of the ocean to the wind forcing accounts for the interannual fluctuation of the NEC/NEUC velocity observed by the mooring array.

Coffin-Siris syndrome in two chinese patients with novel pathogenic variants of ARID1A and SMARCA4 - Mingjie Liu; Linlin Wan; Chunrong Wang; Hongyu Yuan; Yun Peng; Na Wan; Zhichao Tang; Xinrong Yuan; Daji Chen; Zhe Long; Yuting Shi; Rong Qiu; et al. (Genes & Genomics, 2022)

AlgaeMask: An Instance Segmentation Network for Floating Algae Detection - Xiaoliang Wang; Lei Wang; Liangyu Chen; Feng Zhang; Kuo Chen; Zhiwei Zhang; Yibo Zou; Linlin Zhao (Journal of Marine Science and Engineering, 2022)
Video surveillance on the offshore booster station and around the coast is a effective way to monitor floating macroalgae. Previous studies on floating algae detection are mainly based on traditional image segmentation methods. However, these algorithms cannot effectively solve the problem of extracting Ulva prolifra and Sargassum at different sizes and views. Recently, instance segmentation methods have achieved great success in computer vision applications. In this paper, based on the CenterMask network, a novel instance segmentation architecture named AlgaeMask is proposed for floating algae detection from the surveillance videos. To address the feature extraction ability of the network in the inter-dependencies for position and channel, we introduce a new OSA-V3 module with the dual-attention block, which consists of a position attention mechanism and channel attention mechanism. Meanwhile, scale-equalizing pyramid convolution is introduced to solve the problem of scale difference. Finally, we introduce the feature decoder module based on FCOS head and segmentation head to obtain the segmentation area of floating algae in each bounding box. The extensive experiment results show that the average precision of our AlgaeMask in the tasks of mask segmentation and box detection can reach 44.22% and 48.13%, respectively, which has 15.09% and 8.24% improvement over CenterMask. In addition, the AlgaeMask can meet the real-time requirements of floating algae detection.

Health risk assessment of As due to rice ingestion based on iAs distribution and actual consumption patterns for the residents in Beijing: a cross-sectional study - Suzhen Cao; Qi Cao; Kan Shao; Yijin Kang; Weigang Liang; Linlin Zhang; Juan Wang; Ning Qin; Xiaoli Duan (Environmental Geochemistry and Health, 2022)

Statin therapy protects against abdominal aortic aneurysms by inducing the accumulation of regulatory T cells in ApoE−/− mice - Linlin Meng; Yue Lu; Xinlu Wang; Wenhai Sui; Xiao Ge; Ming Zhong; Xiao Meng; Yun Zhang (Journal of Molecular Medicine, 2022)

Deep-Sea-Derived Fungi as Valuable Producers of Cytotoxic Secondary Metabolites and Their Leads Potential - Guangrong Zhao; Wenli Tang; Jianlong Zhang; Peimin Shi; Youzhi Li; Jiao Wang; Qingqin Shen; Haixia Si; Linlin Jiang; Xin Yu; Hongwei Zhu; Guozhong Chen; et al. (Frontiers in Marine Science, 2022)
Cancer is the leading lethal disease worldwide. Natural products have contributed significantly to the development of approved therapeutic agents. Therefore, research into new bioactive naturally sourced metabolites with lead potential is urgently needed. It is well-known that marine microorganisms are by far one of the most notable and prolific sources of bioactive natural products. Among them, deep-sea-derived fungi are extraordinarily adapted and metabolically active under extreme environmental conditions, which enable them to produce a large number of novel secondary metabolites. Chemical examination of deep-sea-derived fungi has yielded enormous amounts of cytotoxic natural products and potential drug leads. This review summarizes a total of 229 cytotoxic compounds isolated from deep-sea-derived fungi from 2010 to 2021. The emphasis is on the unique chemical diversity of these metabolic products, together with their relevant cytotoxic properties. Among the isolated metabolites, 82 compounds have been found to possess moderate to potent cytotoxic activities. Meanwhile, we also highlight some compounds with potent cytotoxicities (namely “star molecules”) considering their high drug lead potential. This review reveals deep-sea-derived fungi as considerable resources for the development of new drugs and the potential of the newly discovered secondary metabolites as valuable antitumor lead compounds.

Chromosomal Assembly of the Hexagrammos agrammus Genome via Third-Generation DNA Sequencing and Hi-C Technology - Linlin Zhao; Shenghao Liu; Shouqiang Wang; Tianyan Yang; Qi Liu; Tianxiang Gao (Frontiers in Marine Science, 2022)

Genomic analysis of a recombinant coxsackievirus A19 identified in Xinxiang, China, in 2019 - Liang Yi; Li Zhang; Linlin Feng; Xubo Luan; Qian Zhao; Pengwei Xu; Yinbiao Wang; Ling Tao; Weidong Wu (Archives of Virology, 2022)

Correction to: Circular RNA hsa_circ_0000034 accelerates retinoblastoma advancement through the miR-361-3p/ADAM19 axis - Yanhua Jiang; Fan Xiao; Lin Wang; Ting Wang; Linlin Chen (Molecular and Cellular Biochemistry, 2022)

Effectiveness of Selenium on Chondrocyte Glycoprotein Glycosylation Which Play Important Roles in the Pathogenesis of an Endemic Osteoarthritis, Kashin–Beck Disease - Sen Wang; Lingling Geng; Guanghui Zhao; Peilin Meng; Linlin Yuan; Xiong Guo (Biological Trace Element Research, 2022)

Lower activity time constraint on the ore-controlling Erdaogou fault in the Qingchengzi orefield of the Liaodong Peninsula, NE China - Yan Zhao; Yuewen Feng; Peng Zhang; Linlin Kou; Zhongzhu Yang; Shenghui Li; Wei Wang (Acta Geochimica, 2022)

Two Flavors of Intraseasonal Variability and Their Dynamics in the North Equatorial Current/Undercurrent Region - Zhenxiao Wang; Linlin Zhang; Yuchao Hui; Fan Wang; Dunxin Hu (Frontiers in Marine Science, 2022)
Significant surface-intensified and subsurface-intensified intraseasonal variability (ISV) of the North Equatorial Current/Undercurrent with different periods are detected to coexist with mooring ADCP measurements at 13°N, 130°E. The ISV of the currents in the upper 200 m has a relatively shorter period of 45 days, while the period of the subsurface-intensified ISV between 400 and 800 m is around 85 days. By combining with sea surface height measurements from satellite altimeters and outputs from an eddy-resolving ocean general circulation model, the origin and dynamic mechanism of the two flavors of ISV are investigated. Eddy trajectory tracking and energy analysis indicate that both the surface-intensified and subsurface-intensified ISV are related to locally generated meso-scale eddies near the mooring sites. Stability analysis suggests the surface-intensified ISV is related to the baroclinic instability induced by the vertical velocity shear of the North Equatorial Current. While the generation of the subsurface-intensified ISV is more complex and is partly related to the enhanced barotropic instability induced by the intensified horizontal shear of the subsurface zonal background flow.

Bak interacts with AKT and is involved in TNFα/CHX-induced apoptosis - Jiayue Song; Fuqiang Zhang; Yu Wang; Yuxiang Wang; Jingtian Zhang; Zixuan Xiao; Xueqi Fu; Xuemin Xu; Linlin Zeng (Molecular and Cellular Biochemistry, 2022)

The lag effect of 24-year tobacco consumption on lung cancer mortality in Henan Province, China, 1992 to 2016 - Linlin Li; Jie Lu; Xin Dai; Li Ma; Chongjian Wang; Liyun Feng (Environmental Science and Pollution Research, 2022)

Katabatic Flow Structures Indicative of the Flux Dissimilarity for Stable Stratification - Xiaofeng Guo; Wei Yang; Zhiqiu Gao; Linlin Wang; Jinkyu Hong; Baohong Ding; Long Zhao; Degang Zhou; Kun Yang (Boundary-Layer Meteorology, 2022)

Full-Length Transcriptome of the Whale Shark (Rhincodon typus) Facilitates the Genome Information - Fangrui Lou; Li Wang; Zhiyang Wang; Lei Wang; Linlin Zhao; Qingjie Zhou; Zhichuang Lu; Yongzheng Tang (Frontiers in Marine Science, 2022)
Rhincodon typus is a keystone and indicator species in marine ecosystems. Meanwhile, R. typus has been listed on the IUCN red list of vulnerable species. Here we used ONT platform to determine the full-length (FL) transcriptome of R. typus and obtained 14,930 FL transcripts. Among all FL transcripts, 14,915 transcripts were covered 11,892 genetic loci and 1,642 novel genetic loci were further found. Meanwhile, we identified 714 novel transcripts by compared FL transcripts with the R. typus genome. Based on FL transcripts, we also predicted the distribution patterns of ASs, LncRNAs, polyAs, CDSs and methylation sites on FL transcriptome of R. typus . Furthermore, a total of 31,021 (97.86%) CDSs can obtained annotation information. Overall, our work firstly provided the FL transcriptome and these sequences complete the annotated R. typus genome information. Furthermore, these information are a potential resource to study biological processes of R. typus .

Genetic background and cis-organization regulate ALDH7B4 gene expression in Eutrema salsugineum: a promoter analysis case study - Quancan Hou; Tianye Zhang; Wei Zhao; Linlin Wang; Lu Lu; Yuchen Qi; Dorothea Bartels (Planta, 2022)

Correction to: Wnt/β-catenin signaling pathway in severe preeclampsia - Xiaofang Wang; Zhan Zhang; Xianxu Zeng; Jinming Wang; Linlin Zhang; ·Wanyu Song; Ying Shi (Journal of Molecular Histology, 2022)

Characterizing the Semi-Volatile Organic Compounds in Runoff from Roads and Other Impervious Surfaces in a Suburban Area of Beijing - Liang Zhang; Haiyan Li; Youshu Wang; Zhichao Yang; Ziyang Zhang; Fei Liu; Linlin Tong; Ying Wang; Yongwei Gong; Hua Yang (Archives of Environmental Contamination and Toxicology, 2022)

Thermo-poroelastic modelling of cement sheath: pore pressure response, thermal effect and thermo-osmotic effect - Zihua Niu; Jiyun Shen; Linlin Wang; Rongwei Yang (European Journal of Environmental and Civil Engineering, 2022)

Taxonomy and regeneration of a newly recorded Polychaete Capitella teleta (Annelida, Capitellidae) in the coastal water of Shandong, China - Qian Li; Yongnan Li; Yue Wang; Xuwen Wu; Linlin Zhang (Journal of Oceanology and Limnology, 2022)

Save reservoirs of humid subtropical cities from eutrophication threat - Meijie Liu; Xiaoyu Lei; Yanyan Zhou; Jingsi Gao; Yun Zhou; Linlin Wang; Jia Zhu; Xian-zhong Mao (Environmental Science and Pollution Research, 2022)

Isocitrate dehydrogenase of Bacillus cereus is involved in biofilm formation - Linlin Zhao; Qing Liu; Qiubin Huang; Fengying Liu; Huiping Liu; Gang Wang (World Journal of Microbiology and Biotechnology, 2021)

Different Changing Patterns of Three NOS–NO System Activities after Ischemia–Reperfusion in Rabbit with AMI - Jun Zhang; Chao Chen; Fengpeng Li; Guangren Gao; Jinguo Fu; Heping Niu; Kai Yu; Lei Wang; Run Guo; Yanfang Wan; Zhanfeng Ma; Qianyu Zhang; et al. (Cell Biochemistry and Biophysics, 2021)

Warming reshaped the microbial hierarchical interactions - Yuqi Zhou; Baoyu Sun; Baohua Xie; Kai Feng; Zhaojing Zhang; Zheng Zhang; Shuzhen Li; Xiongfeng Du; Qi Zhang; Songsong Gu; Wen Song; Linlin Wang; et al. (Global Change Biology, 2021)
Global warming may alter microbially mediated ecosystem functions through reshaping of microbial diversity and modified microbial interactions. Here, we examined the effects of 5‐year experimental warming on different microbial hierarchical groups in a coastal nontidal soil ecosystem, including prokaryotes (i.e., bacteria and archaea), fungi, and Cercozoa, which is a widespread phylum of protists. Warming significantly altered the diversity and structure of prokaryotic and fungal communities in soil and additionally decreased the complexity of the prokaryotic network and fragmented the cercozoan network. By using the Inter‐Domain Ecological Network approach, the cross‐trophic interactions among prokaryotes, fungi, and Cercozoa were further investigated. Under warming, cercozoan–prokaryotic and fungal–prokaryotic bipartite networks were simplified, whereas the cercozoan–fungal network became slightly more complex. Despite simplification of the fungal–prokaryotic network, the strengthened synergistic interactions between saprotrophic fungi and certain prokaryotic groups, such as the Bacteroidetes, retained these phyla within the network under warming. In addition, the interactions within the fungal community were quite stable under warming conditions, which stabilized the interactions between fungi and prokaryotes or protists. Additionally, we found the microbial hierarchical interactions were affected by environmental stress (i.e., salinity and pH) and soil nutrients. Interestingly, the relevant microbial groups could respond to different soil properties under ambient conditions, whereas under warming these two groups tended to respond to similar soil properties, suggesting network hub species responded to certain environmental changes related to warming, and then transferred this response to their partners through trophic interactions. Finally, warming strengthened the network modules’ negative association with soil organic matters through some fungal hub species, which might trigger soil carbon loss in this ecosystem. Our study provides new insights into the response and feedback of microbial hierarchical interactions under warming scenario.

Influence of Initial Stress and Deformation States on the Shear Creep Behavior of Rock Discontinuities with Different Joint Roughness Coefficients - Zhen Wang; Linlin Gu; Qingzhao Zhang; Bo-An Jang (Rock Mechanics and Rock Engineering, 2021)

Experimental and numerical investigation on the influence of PC window beam on the seismic performance of PC shear wall structures - Linlin Xie; Xun Chong; Lanfang Zhang; Xianguo Ye; Qing Jiang; Decai Wang (European Journal of Environmental and Civil Engineering, 2021)

Characteristics of Plastic Pollution in the Environment: A Review - Penghui Li; Xiaodan Wang; Min Su; Xiaoyan Zou; Linlin Duan; Hongwu Zhang (Bulletin of Environmental Contamination and Toxicology, 2021)

Decoupling between Oxygen and Radiogenic Isotopes: Evidence for Generation of Juvenile Continental Crust by Partial Melting of Subducted Oceanic Crust - Xuan-Ce Wang; Qiuli Li; Simon A. Wilde; Zheng-Xiang Li; Chaofeng Li; Kai Lei; Shao-Jie Li; Linlin Li; Manoj K. Pandit (Journal of Earth Science, 2021)

A leucoanthocyanidin dioxygenase gene (RtLDOX2) from the feral forage plant Reaumuria trigyna promotes the accumulation of flavonoids and improves tolerance to abiotic stresses - Ningning Li; Xue Wang; Binjie Ma; Zhigang Wu; Linlin Zheng; Zhi Qi; Yingchun Wang (Journal of Plant Research, 2021)

Dynamic monitoring of a super high-rise structure based on GNSS-RTK technique combining CEEMDAN and wavelet threshold analysis - Chunbao Xiong; Yanbo Niu; Zhilin Wang; Linlin Yuan (European Journal of Environmental and Civil Engineering, 2021)

Phylogenomics Based on Transcriptome Data Provides Evidence for the Internal Phylogenetic Relationships and Potential Terrestrial Evolutionary Genes of Lungfish - Linlin Zhao; Shouqiang Wang; Fangrui Lou; Tianxiang Gao; Zhiqiang Han (Frontiers in Marine Science, 2021)
The evolutionary relationships of lungfish can provide crucial information on the transition from Sarcopterygii to tetrapods. Phylogenomics is necessary to explore accurate internal phylogenetic relationships among all lungfish species. In the context of the lack of genome-wide genetic information for Protopterus amphibious , we are the first to systematically report the transcriptome of P. amphibius and these sequences can be used to enrich the genome-wide genetic information of lungfish. Meanwhile, we also found significant differences in the expression levels of 3,189 genes between the lung and heart of P. amphibious . Based on phylogenomics, 1,094 shared orthologous genes were identified and then applied to reconstruct the internal phylogenetic structure of lungfish species. The reconstructed phylogenetic relationships provide evidence that lungfish is the sister group of terrestrial vertebrates and that Neoceratodus forsteri is the most primitive lungfish. Moreover, the divergence time between the most primitive lungfish and other lungfish species is between 186.11 and 195.36 MYA. Finally, 43 protein metabolism-related, stress response-related, and skeletogenesis-related genes were found to have undergone positive selection and fast evolution in N. forsteri . We suspected that these genes possibly helped ancient fish adapt to the new terrestrial environment and ultimately contributed to its spreading to land.

High-frequency in vitro plantlet regeneration in Lilium davidii var. unicolour Salisb, an important edible and medicinal plant, and confirmation of genetic fidelity of regeneration plantlets using ISSR markers - Linlin Yang; Liqin Chao; Xiuhong Su; Chunyan Wang; Chengming Dong; Suiqing Chen (Plant Biotechnology Reports, 2021)

Effects of sodium arsenite and dimethyl arsenic acid on Liaoning cashmere goat skin fibroblasts - Fengqin Zhao; Chuang Wang; Dongyu Sun; Linlin Zhang; Zhiyue Wang; Jun Piao; Jingai Piao; Mei Jin (Environmental Science and Pollution Research, 2021)

Biochar Derived from Treated Lotus Stem and Adsorption of Phthalic Acid Esters - Ruiling Zhang; Linlin Chen; Binbin Qiu; Xiaojing Sun; Songyan Qin; Bo Wang; Feiyue Li; Lixin Zhao; Zhe Zhu (Water, Air, & Soil Pollution, 2021)

Constitutive activation of β-catenin in odontoblasts induces aberrant pulp calcification in mouse incisors - Shijian Deng; Linlin Fan; Yunfei Wang; Qi Zhang (Journal of Molecular Histology, 2021)

A Role for Transmembrane Protein 16C/Slack Impairment in Excitatory Nociceptive Synaptic Plasticity in the Pathogenesis of Remifentanil-induced Hyperalgesia in Rats - Yize Li; Linlin Zhang; Jing Li; Chunyan Wang; Yi Chen; Yuan Yuan; Keliang Xie; Guolin Wang; Yonghao Yu (Neuroscience Bulletin, 2021)

Spring phenology outweighed climate change in determining autumn phenology on the Tibetan Plateau - Jie Peng; Chaoyang Wu; Xiaoyue Wang; Linlin Lu (International Journal of Climatology, 2021)
As the third pole of the Earth, the Tibetan Plateau (TP) is highly sensitive to climate change. Phenological changes in spring (i.e., the start of the growing season, SOS) over the TP are of much debate, while our understanding on the variation of autumn phenology (i.e., the end of the growing season, EOS) is still lacking. Given the significance of tracing the latest variation of EOS induced by the ongoing global change, we used the currently longest time series (1982–2018) of the normalized difference vegetation index of the Long Term Data Record from the Advanced Very High Resolution Radiometer (AVHRR LTDR NDVI) and investigated the responses of EOS to biological and climatic factors. We found that the EOS showed an insignificantly delayed trend at an average rate of 0.14 days·decade −1 on the TP. This variation was found for all vegetation types except for alpine sparse vegetation. We further showed that spring SOS had the largest contribution to the interannual variations in EOS, where 46.5% of the vegetated areas showed significantly positive correlations between SOS and EOS ( p

Effect of divalent manganese (Mn2+) concentration on the growth and nitrate nitrogen content of lettuce during aeroponic intercropping with cherry radish - Lei Zhang; Linlin Wang; Faqinwei Li; Fei Xiao; Haiye Yu (Horticulture, Environment, and Biotechnology, 2021)

Development of the CSOMIO Coupled Ocean-Oil-Sediment- Biology Model - Dmitry S. Dukhovskoy; Steven L. Morey; Eric P. Chassignet; Xu Chen; Victoria J. Coles; Linlin Cui; Courtney K. Harris; Robert Hetland; Tian-Jian Hsu; Andrew J. Manning; Michael Stukel; Kristen Thyng; et al. (Frontiers in Marine Science, 2021)
The fate and dispersal of oil in the ocean is dependent upon ocean dynamics, as well as transformations resulting from the interaction with the microbial community and suspended particles. These interaction processes are parameterized in many models limiting their ability to accurately simulate the fate and dispersal of oil for subsurface oil spill events. This paper presents a coupled ocean-oil-biology-sediment modeling system developed by the Consortium for Simulation of Oil-Microbial Interactions in the Ocean (CSOMIO) project. A key objective of the CSOMIO project was to develop and evaluate a modeling framework for simulating oil in the marine environment, including its interaction with microbial food webs and sediments. The modeling system developed is based on the Coupled Ocean-Atmosphere-Wave-Sediment Transport model (COAWST). Central to CSOMIO’s coupled modeling system is an oil plume model coupled to the hydrodynamic model (Regional Ocean Modeling System, ROMS). The oil plume model is based on a Lagrangian approach that describes the oil plume dynamics including advection and diffusion of individual Lagrangian elements, each representing a cluster of oil droplets. The chemical composition of oil is described in terms of three classes of compounds: saturates, aromatics, and heavy oil (resins and asphaltenes). The oil plume model simulates the rise of oil droplets based on ambient ocean flow and density fields, as well as the density and size of the oil droplets. The oil model also includes surface evaporation and surface wind drift. A novel component of the CSOMIO model is two-way Lagrangian-Eulerian mapping of the oil characteristics. This mapping is necessary for implementing interactions between the ocean-oil module and the Eulerian sediment and biogeochemical modules. The sediment module is a modification of the Community Sediment Transport Modeling System. The module simulates formation of oil-particle aggregates in the water column. The biogeochemical module simulates microbial communities adapted to the local environment and to elevated concentrations of oil components in the water column. The sediment and biogeochemical modules both reduce water column oil components. This paper provides an overview of the CSOMIO coupled modeling system components and demonstrates the capabilities of the modeling system in the test experiments.

Comparison of Class 2 Integron Integrase Activities - Xiaotong Wang; Nana Kong; Mei Cao; Long Zhang; Muzhen Sun; Linlin Xiao; Gang Li; Quhao Wei (Current Microbiology, 2021)

Biomechanical Regulation of Stem Cell Fate - Linlin Jin; Ping Wang; Fang Ni (Current Stem Cell Reports, 2021)

IL-21 enhances STAT3/Blimp-1 signaling pathway in B cells and contributes to plasma cell differentiation in newly diagnosed patients with myasthenia gravis - Yanan Xu; Xiaoyu Huang; Fengzhan Li; Tan Liu; Tingting Yang; Fei Chen; Jie Zhu; Meng Pan; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; et al. (Immunologic Research, 2021)

Utilization of serum procalcitonin as a biomarker in the diagnosis and treatment of children with bacterial hospital-acquired pneumonia - Wenlong Wang; Yitang Zhu; Linlin Yin; Yaoyao Deng; Guoxian Chu; Supin Liu (Molecular and Cellular Biochemistry, 2021)

Circular RNA has_circ_0000034 accelerates retinoblastoma advancement through the miR-361-3p/ADAM19 axis - Yanhua Jiang; Fan Xiao; Lin Wang; Ting Wang; Linlin Chen (Molecular and Cellular Biochemistry, 2021)

Seasonal variation of net ecosystem CO2 exchange and its influencing factors in an apple orchard in the Loess Plateau - Jianfeng Yang; Yumin Duan; Linlin Wang; Dan Kang; Mukesh Kumar Awasthi; Huike Li; Linsen Zhang (Environmental Science and Pollution Research, 2020)

Quantitative assessment on soil concentration of heavy metal–contaminated soil with various sample pretreatment techniques and detection methods - Fei Pan; Yong Yu; Lei Yu; Hailan Lin; Yeyao Wang; Linlin Zhang; Dawei Pan; Rilong Zhu (Environmental Monitoring and Assessment, 2020)

Analysis and prediction of land subsidence along significant linear engineering - Pengpeng Ding; Chao Jia; Shengtong Di; Linlin Wang; Chao Bian; Xiao Yang (Bulletin of Engineering Geology and the Environment, 2020)

Three dimensional convolutional neural network-based classification of conduct disorder with structural MRI - Jianing Zhang; Xuechen Li; Yuexiang Li; Mingyu Wang; Bingsheng Huang; Shuqiao Yao; Linlin Shen (Brain Imaging and Behavior, 2020)

Do Supercontinent-Superplume Cycles Control the Growth and Evolution of Continental Crust? - Xuan-Ce Wang; Simon A. Wilde; Zheng-Xiang Li; Shaojie Li; Linlin Li (Journal of Earth Science, 2020)

Somatic mutations in planar cell polarity genes in neural tissue from human fetuses with neural tube defects - Tian Tian; Yunping Lei; Yongyan Chen; Menuka Karki; Lei Jin; Richard H. Finnell; Linlin Wang; Aiguo Ren (Human Genetics, 2020)

The immune response to a recombinant Lactococcus lactis oral vaccine against foot-and-mouth disease virus in mice - Xinsheng Liu; Linlin Qi; Jianliang Lv; Zhongwang Zhang; Peng Zhou; Zhongyuan Ma; Yonglu Wang; Yongguang Zhang; Li Pan (Biotechnology Letters, 2020)

A benchmark city for seismic resilience assessment - Qingxue Shang; Xiaodong Guo; Quanwang Li; Zhen Xu; Linlin Xie; Chaofeng Liu; Jichao Li; Tao Wang (Earthquake Engineering and Engineering Vibration, 2020)

Instability in boundary layer between the North Equatorial Current and underlying zonal jets based on mooring observations - Fujun Wang; Junqiao Feng; Qingye Wang; Linlin Zhang; Shijian Hu; Dunxin Hu (Journal of Oceanology and Limnology, 2020)

Revisiting the Concentration Observations and Source Apportionment of Atmospheric Ammonia - Yuepeng Pan; Mengna Gu; Yuexin He; Dianming Wu; Chunyan Liu; Linlin Song; Shili Tian; Xuemei Lü; Yang Sun; Tao Song; Wendell W. Walters; Xuejun Liu; et al. (Advances in Atmospheric Sciences, 2020)

Adaptive feeding in the American oyster Crassostrea virginica : Complex impacts of pulsatile flow during pseudofecal ejection events - Linlin Wang; Junting Song; Hongsheng Bi; Matthew Gray; Chunlei Fan; Ming Liu; Xian‐Zhong Mao (Limnology and Oceanography, 2020)
Adaptive feeding is a strategy used by many organisms to maintain growth and reproduction success while encountering varying feeding conditions. Oysters are sessile benthic and non‐siphon filter feeders. Oysters are well adapted to modify the ambient microenvironment through their pumping behavior and particle selection activity. Rejection of unsuitable food particulates bound in pseudofeces via ejection events are an integral part of oyster feeding during which oysters produced strong flow opposite to their inhalant feeding flow. The strong opposite pulsatile flow during the ejection event inevitably disrupts the oyster's normal feeding cycle, but how oysters restart their feeding and allocate their energy consumption during an ejection event has not been investigated. The present study used particle image velocimetry (PIV) to examine the impact of ejection events on the feeding of the American oyster, Crassostrea virginica . The strong pulsatile flow resulting from pseudofecal ejection altered the external flow fields by moving water away from the shell. The initial feeding zone after pseudofecal ejection was relatively narrow, possessed a low pulsatile flow, and did not exploit the full flow field. The feeding zone gradually expanded as the pulsatile flow weakened. The strong shear rate at the stable feeding zone then sustained the feeding flow that facilitated oyster feeding. Furthermore, the volumetric fluxes often increased after the ejection event, suggesting increase in feeding efficiency after ejection events. These PIV studies provide new insight on the interactions between feeding oysters and the surrounding physical environment at small yet ecologically relevant scales.

Action of Akt Pathway on La-Induced Hippocampal Neuron Apoptosis of Rats in the Growth Stage - Jinting Wang; Tianwei Wu; Lan Ma; Ying Guo; Yali Huang; Linlin Zheng (Neurotoxicity Research, 2020)

Experimental investigation on the mechanical behaviour of a new superimposed RC exterior basement wall with socket base - Xun Chong; Linlin Xie; Xianguo Ye; Qing Jiang; Decai Wang (European Journal of Environmental and Civil Engineering, 2020)

Review on observational studies of western tropical Pacific Ocean circulation and climate - Dunxin Hu; Fan Wang; Janet Sprintall; Lixin Wu; Stephen Riser; Sophie Cravatte; Arnold Gordon; Linlin Zhang; Dake Chen; Hui Zhou; Kentaro Ando; Jianing Wang; et al. (Journal of Oceanology and Limnology, 2020)

Dynamic features of near-inertial oscillations in the Northwestern Pacific derived from mooring observations from 2015 to 2018 - Shijian Hu; Lingling Liu; Cong Guan; Linlin Zhang; Jianing Wang; Qingye Wang; Jie Ma; Fujun Wang; Fan Jia; Junqiao Feng; Xi Lu; Fan Wang; et al. (Journal of Oceanology and Limnology, 2020)

An Improved Coal Permeability Model with Variable Cleat Width and Klinkenberg Coefficient - Gang Wang; Zhiyong Xiao; Junhong Yu; Lu Zhang; Linlin Sun (Geotechnical and Geological Engineering, 2020)

Quality by Design–Based Assessment for Analytical Similarity of Adalimumab Biosimilar HLX03 to Humira® - Erhui Zhang; Liqi Xie; Peilan Qin; Lihong Lu; Yanpeng Xu; Wenyuan Gao; Linlin Wang; Michael Hongwei Xie; Weidong Jiang; Scott Liu (The AAPS Journal, 2020)
Quality by design (QbD) is an efficient but challenging approach for the development of biosimilar due to the complex relationship among process, quality, and efficacy. Here, the analytical similarity of adalimumab biosimilar HLX03 to Humira® was successfully established following a QbD quality study. Quality target product profile (QTPP) of HLX03 was first generated according to the public available information and initial characterization of 3 batches of Humira®. The critical quality attributes (CQAs) were then identified through risk assessment according to impact of each quality attribute on efficacy and safety. The anticipated range for each CQA was derived from similarity acceptance range and/or the corresponding regulatory guidelines. Finally, a panel of advanced and orthogonal physicochemical and functional tests and comparison of 6 batches of HLX03 and 10 batches of the reference standard demonstrated high similarity of HLX03 to Humira®, except for slightly lower percentage of high mannosylated glycans (%HM) in HLX03 which had no effect on FcγRIII binding and antibody-dependent cell-mediated cytotoxicity (ADCC) activity in human peripheral blood mononuclear cell (PBMC). All above demonstrated the feasibility and efficiency of QbD-based similarity assessment of a biosimilar monoclonal antibody (mAb).

Creep characteristics and prediction of creep failure of rock discontinuities under shearing conditions - Zhen Wang; Linlin Gu; Qingzhao Zhang; Songlin Yue; Guokai Zhang (International Journal of Earth Sciences, 2020)

Variability of voriconazole concentrations in patients with hematopoietic stem cell transplantation and hematological malignancies: influence of loading dose, procalcitonin, and pregnane X receptor polymorphisms - Guangting Zeng; Linlin Wang; Lihong Shi; Huilan Li; Miaomiao Zhu; Jia Luo; Zanling Zhang (European Journal of Clinical Pharmacology, 2020)

Controlled synchronization of prolactin/STAT5 and AKT1/mTOR in bovine mammary epithelial cells - Baosheng Wang; Linlin Shi; Jingjing Men; Qingzhang Li; Xiaoming Hou; Chunmei Wang; Feng Zhao (In Vitro Cellular & Developmental Biology - Animal, 2020)

Cutibacterium acnes Type II strains are associated with acne in Chinese patients - Shuyang Zhao; Jiayu Ci; Jinhui Xue; Yaofeng Wang; Xuelong Li; Linlin Hao; Liu Tian; Haiyan Guo; Chengqi Xin; Yujie Zhao (Antonie van Leeuwenhoek, 2020)

Different chemical composition and storage mechanism of soil organic matter between active and permafrost layers on the Qinghai–Tibetan Plateau - Yinghui Wang; Yunping Xu; Dandan Wei; Linlin Shi; Zehua Jia; Yuanhe Yang (Journal of Soils and Sediments, 2020)

Low shear stress damages endothelial function through STAT1 in endothelial cells (ECs) - Linlin Zhu; Feng Wang; Hongfeng Yang; Junjie Zhang; Shaoliang Chen (Journal of Physiology and Biochemistry, 2020)

Interaction between CA repeat microsatellites and HIF1α regulated the transcriptional activity of porcine IGF1 promoter - Hongwei Geng; Linlin Hao; Yunyun Cheng; Chunli Wang; Shan Huang; Wenzhen Wei; Rui Yang; Haoyang Li; Songcai Liu; Hao Yu; Huayi Lu (Journal of Applied Genetics, 2020)

Physiological responses of yellow-horn seedlings to high temperatures under drought condition - Hua Jin; Jixiang Zou; Linlin Li; Xinlei Bai; Tong Zhu; Junbao Li; Bingcheng Xu; Zhi Wang (Plant Biotechnology Reports, 2020)

Four superoxide dismutases of Bacillus cereus 0–9 are non-redundant and perform different functions in diverse living conditions - Juanmei Zhang; Haodong Wang; Qiubin Huang; Ying Zhang; Linlin Zhao; Fengying Liu; Gang Wang (World Journal of Microbiology and Biotechnology, 2020)

Identification of Fusarium graminearum-responsive miRNAs and their targets in wheat by sRNA sequencing and degradome analysis - Xiaojie Jin; Linlin Jia; Yongxia Wang; Baoquan Li; Dongfa Sun; Xueyan Chen (Functional & Integrative Genomics, 2020)

Evaluation of Genomic Selection for Seven Economic Traits in Yellow Drum (Nibea albiflora) - Guijia Liu; Linsong Dong; Linlin Gu; Zhaofang Han; Wenjing Zhang; Ming Fang; Zhiyong Wang (Marine Biotechnology, 2019)
Yellow drum ( Nibea albiflora ) is an important maricultural fish in China, and genetic improvement is necessary for this species. This research evaluated the application of genomic selection methods to predict the genetic values of seven economic traits for yellow drum. Using genome-wide single-nucleotide polymorphisms (SNPs), we estimated the genetic parameters for seven traits, including body length (BL), swimming bladder index (SBI), swimming bladder weight (SBW), body thickness (BT), body height (BH), body length/body height ratio (LHR), and gonad weight index (GWI). The heritability estimates ranged from 0.309 to 0.843. We evaluated the prediction performance of various statistical methods, and no one method provided the highest predictive ability for all traits. We then evaluated and compared the use of genome-wide association study (GWAS)–informative SNPs and random SNPs for prediction and found that GWAS-informative SNPs obviously increased. It only needed 5 and 100 informative SNPs for LHR and BT to achieve almost the same predictive abilities as using genome-wide SNPs, and for BL, SBI, SBW, BH, and GWI, about 1000 to 3000 informative SNPs were needed to achieve whole-genome level predictive abilities. It can be concluded from the test results that breeders can use fewer SNPs to save the breeding costs of genomic selection for some traits.

Sulfate-enhanced degradation of Rhodamine B in the hydrogen peroxide/hydroxylamine system - Shengli Wang; Linlin Yan; Xiaohui Guan; Yanping Jia; Lianfa Song; Haifeng Zhang (Environmental Chemistry Letters, 2019)

Gelatin Methacrylate (GelMA)-Based Hydrogels for Cell Transplantation: an Effective Strategy for Tissue Engineering - Shining Xiao; Tengfei Zhao; Jingkai Wang; Chenggui Wang; Jiangnan Du; Liwei Ying; Jiangtao Lin; Caihua Zhang; Wanglu Hu; Linlin Wang; Kan Xu (Stem Cell Reviews and Reports, 2019)

Wheat methionine sulfoxide reductase A4.1 interacts with heme oxygenase 1 to enhance seedling tolerance to salinity or drought stress - Pengcheng Ding; Linlin Fang; Guangling Wang; Xiang Li; Shu Huang; Yankun Gao; Jiantang Zhu; Langtao Xiao; Jianhua Tong; Fanguo Chen; Guangmin Xia (Plant Molecular Biology, 2019)

Assessment of the effects of lethal and sublethal exposure to dinotefuran on the wheat aphid Rhopalosiphum padi (Linnaeus) - Denghui Deng; Wenbo Duan; Hao Wang; Kun Zhang; Jianglong Guo; Linlin Yuan; Likui Wang; Shaoying Wu (Ecotoxicology, 2019)

Spatiotemporal evolution of C3/C4 vegetation and its controlling factors in southern China since the last glacial maximum - Linlin Cui; Jianfang Hu; Xu Wang (Science China Earth Sciences, 2019)

Exploration of the key functional strains from an azo dye degradation microbial community by DGGE and high-throughput sequencing technology - Yan Chen; Lizhen Zhang; Linlin Feng; Guotao Chen; Yuanxiu Wang; Zhijun Zhai; Qinghua Zhang (Environmental Science and Pollution Research, 2019)

Effects of key species mud snail Bullacta exarata (Gastropoda) on oxygen and nutrient fluxes at the sediment-water interface in the Huanghe River Delta, China - Baoquan Li; Tjeerd J. Bouma; Quanchao Wang; Laura M. Soissons; Francesco Cozzoli; Guanghai Feng; Xiaojing Li; Zhengquan Zhou; Linlin Chen (Acta Oceanologica Sinica, 2019)

Diversity of the Fusarium pathogens associated with crown rot in the Huanghuai wheat‐growing region of China - Haifeng Zhou; Xiaolun He; Shuo Wang; Qingzhou Ma; Bingjian Sun; Shengli Ding; Linlin Chen; Meng Zhang; Honglian Li (Environmental Microbiology, 2019)
Summary To investigate the distribution and diversity of the pathogens associated with Fusarium crown rot in the Huanghuai wheat‐growing region (HHWGR) of China, we collected wheat samples with symptomatic stem bases from seven provinces in the HHWGR between 2013 and 2016. A total of 1196 isolates obtained from 222 locations were identified as 9 Fusarium species based on morphological and molecular identification. Of these pathogen species, F. pseudograminearum was the dominant species. Furthermore, F. sinensis was isolated from the disease specimens and tested for virulence to wheat. The result of the pathogenicity revealed that an intraspecific differentiation existed in F. pseudograminearum ; sequence analysis of the EF‐1α gene showed that 194 F. pseudograminearum isolates were differentiated into two distinct clades which closed to the strains from Australia and China respectively, but neither pathogenicity nor EF‐1α sequence was related to the geographic origins of these isolates. However, universal rice primers‐polymerase chain reaction showed a correlation with the geographical origins of the 194 isolates, which were divided into eight subclusters, the level of genetic diversity was higher within a geographical population than among the different populations. The results of these analyses can be directly used to facilitate disease monitoring and development of control strategies.

Geochemical characteristics of dust aerosol availability in northwestern China - Xunming Wang; Jimin Sun; Mingrui Qiang; Caixia Zhang; Danfeng Li; Ting Hua; Hui Li; Lili Lang; Linlin Jiao; Diwen Cai; Wenyong Ma (Arabian Journal of Geosciences, 2019)

Luteolin decreases the yield of influenza A virus in vitro by interfering with the coat protein I complex expression - Haiyan Yan; Linlin Ma; Huiqiang Wang; Shuo Wu; Hua Huang; Zhengyi Gu; Jiandong Jiang; Yuhuan Li (Journal of Natural Medicines, 2019)

Expression analysis of And4 during fin regeneration in Misgurnus anguillicaudatus provides insights into its function - Li Li; Qian Xiao; Linlin Wang; Zhongjie Chang (Fish Physiology and Biochemistry, 2019)

Major ion and dissolved heavy metal geochemistry, distribution, and relationship in the overlying water of Dongting Lake, China - Yan Chen; Lingqing Wang; Tao Liang; Jun Xiao; Jing Li; Haicheng Wei; Linlin Dong (Environmental Geochemistry and Health, 2019)

Classification and characterization of bound water in marine mucky silty clay - Shuo Li; Changming Wang; Xianwei Zhang; Linlin Zou; Zhenxue Dai (Journal of Soils and Sediments, 2019)

A miR-511-binding site SNP in the 3′UTR of IGF-1 gene is associated with proliferation and apoptosis of PK-15 cells - Wenzhen Wei; Gang Wang; Yunyun Cheng; Rui Yang; Jie Song; Shan Huang; Haoyang Li; Hongwei Geng; Hao Yu; Songcai Liu; Linlin Hao (In Vitro Cellular & Developmental Biology - Animal, 2019)

A study of the coupled bioelectrochemical system-upflow anaerobic sludge blanket for efficient transformation of 2,4-dichloronitrobenzene - Hui Chen; Donghui Lu; Linlin Chen; Caiqin Wang; Xiangyang Xu; Liang Zhu (Environmental Science and Pollution Research, 2019)

Sodium Fluoride (NaF) Induces Inflammatory Responses Via Activating MAPKs/NF-κB Signaling Pathway and Reducing Anti-inflammatory Cytokine Expression in the Mouse Liver - Linlin Chen; Ping Kuang; Huan Liu; Qin Wei; Hengmin Cui; Jing Fang; Zhicai Zuo; Junliang Deng; Yinglun Li; Xun Wang; Ling Zhao (Biological Trace Element Research, 2019)

Coseismic deformation and source model of the 12 November 2017 M W 7.3 Kermanshah Earthquake (Iran–Iraq border) investigated through DInSAR measurements - Jianming Kuang; Linlin Ge; Graciela Isabel Metternicht; Alex Hay-Man Ng; Hua Wang; Mehdi Zare; Farnaz Kamranzad (International Journal of Remote Sensing, 2019)

Heat Transfer in Sandstones at Low Temperature - Zhiqiang Liu; Linlin Wang; Bo Zhao; Jingyi Leng; Guangqing Zhang; Diansen Yang (Rock Mechanics and Rock Engineering, 2019)

Ascorbic acid induces cardiac differentiation of white adipose tissue-derived stem cells - Wenhui Liu; Huan Liu; Yinghui Wang; Linlin Zhang; Chunhui Wang; Haifang Li (Molecular and Cellular Biochemistry, 2019)

Development of genome-wide SNPs for population genetics of Collichthys lucidus - Linlin Zhao; Meijie Jiang; Fangyuan Qu; Dan Yi; Shouqiang Wang; Zhaohui Zhang (Conservation Genetics Resources, 2018)

Spirillospora tritici sp. nov., a Novel Actinomycete Isolated from Rhizosphere Soil of Triticum aestivum L. - Jing Song; Jiabin Wang; Tianyu Sun; Chuang Li; Hairong He; Linlin Shi; Xiaowei Guo; Junwei Zhao; Wensheng Xiang (Current Microbiology, 2018)

Constitutive activation of β-catenin in ameloblasts leads to incisor enamel hypomineralization - Linlin Fan; Shijian Deng; Xin Sui; Mengmeng Liu; Shuhua Cheng; Yunfei Wang; Yuguang Gao; Chun-Hung Chu; Qi Zhang (Journal of Molecular Histology, 2018)

Tissue Distribution and Gender-Specific Protein Expression of Cytochrome P450 in five Mouse Genotypes with a Background of FVB - Jiamei M. Chen; Qisong S. Zhang; Xiaoyan Y. Li; Xia Gong; Yanjiao J. Ruan; Sijing J. Zeng; Linlin L. Lu; Xiaoxiao X. Qi; Ying Wang; Ming Hu; Lijun J. Zhu; Zhongqiu Q. Liu (Pharmaceutical Research, 2018)

Prevalence and trend of isolated and complicated congenital hydrocephalus and preventive effect of folic acid in northern China, 2005–2015 - Jufen Liu; Lei Jin; Zhiwen Li; Yali Zhang; Le Zhang; Linlin Wang; Aiguo Ren (Metabolic Brain Disease, 2018)

The impact of urbanization on wind speed and surface aerodynamic characteristics in Beijing during 1991–2011 - Junkai Liu; Zhiqiu Gao; Linlin Wang; Yubin Li; Chloe Y. Gao (Meteorology and Atmospheric Physics, 2018)

Osteoprotegerin deficiency causes morphological and quantitative damage in epithelial rests of Malassez - Yunfei Wang; Mengmeng Liu; Shijian Deng; Xin Sui; Linlin Fan; Qi Zhang (Journal of Molecular Histology, 2018)

Wnt/β-catenin signaling pathway in severe preeclampsia - Xiaofang Wang; Zhan Zhang; Xianxu Zeng; Jinming Wang; Linlin Zhang; Wanyu Song; Ying Shi (Journal of Molecular Histology, 2018)

The potential effects of aeolian processes on the vegetation in a semiarid area: geochemical evidence from plants and soils - Junpeng Lou; Xunming Wang; Bingqi Zhu; Danfeng Li; Linlin Jiao; Wenyong Ma; Diwen Cai (Arabian Journal of Geosciences, 2018)

Size distribution of individuals in the population of Asterias amurensis (Echinodermata: Asteroidea) and its reproductive cycle in China - Baoquan Li; Zhengquan Zhou; Bingjun Li; Quanchao Wang; Xiaojing Li; Linlin Chen (Acta Oceanologica Sinica, 2018)

Adsorptive removal of organics from aqueous phase by acid-activated coal fly ash: preparation, adsorption, and Fenton regenerative valorization of “spent” adsorbent - Nannan Wang; Linlin Hao; Jiaqing Chen; Qiang Zhao; Han Xu (Environmental Science and Pollution Research, 2018)

Labile organic carbon fractions and carbon pool management index in a 3-year field study with biochar amendment - Xu Yang; Di Wang; Yu Lan; Jun Meng; Linlin Jiang; Qiang Sun; Dianyun Cao; Yuanyuan Sun; Wenfu Chen (Journal of Soils and Sediments, 2018)

The decreased expression of Stat3 and p-Stat3 in preeclampsia-like rat placenta - Zhan Zhang; Xiaofang Wang; Jinming Wang; Linlin Zhang (Journal of Molecular Histology, 2018)

The role of Ustilaginoidea virens sclerotia in increasing incidence of rice false smut disease in the subtropical zone in China - Mingli Yong; Qide Deng; Linlin Fan; Jiankun Miao; Chaohui Lai; Hongming Chen; Xiujuan Yang; Shu Wang; Furu Chen; Li Jin; Binghui Yang; Yuanjun Bai; et al. (European Journal of Plant Pathology, 2018)

Time-Dependent Lactate Production and Amino Acid Utilization in Cultured Astrocytes Under High Glucose Exposure - Dan Wang; Liangcai Zhao; Hong Zheng; Minjian Dong; Linlin Pan; Xi Zhang; Huajie Zhang; Hongchang Gao (Molecular Neurobiology, 2018)

An integrated approach for water scarcity evaluation—a case study of Yunnan, China - Hongrui Wang; Linlin Fan; Yuan Liang; Cheng Wang (Environment, Development and Sustainability, 2018)

Influence of polymeric carrier on the disposition and retention of 20(R)-ginsenoside-rg3-loaded swellable microparticles in the lung - Xiuhua Wang; Xiao Zhang; Linlin Fan; Huan He; Xiaofei Zhang; Yuyang Zhang; Shirui Mao (Drug Delivery and Translational Research, 2018)

Plantactinospora solaniradicis sp. nov., a novel actinomycete isolated from the root of a tomato plant (Solanum lycopersicum L.) - Wenchao Li; Xiaowei Guo; Linlin Shi; Junwei Zhao; Liangliang Yan; Xiaotong Zhong; Chen Zhang; Yufei Chen; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2018)

MicroRNA-192 regulates hypertrophic scar fibrosis by targeting SIP1 - Yan Li; Julei Zhang; Wei Zhang; Yang Liu; Yuehua Li; Kejia Wang; Yijie Zhang; Chen Yang; Xiaoqiang Li; Jihong Shi; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

The vertical structure and variability of the western boundary currents east of the Philippines: case study from in situ observations from December 2010 to August 2014 - Fujun Wang; Linlin Zhang; Dunxin Hu; Qingye Wang; Fangguo Zhai; Shijian Hu (Journal of Oceanography, 2017)

MiR-125a regulates mitochondrial homeostasis through targeting mitofusin 1 to control hypoxic pulmonary vascular remodeling - Cui Ma; Chen Zhang; Mingfei Ma; Lixin Zhang; Linlin Zhang; Fengying Zhang; Yingli Chen; Fangyuan Cao; Minghui Li; Guangtian Wang; Tingting Shen; Hongmin Yao; et al. (Journal of Molecular Medicine, 2017)

The analgesic effect of trans-resveratrol is regulated by calcium channels in the hippocampus of mice - Weijie Wang; Yingcong Yu; Jing Li; Lin Wang; Zhi Li; Chong Zhang; Linlin Zhen; Lianshu Ding; Gang Wang; Xiaoyang Sun; Ying Xu (Metabolic Brain Disease, 2017)

Settlement mechanism of piled-raft foundation due to cyclic train loads and its countermeasure - Linlin Gu; Guanlin Ye; Zhen Wang; Xianzhang Ling; Feng Zhang (Earthquake Engineering and Engineering Vibration, 2017)

Staphylococcus enterotoxin profile of China isolates and the superantigenicity of some novel enterotoxins - Menglu Shen; Yi Li; Linlin Zhang; Songbao Dai; Jiashun Wang; Yongqing Li; Lei Zhang; Jinhai Huang (Archives of Microbiology, 2017)

Occurrence of diazepam and its metabolites in wastewater and surface waters in Beijing - Congcong Wang; Linlin Hou; Jing Li; Zeqiong Xu; Tingting Gao; Jun Yang; Huafang Zhang; Xiqing Li; Peng Du (Environmental Science and Pollution Research, 2017)

The death of the circulatory system diseases in China: provincial socioeconomic and environmental perspective - Haixia Pu; Jiatian Li; Pin Wang; Linlin Cui; Huaxin Wang (Environmental Science and Pollution Research, 2017)

A Selenium-Enriched Ziyang Green Tea Polysaccharide Induces Bax-Dependent Mitochondrial Apoptosis and Inhibits TGF-β1-Stimulated Collagen Expression in Human Keloid Fibroblasts via NG2 Inactivation - Lele Lu; Linlin Chai; Wenping Wang; Xi Yuan; Shirong Li; Chuan Cao (Biological Trace Element Research, 2017)

Late Quaternary lake evolution in the Gaxun Nur basin, central Gobi Desert, China, based on quartz OSL and K‐feldspar pIRIR dating of paleoshorelines - Guoqiang Li; Fangliang Li; Ming Jin; Linlin She; Yanwu Duan; David Madsen; Leibin Wang; Fahu Chen (Journal of Quaternary Science, 2017)
Paleoenvironmental changes in the Gobi Desert of Mongolia are of global significance because fluvial and lacustrine deposits in the region constitute one of the dominant sources of Northern Hemisphere dust. A series of well‐preserved geomorphic shoreline features at different elevations around the Gaxun Nur basin, central Gobi Desert, indicate past fluctuations of the basin's terminal lake. We measured the exact elevation of shorelines in the basin using a Differential Global Positioning System, and found six shorelines at ∼24, ∼20, ∼18, ∼16, ∼15 m and ∼8 m above the modern basin floor. Quartz optically stimulated luminescence and K‐feldspar post‐infrared infrared stimulated luminescence methods were used to date these shoreline features. The reliability of the dates was confirmed using internal checks of luminescence characteristics and by comparing the quartz and K‐feldspar ages. Our results suggest a lake developed in the Gaxun Nur basin by at least ∼121 ka. Lake levels increased from ∼8 to ∼24 m from ∼121 to ∼85 ka. A 20–13‐m‐deep lake again formed in the basin between ∼8.4 and 0.8 ka. Monsoonal precipitation and temperature variations during Marine Isotope Stage 5 and the mid–late Holocene were the likely causes of paleolake formation and lake level fluctuations.

Estimate of Boundary-Layer Depth Over Beijing, China, Using Doppler Lidar Data During SURF-2015 - Meng Huang; Zhiqiu Gao; Shiguang Miao; Fei Chen; Margaret A. LeMone; Ju Li; Fei Hu; Linlin Wang (Boundary-Layer Meteorology, 2017)

Characterization of Gastric Microbiota in Twins - Quanjiang Dong; Yongning Xin; Lili Wang; Xinying Meng; Xinjuan Yu; Linlin Lu; Shiying Xuan (Current Microbiology, 2017)

Characterization of harpinXoo induced hypersensitive responses in non host plant, tobacco - Linlin Xie; Yue Liu; Hui Wang; Wenbo Liu; Rong Di; Weiguo Miao; Fucong Zheng (Journal of Plant Biochemistry and Biotechnology, 2017)

CD19+ Tim-1+ B cells are decreased and negatively correlated with disease severity in Myasthenia Gravis patients - Yong Zhang; Xiuying Zhang; Yan Xia; Xiao Jia; Hao Li; Yanyan Zhang; Zhen Shao; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; et al. (Immunologic Research, 2016)

Trivalent chromium alleviates oleic acid induced steatosis in SMMC-7721 cells by decreasing fatty acid uptake and triglyceride synthesis - Song Wang; Jian Wang; Xiaonan Zhang; Linlin Hu; Zhijia Fang; Zhiwei Huang; Ping Shi (BioMetals, 2016)

Phosphatidylinositol 3-phosphate, an essential lipid in Phytophthora sojae, enriches in the haustoria during infection - Linlin Chen; Wen Wang; Ying Hou; Yuren Wu; Honglian Li; Daolong Dou (Australasian Plant Pathology, 2016)

A novel short anionic antibacterial peptide isolated from the skin of Xenopus laevis with broad antibacterial activity and inhibitory activity against breast cancer cell - Siming Li; Linlin Hao; Wanguo Bao; Ping Zhang; Dan Su; Yunyun Cheng; Linyan Nie; Gang Wang; Feng Hou; Yang Yang (Archives of Microbiology, 2016)

Characterization of chromophoric dissolved organic matter and relationships among PARAFAC components and water quality parameters in Heilongjiang, China - Hongyang Cui; Jianhong Shi; Linlin Qiu; Yue Zhao; Zimin Wei; Xinglei Wang; Liming Jia; Jiming Li (Environmental Science and Pollution Research, 2016)

Allogeneic adipose-derived stem cells promote survival of fat grafts in immunocompetent diabetic rats - Jun Zhang; Xiaozhi Bai; Bin Zhao; Yunchuan Wang; Linlin Su; Peng Chang; Xujie Wang; Shichao Han; Jianxin Gao; Xiaolong Hu; Dahai Hu; Xiaoyan Liu (Cell and Tissue Research, 2016)

Structural controls on joint development in the southeastern margin of the Ordos basin - Linlin Wang; Bo Jiang; Jilin Wang; Zhenghui Qu; Run Chen (Arabian Journal of Geosciences, 2016)

Impact of atmospheric and oceanic conditions on the frequency and genesis location of tropical cyclones over the western North Pacific in 2004 and 2010 - Pan Song; Jiang Zhu; Zhong Zhong; Linlin Qi; Xiaodan Wang (Advances in Atmospheric Sciences, 2016)

Bioinformatics analyses of Shigella CRISPR structure and spacer classification - Pengfei Wang; Bing Zhang; Guangcai Duan; Yingfang Wang; Lijuan Hong; Linlin Wang; Xiangjiao Guo; Yuanlin Xi; Haiyan Yang (World Journal of Microbiology and Biotechnology, 2016)

Biosorption and degradation of decabromodiphenyl ether by Brevibacillus brevis and the influence of decabromodiphenyl ether on cellular metabolic responses - Linlin Wang; Litao Tang; Ran Wang; Xiaoya Wang; Jinshao Ye; Yan Long (Environmental Science and Pollution Research, 2016)

Gene transcript profiles in the desert plant Nitraria tangutorum during fruit development and ripening - Jia Wang; Zhenhua Dang; Huirong Zhang; Linlin Zheng; Tebuqin Borjigin; Yingchun Wang (Molecular Genetics and Genomics, 2016)

NF45 overexpression is associated with poor prognosis and enhanced cell proliferation of pancreatic ductal adenocarcinoma - Chunhua Wan; Chen Gong; Li Ji; Xiaorong Liu; Yayun Wang; Liang Wang; Mengting Shao; Linlin Yang; Shaoqing Fan; Yin Xiao; Xiaotong Wang; Manhua Li; et al. (Molecular and Cellular Biochemistry, 2015)

TIPE2 Play a Negative Role in TLR4-Mediated Autoimmune T Helper 17 Cell Responses in Patients with Myasthenia Gravis - Yong Zhang; Zhen Shao; Xiuying Zhang; Xiao Jia; Yan Xia; Yanyan Zhang; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; Linlin Fu; et al. (Journal of Neuroimmune Pharmacology, 2015)

The effects of commercial microbial agents (probiotics) on phytoplankton community structure in intensive white shrimp (Litopenaeus vannamei) aquaculture ponds - Betina Lukwambe; Linlin Qiuqian; Jinfeng Wu; Demin Zhang; Kai Wang; Zhongming Zheng (Aquaculture International, 2015)

Mechanical Behavior of Salt Caverns: Closed-Form Solutions vs Numerical Computations - Linlin Wang; Pierre Bérest; Benoît Brouard (Rock Mechanics and Rock Engineering, 2015)

Evaluation of MODIS Spectral Indices for Monitoring Hydrological Dynamics of a Small, Seasonally-Flooded Wetland in Southern Spain - Linlin Li; Anton Vrieling; Andrew Skidmore; Tiejun Wang; Antonio-Román Muñoz; Eren Turak (Wetlands, 2015)

MRP1 knockdown down-regulates the deposition of collagen and leads to a reduced hypertrophic scar fibrosis - Yan Li; Longlong Yang; Zhao Zheng; Jihong Shi; Xue Wu; Hao Guan; Yanhui Jia; Ke Tao; Hongtao Wang; Shichao Han; Jianxin Gao; Bin Zhao; et al. (Journal of Molecular Histology, 2015)

Seasonal and interannual variations of carbon exchange over a rice-wheat rotation system on the North China Plain - Chen Chen; Dan Li; Zhiqiu Gao; Jianwu Tang; Xiaofeng Guo; Linlin Wang; Bingcheng Wan (Advances in Atmospheric Sciences, 2015)

Association of interleukin-6 gene polymorphism with coronary artery disease: an updated systematic review and cumulative meta-analysis - Haifeng Hou; Chenglin Wang; Fengjing Sun; Linlin Zhao; Aishe Dun; Zheng Sun (Inflammation Research, 2015)

Pygo2 siRNA Inhibit the Growth and Increase Apoptosis of U251 Cell by Suppressing Histone H3K4 Trimethylation - Mingcong Li; Linlin Chao; Jian Wu; Hao Xu; Shanghan Shen; Sifang Chen; Xin Gao; Ning Yu; Zhanxiang Wang (Journal of Molecular Neuroscience, 2015)

Structural control on pore-fracture characteristics of coals from Xinjing coal mine, northeastern Qinshui basin, China - Jiegang Liu; Bo Jiang; Ming Li; Zhenghui Qu; Linlin Wang; Lei Li (Arabian Journal of Geosciences, 2015)

Heavy mineral assemblage characteristics and the Cenozoic paleogeographic evolution in southwestern Qaidam Basin - LinLin Li; ZhaoJie Guo; ShuWei Guan; SuPing Zhou; MingZhen Wang; YaNan Fang; ChenChen Zhang (Science China Earth Sciences, 2015)

Triple Recycling Processes Impact Systemic and Local Bioavailability of Orally Administered Flavonoids - Peimin Dai; Lijun Zhu; Feifei Luo; Linlin Lu; Qiang Li; Liping Wang; Ying Wang; Xinchun Wang; Ming Hu; Zhongqiu Liu (The AAPS Journal, 2015)

Highly sensitive fluorescence biosensors for sparfloxacin detection at nanogram level based on electron transfer mechanism of cadmium telluride quantum dots - Wanjun Liang; Shaopu Liu; Jing Song; Chenxia Hao; Linlin Wang; Dan Li; Youqiu He (Biotechnology Letters, 2015)

Erratum to: Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Decreased expression and activation of Stat3 in severe preeclampsia - Zhan Zhang; Xiaoqian Yang; Linlin Zhang; Zhenfeng Duan; Liting Jia; Peng Wang; Ying Shi; Ying Li; Junjun Gao (Journal of Molecular Histology, 2015)

Contrasting characteristics of the surface energy balance between the urban and rural areas of Beijing - Linlin Wang; Zhiqiu Gao; Shiguang Miao; Xiaofeng Guo; Ting Sun; Maofeng Liu; Dan Li (Advances in Atmospheric Sciences, 2015)

Effects of Superabsorbent Polymers on Infiltration and Evaporation of Soil Moisture Under Point Source Drip Irrigation - Linlin Yang; Yuguo Han; Peiling Yang; Chengzhi Wang; Shengmin Yang; Shuya Kuang; Hanzheng Yuan; Congying Xiao (Irrigation and Drainage, 2015)
The application of superabsorbent polymers (SAPs) in agriculture can enhance water use efficiency and ease water shortage in agriculture. In this study, by applying SAPs to the middle layer of the soil root zone, the effects of SAPs on moisture distribution during infiltration and evaporation under the condition of point source irrigation were investigated. The results show that during infiltration, the wetting front formed an accident change zone in the horizontal direction; in the bottom layer, the horizontal infiltration rate is greater than the vertical infiltration rate due to the effect of SAPs from the middle layer; the soil water content in the middle layer increased remarkably by 23.6%, higher than that in the surface and bottom layers; during evaporation, the soil water content changed significantly in the surface layer due to strong evaporation on the surface, it was largest and quite even in the SAP–soil mixture layer, and decreased the least in the bottom layer due to water storage in the mixture layer. Therefore, SAP application in the crop root layer is helpful to conserve soil water content in the crop root zone, inhibit evaporation of soil water in the lower layer and facilitate moisture conservation. Copyright © 2015 John Wiley & Sons, Ltd.

Identification and characteristics of imipenem-resistant Acinetobacter baumannii in surgical wards in a Chinese university hospital - Dalin Wang; Linlin Ma; Zhenyu Wu; Mingcheng Li; Xiaohan Li; Wei Zhang; Kun Chen (Infectious Diseases, 2015)

Significantly Decreased and More Variable Expression of Major CYPs and UGTs in Liver Microsomes Prepared from HBV-Positive Human Hepatocellular Carcinoma and Matched Pericarcinomatous Tissues Determined Using an Isotope Label-free UPLC-MS/MS Method - Tongmeng Yan; Song Gao; Xiaojuan Peng; Jian Shi; Cong Xie; Qiang Li; Linlin Lu; Ying Wang; Fuyuan Zhou; Zhongqiu Liu; Ming Hu (Pharmaceutical Research, 2015)

Detection and Analysis of CRISPRs of Shigella - Xiangjiao Guo; Yingfang Wang; Guangcai Duan; Zerun Xue; Linlin Wang; Pengfei Wang; Shaofu Qiu; Yuanlin Xi; Haiyan Yang (Current Microbiology, 2015)

Expression and Localization of Estrogen Receptor in Human Breast Cancer and Its Clinical Significance - Lv Li; Qimin Wang; Xiupeng Lv; Lin Sha; Huamin Qin; Lifen Wang; Linlin Li (Cell Biochemistry and Biophysics, 2015)

Study on Evolution Features and Spatial Distribution Patterns of Coastal Wetlands in North Jiangsu Province, China - Huajun Liao; Guosheng Li; Linlin Cui; Ninglei Ouyang; Yue Zhang; Shaohua Wang (Wetlands, 2014)

Overexpression of the PLAP-1 gene inhibits the differentiation of BMSCs into osteoblast-like cells - Jing Sun; Ting Zhang; Panpan Zhang; Linlin Lv; Yanzhi Wang; Jing Zhang; Shu Li (Journal of Molecular Histology, 2014)

An Emerging Water Contaminant, Semicarbazide, Exerts an Anti-estrogenic Effect in Zebrafish (Danio rerio) - Su Gao; Wei Wang; Hua Tian; Xiaona Zhang; Linlin Guo; Shaoguo Ru (Bulletin of Environmental Contamination and Toxicology, 2014)

A KPCA texture feature model for efficient segmentation of RADARSAT-2 SAR sea ice imagery - Linlin Xu; Jonathan Li; Alexander Wong; Cheng Wang (International Journal of Remote Sensing, 2014)

Healing of periodontal defects and calcitonin gene related peptide expression following inferior alveolar nerve transection in rats - Linlin Lv; Yanzhi Wang; Jing Zhang; Ting Zhang; Shu Li (Journal of Molecular Histology, 2014)

Cloning and functional analysis of two flavanone-3-hydroxylase genes from Reaumuria trigyna - Huirong Zhang; Lixia Zhao; Jia Wang; Linlin Zheng; Zhenhua Dang; Yingchun Wang (Acta Physiologiae Plantarum, 2014)

Transcriptomic analysis reveals key regulators of mammogenesis and the pregnancy-lactation cycle - YuanYuan Zhou; Wei Gong; JingFa Xiao; JiaYan Wu; LinLin Pan; XiaoNuan Li; XuMin Wang; WeiWei Wang; SongNian Hu; Jun Yu (Science China Life Sciences, 2014)

Construction and de novo characterization of a transcriptome of Chrysanthemum lavandulifolium: analysis of gene expression patterns in floral bud emergence - Yi Wang; He Huang; Yueping Ma; Jianxin Fu; Linlin Wang; Silan Dai (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Erratum to: Turbulent Transport of Momentum and Scalars Above an Urban Canopy - Linlin Wang; Dan Li; Zhiqiu Gao; Ting Sun; Xiaofeng Guo; Elie Bou-Zeid (Boundary-Layer Meteorology, 2014)

Turbulent Transport of Momentum and Scalars Above an Urban Canopy - Linlin Wang; Dan Li; Zhiqiu Gao; Ting Sun; Xiaofeng Guo; Elie Bou-Zeid (Boundary-Layer Meteorology, 2014)

The characteristics of epithelial cell rests of Malassez during tooth eruption of development mice - Yanzhi Wang; Linlin Lv; Xijiao Yu; Ting Zhang; Shu Li (Journal of Molecular Histology, 2014)

Isolation and characterization of a Δ1-pyrroline-5-carboxylate synthetase (NtP5CS) from Nitraria tangutorum Bobr. and functional comparison with its Arabidopsis homologue - Linlin Zheng; Zhenhua Dang; Haoyu Li; Huirong Zhang; Shubiao Wu; Yingchun Wang (Molecular Biology Reports, 2014)

Effects of Exogenous Salicylic Acid and Nitric Oxide on Physiological Characteristics of Perennial Ryegrass Under Cadmium Stress - Quanhui Wang; Xue Liang; Yuanjie Dong; Linlin Xu; Xiuwei Zhang; Jing Kong; Shuang Liu (Journal of Plant Growth Regulation, 2013)

Identification of Novel MicroRNA Signatures Linked to Experimental Autoimmune Myasthenia Gravis Pathogenesis: Down-Regulated miR-145 Promotes Pathogenetic Th17 Cell Response - Jiao Wang; Shuangshuang Zheng; Ning Xin; Changxin Dou; Linlin Fu; Xiuying Zhang; Jing Chen; Yanyan Zhang; Deqin Geng; Chenghua Xiao; Guiyun Cui; Xia Shen; et al. (Journal of Neuroimmune Pharmacology, 2013)

Lipopolysaccharides Reduce Adipogenesis in 3T3-L1 Adipocytes Through Activation of NF-κB Pathway and Downregulation of AMPK Expression - Lifeng Wang; Linlin Li; Xinjian Ran; Mei Long; Minfang Zhang; Yicun Tao; Xin Luo; Ye Wang; Yi Jiao; Xinmin Mao; Jun Ren (Cardiovascular Toxicology, 2013)

Potential short-term effects of yak and Tibetan sheep dung on greenhouse gas emissions in two alpine grassland soils under laboratory conditions - Yanjiang Cai; Xiaodan Wang; Weixin Ding; Linlin Tian; Hui Zhao; Xuyang Lu (Biology and Fertility of Soils, 2013)

Assessment of the SeaWinds scatterometer for vegetation phenology monitoring across China - Linlin Lu; Huadong Guo; Cuizhen Wang; Qingting Li (International Journal of Remote Sensing, 2013)

Vibrational mode analysis and heat capacity calculation of K2SiSi3O9-wadeite - Linlin Chang; Xi Liu; Hong Liu; Hiroshi Kojitani; Sicheng Wang (Physics and Chemistry of Minerals, 2013)

Fosmid library construction and end sequences analysis of the Pacific oyster, Crassostrea gigas - Linlin Zhang; Li Li; Fei Xu; Haigang Qi; Xiaotong Wang; Huayong Que; Guofan Zhang (Molluscan Research, 2013)

PEGylated Multi-Walled Carbon Nanotubes for Encapsulation and Sustained Release of Oxaliplatin - Linlin Wu; Changjun Man; Hong Wang; Xiaohe Lu; Qinghai Ma; Yu Cai; Wanshan Ma (Pharmaceutical Research, 2013)

Inducible regulation of GDNF expression in human neural stem cells - ShuYan Wang; Ping Ren; YunQian Guan; ChunLin Zou; LinLin Fu; Yu Zhang (Science China Life Sciences, 2013)

Expansivity and compressibility of wadeite-type K2Si4O9 determined by in situ high T/P experiments, and their implication - Linlin Chang; Zhiqiang Chen; Xi Liu; Hejing Wang (Physics and Chemistry of Minerals, 2013)

Large-scale collection and annotation of gene models for date palm (Phoenix dactylifera, L.) - Guangyu Zhang; Linlin Pan; Yuxin Yin; Wanfei Liu; Dawei Huang; Tongwu Zhang; Lei Wang; Chengqi Xin; Qiang Lin; Gaoyuan Sun; Mohammed M. Ba Abdullah; Xiaowei Zhang; et al. (Plant Molecular Biology, 2012)

Purification and characterization of an extracellular poly(3-hydroxybutyrate-co-3-hydroxyvalerate) depolymerase from Acidovorax sp. HB01 - Zhanyong Wang; Jia Gao; Linlin Li; Husheng Jiang (World Journal of Microbiology and Biotechnology, 2012)

Propagation characteristic of atmospheric responses to abnormal warm SST in the Kuroshio Extension in winter - Wang Xiaodan; Zhong Zhong; Liu Jianwen; Qi Linlin (Theoretical and Applied Climatology, 2012)

PTEN inhibits proliferation and functions of hypertrophic scar fibroblasts - Liang Guo; Liang Chen; Sheng Bi; Linlin Chai; Zengxiang Wang; Chuan Cao; Ling Tao; Shirong Li (Molecular and Cellular Biochemistry, 2012)

Effects of Aluminum Exposure on Serum Sex Hormones and Androgen Receptor Expression in Male Rats - Hao Sun; Chongwei Hu; Linlin Jia; Yanzhu Zhu; Hansong Zhao; Bing Shao; Nan Wang; Zhigang Zhang; Yanfei Li (Biological Trace Element Research, 2011)

Coseismic Slip from the 6 October 2008, M w6.3 Damxung Earthquake, Tibetan Plateau, Constrained by InSAR Observations - Xuejun Qiao; Shaomin Yang; Ruilin Du; Linlin Ge; Qi Wang (Pure and Applied Geophysics, 2011)

Variable length LMS adaptive filter for carrier phase multipath mitigation - Huicui Liu; Xiaojing Li; Linlin Ge; Chris Rizos; Feixue Wang (GPS Solutions, 2011)

Left ventricular hypertrophy induced by abdominal aortic banding and its prevention by angiotensin receptor blocker telmisartan—a proteomic analysis - Li Liu; Wen Wang; Xianmin Meng; Jiuming Gao; Haiying Wu; Peihe Wang; Weichun Wu; Linlin Wang; Liyuan Ma; Weiguo Zhang (Journal of Physiology and Biochemistry, 2010)

Ice phase as an important factor on the seasonal variation of polycyclic aromatic hydrocarbons in the Tumen River, Northeastern of China - Linlin Cong; Yingyu Fang; Miao He; Xinshun Wang; Narayanan Kannan; Donghao Li (Environmental Science and Pollution Research, 2010)

Fibronectin and asialoglyprotein receptor mediate hepatitis B surface antigen binding to the cell surface - Jing Yang; Feng Wang; Linlin Tian; Jing Su; Xiangqian Zhu; Li Lin; Xiaoran Ding; Xuejun Wang; Shengqi Wang (Archives of Virology, 2010)

Regulation of Cell Division and Growth in Roots of Lactuca sativa L. Seedlings by the Ent-Kaurene Diterpenoid Rabdosin B - Lan Ding; Hongwei Jing; Bo Qin; Linlin Qi; Jing Li; Tao Wang; Guoan Liu (Journal of Chemical Ecology, 2010)

Distribution of borehole temperature at four high-altitude alpine glaciers in Central Asia - Yaping Liu; Shugui Hou; Yetang Wang; Linlin Song (Journal of Mountain Science, 2009)

Interpollutant emission trading of ozone precursors in southeast Texas - Linlin Wang; David Allen; Elena McDonald-Buller (Clean Technologies and Environmental Policy, 2009)

An improved method for modeling spatial distribution of δD in surface snow over Antarctic ice sheet - Yetang Wang; Shugui Hou; Bjorn Grigholm; Linlin Song (Chinese Geographical Science, 2009)

The expression of analgesic-antitumor peptide (AGAP) from Chinese Buthus martensii Karsch in transgenic tobacco and tomato - Linlin Lai; Tingting Huang; Yi Wang; Yanfeng Liu; Jinghai Zhang; Yongbo Song (Molecular Biology Reports, 2009)

Growth inhibition induced by transforming growth factor-β1 in human oral squamous cell carcinoma - Xiumei Wang; Wenjing Sun; Jing Bai; Linlin Ma; Yang Yu; Jingshu Geng; Jiping Qi; Zhongcheng Shi; Songbin Fu (Molecular Biology Reports, 2009)

Evaled Expression of ICAM-1 and Its Ligands in the Rat Spinal Cord Following Lipopolysaccharide Intraspinal Injection - Junling Yang; Min Fei; Yangyang Gu; Linlin Sun; Zhiyun Ben; Dan Zhou; Jianping Chen; Youhua Wang; Ping Wang; Aiguo Shen; Chun Cheng (NeuroMolecular Medicine, 2008)

The Prevalence of Type 2 Diabetes and Hypertension in Uygur and Kazak Populations - Yicun Tao; Xinmin Mao; Zijing Xie; Xinjian Ran; Xiaoyan Liu; Ye Wang; Xin Luo; Mengying Hu; Wenning Gen; Minfang Zhang; Tao Wang; Jun Ren; et al. (Cardiovascular Toxicology, 2008)

Phytotoxic Effects of Leukamenin E (an ent-kaurene diterpenoid) on Root Growth and Root Hair Development in Lactuca sativa L. seedlings - Lan Ding; Linlin Qi; Hongwei Jing; Juan Li; Wei Wang; Tao Wang (Journal of Chemical Ecology, 2008)

Lipopolysaccharide-Induced Upregulation of Tumor Necrosis Factor-α (TNF-α) and TNF Receptors in Rat Sciatic Nerve - Youhua Wang; Dan Zhou; Qin Shen; Chun Cheng; Hai-ou Liu; Yongwei Qin; Linlin Sun; Feng Xiao; Jian Zhao; Aiguo Shen (Journal of Molecular Neuroscience, 2007)

Bioaugmentation of Bromoamine Acid Degradation with Sphingomonas xenophaga QYY and DNA Fingerprint Analysis of Augmented Systems - Yuanyuan Qu; Jiti Zhou; Jing Wang; Zhiyong Song; Linlin Xing; Xiang Fu (Biodegradation, 2006)

Preliminary study on the relationship between osteoporosis and trace elements with rat models - Huiling Nie; Linlin Qin; Weizhi Tian; Bangfa Ni; Ande Bao; Pingsheng Wang (Biological Trace Element Research, 1999)